Public transparency and physicochemical standardization in the regulation of PMMA dermal fillers: a comparative analysis of FDA, EU MDR, and ANVISA frameworks - Evilasio Anisio Costa Filho; Albaniza Alves Tavares; Antonio Gilson Barbosa de Lima; Victhor Alexandre Vilarins Cardoso da Silva; Stela Candioto Melchior; Maria Glória Vicente; Marcus Vinicius Lia Fook; Suédina Maria de Lima Silva (Regulatory Toxicology and Pharmacology, 2026)

Influence of thermal treatment on the petrophysical and microstructural properties of saturated limestone - Natalino da Silva Souza; Jéssica Nascimento Pereira; Igor Alexandre Rocha Barreto; Marcondes Lima da Costa; Daniel Nobre Nunes da Silva; Pedro Tupã Pandava Aum; Cláudio Regis dos Santos Lucas (Geothermics, 2026)

Integrating the Classical and Molecular Approaches Toward Passion Fruit Resistance Against CABMV - Julie Anne Vieira Salgado de Oliveira; Alexandre Pio Viana; Natan Ramos Cavalcante; Eileen Azevedo Santos; Marcela Santana Bastos Boechat; Débora Souza Mendes; Luis Carlos Loose Coelho; Flavia Alves da Silva; Joameson Antunes Lima; Thays Correa Costa (Plant Molecular Biology Reporter, 2026)
Passion fruit, a tropical species cultivated across various nations, faces challenges in expanding its cultivation areas due to several constraints, including total crop losses, caused by the fruit woodiness virus. In Brazil, this condition is attributed to the cowpea aphid-borne mosaic virus (CABMV), and currently, no passion fruit cultivars are resistant to this virus. This study integrates classical breeding and molecular analyses to identify CABMV-resistant plants in a backcross population of Passiflora , addressing the need for durable resistance in commercial passion fruit and improving selection efficiency for breeding programs. This research aimed to assess the resistance to CABMV within the third backcross generation (BC 3 ) of passion fruit, employing both phenotypic and genotypic methodologies to identify the most promising families and genotypes. The study utilized a randomized block design and a rating scale to evaluate the manifestation of virus symptoms, facilitating the estimation of the area under the disease progress curve. The 'disease resistance' trait was analyzed using mixed models to estimate variance components through Restricted Maximum Likelihood (REML) and to predict selection gains via Best Unbiased Linear Prediction (BLUP). Twenty-seven microsatellite markers (SSR) were applied to determine the genetic distances among 95 genotypes within the studied population. These SSR markers were effective in differentiating the evaluated groups. Among the top 30 genotypes ranked for CABMV resistance, four genotypes from different families exhibited superior traits, making them suitable candidates for the next backcross generation.

Genetic deletion of MrgD receptor disrupts cardiac protein homeostasis in mice - Beatriz Alexandre-Santos; Luiza Mazzali Ferraz; Ana Beatriz Proença; Nícia Pedreira Soares; Guilherme dos Santos Reis; Maria Eduarda Lima da Silva; D’Angelo Carlo Magliano; Maria Jose Campagnole-Santos; Antonio Claudio Lucas da Nóbrega; Robson Augusto Souza Santos; Eliete Dalla Corte Frantz (Molecular Biology Reports, 2026)
Background Cardiovascular diseases are the leading cause of death worldwide. An important mechanism involved is the disruption in protein homeostasis by overactivation of the classical axis of the renin-angiotensin system. The counterregulatory axis counteracts these effects; however, the MrgD receptor has recently been described, and its effects are unknown. Thus, this study aims to evaluate the impact of MrgD deficiency on cardiac protein homeostasis. Methods 16-week-old wild-type (WT) and MrgD knockout (MrgD KO) male C57BL/6J mice were evaluated for systolic blood pressure (SBP), cardiac morphology, MDA levels, carbonyl content, and protein homeostasis markers. Results SBP and heart mass remained unaltered. MrgD deficiency increased left ventricular mass and led to cardiac atrophy by reduced left ventricular wall thickness and cardiomyocyte cross-sectional area. Collagen (types 1 and 3) deposition and MMP-2 cardiac protein expression were elevated in MrgD KO. Genetic deletion of MrgD increased NOX2, NOX4, and ERO1α cardiac protein expression. MDA levels were similar between groups, and carbonyl content was higher in MrgD KO. GRP78, CHOP, MuRF-1, Atrogin-1, and polyubiquitinated proteins were increased in MrgD KO mice, indicating a loss of protein homeostasis. Conclusions The genetic deletion of MrgD promoted cardiac remodeling and disrupted protein homeostasis, with increased pro-oxidative response and ER stress. This was associated with protein degradation by the activation of the ubiquitin-proteasome pathway.

Intraspecific variation in Bothrops neuwiedi snake venom: Influence of age and sex - Eduardo Oliveira Venancio de Lima; Juan David Gutiérrez Marín; Lídia Jorge Tasima; Caroline Serino-Silva; Jackson Gabriel Miyamoto; Alexandre Keiji Tashima; Kathleen Fernandes Grego; Anita Mitico Tanaka-Azevedo (Toxicon, 2026)

Morphological and chemical characterisation of alluvial gold: A revival of Castelo's history of gold mining, Espírito Santo, Brazil, and a new exploration perspective - Gabriel Piassi Tosi; Alexandre Raphael Cabral; Miguel Tupinambá; Andre Diego Lima de Montalvão Barretto; Gláucia Queiroga (Journal of Geochemical Exploration, 2026)

Flexural behavior and stability of continuous composite beams using NSS and HSS castellated I-sections and slabs of NSC and UHPC - Vinicius Moura de Oliveira; Vinicius Brother dos Santos; Alexandre Rossi; Luciano Rodrigues Ornelas de Lima; Carlos Humberto Martins (Engineering Structures, 2026)

Topography- and depth-driven variability of β-glucosidase activity in Amazonian Forest soils (Brazil): A machine learning and structural equation modeling approach - Gizachew Ayalew Tiruneh; Ciro Abbud Righi; Jefferson Lordello Polizel; Vinicius Gonçalves; Carlos Rodrigues Pereira; Fernando Dini Andreote; Rafael Lima Oliveira; Jean Jesus Macedo Novais; Marcelo Henrique Procópio Pelegrino; Jose Alexandre Melo Dematte; Marcelino Carneiro Guedes; Ranjith P. Udawatta (CATENA, 2026)

Collaborative monitoring networks refine jaguar habitat suitability and reveal conservation gaps in the Brazilian Cerrado - Lucas Gonçalves da Silva; Marco Aurélio Mendes Elias; Juliana Silveira dos Santos; Anah Tereza de Almeida Jácomo; Douglas Santos; Ennio Painkow Neto; Fabio Hudson Souza Soares; Gabriel Caputo de Carvalho; Giselle Bastos Alves; Gonzalo Barquero; Igor Fagundes Perfeito; Marina Motta de Carvalho; et al. (Biological Conservation, 2026)

Diagnostic case report of aspergillosis (Aspergillus sp.) (Michelli, 1729) in budgerigar (Melopsittacus undulatus) (Shaw, 1805) - Cauê Bastos Tertuliano dos Santos; Heloísa Coppini de Lima; Heloísa Máximo Ribeiro; Iolanda Simões Braga; Alexandre Battazza; Mariana Nogueira Gonçalves; Sheila Canevese Rahal; Adriano Sakai Okamoto; Raphael Lúcio Andreatti Filho (Veterinary Research Communications, 2026)
Aspergillosis is a disease caused by species of fungi of the genus Aspergillus sp. and is important for wild birds. A female budgerigar ( Melopsittacus undulatus ) presenting with dyspnea, apathy, anorexia, ruffled feathers, and drowsiness with abnormal tail movements, suggesting respiratory distress, was treated in the emergency room at the Center for Wildlife Medicine and Research. The animal died and the body was sent to the Ornithopathology Laboratory. Histopathological examination revealed multifocal areas of mixed inflammatory infiltrate associated with septate fungal hyphae, with dichotomous branching at 45º and a thickness between 2 and 5 μm in the lungs. Microbiological culture confirmed that this was a case of aspergillosis. After a few weeks, the contact animal was brought to the university with respiratory symptoms. The animal underwent imaging tests, and after changes were found on X-rays, it was treated with antifungal medication and showed clinical improvement. Ante-mortem diagnosis and treatment of aspergillosis are still very difficult, so prevention remains the best approach. This highlights the urgent need for better diagnostic tools and the establishment of more effective therapeutic strategies.

The Missing Branches of the Bee Tree of Life: Addressing Global Darwinian Shortfalls and Their Drivers - Felipe Walter Pereira; Matheus Lima Araujo; Anderson Lepeco; Bruno Ferreira Marques; Hugo Bampi; Lucas Jardim; Luísa Vareira; Luisa G. Carvalheiro; Thiago F. Rangel; José Alexandre F. Diniz Filho (Journal of Biogeography, 2026)
Aim Estimate the Darwinian shortfall (i.e., the lack of knowledge about phylogenetic relationships) of bees worldwide, as well as identify their drivers. Location Global. Taxon Bees (Hymenoptera, Anthophila). Methods We built phylogenies for over 12,000 bee species, combining the most comprehensive phylogeny and an algorithm with random solutions to insert missing lineages. The Darwinian shortfall was quantified as the Phylogenetic Diversity (PD) deficit, the ratio of inserted branch lengths at the assemblage level. We identified potential ecological and socioeconomic drivers of the Darwinian shortfall using Simultaneous Autoregressive (SAR) models. Results The highest shortfalls were identified in the Southern Hemisphere. Mean species range size and species richness were the strongest drivers, as smaller ranges and higher richness were associated with higher deficits. Per capita GDP was negatively associated with PD deficits, while population and road densities showed positive but weak effects. Sample completeness had a weaker effect, limited by missing occurrence data in many regions. Main Conclusions Our findings underscore the need for integrative efforts combining taxonomy, data digitization, adequate research investments, and targeted sampling, especially in the Global South. Overcoming the Darwinian shortfall is essential to develop robust strategies to preserve the Tree of Life, especially for one of the most important groups of pollinators while facing the ongoing biodiversity crisis.

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Cover crops shape soil microbiome and ecological interactions in the soybean rhizosphere under long-term no-till - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Nariane de Andrade; Rafael Lima Oliveira; Victor Lucas Vieira Prudêncio Araújo; Felipe Martins do Rêgo Barros; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Soil and Tillage Research, 2026)

The alginate-carrageenan blend exhibits good printability and supports adhesion of ovarian stromal cells in bioprinted scaffolds - Solano Dantas Martins; Iana Lira Nogueira; Maria Alice Felipe Oliveira; Pedro Everson Alexandre De Aquino; Marjory Lima Holanda Araújo; Vânia Marilande Ceccatto; Valdevane Rocha Araújo (Reproductive Biology, 2026)

Phenylmercury induces structural and functional alterations on hemoglobin: From isolated protein to a biological model - Sheila Oliveira de Souza; Marcos Vinicius dos Santos Sales; Maiara Ingrid Cavalcante Queiroz; Ana Flávia Silva Lima; Wallison dos Santos Dias; Laís Farias Azevedo de Magalhães Oliveira; Josefa Gerlane Silva; Júlio Cosme Santos da Silva; Eduardo Jorge da Silva Fonseca; Letícia Anderson; Alexandre Urban Borbely; Rafael David Souto de Azevedo; et al. (Journal of Hazardous Materials, 2026)

Changes in the taxonomic, functional and phylogenetic diversity of fish assemblages on beaches with contrasting morphodynamic characteristics - Alexandre da Gama Fernandes Vieira-Júnior; Éden Hávila Lima Guedes; André Luiz Machado Pessanha (Estuarine, Coastal and Shelf Science, 2026)

Mapping the unknown: Dark diversity and Wallacean gaps in Neotropical bats (Mammalia: Chiroptera) - Rafaela Jemely Rodrigues Alexandre; Leticia Lima Correia; María Magdalena Ramírez-Martínez; Livia Leon Paniagua; M. Alejandra Camacho; Albert David Ditchfield; Ludmilla Moura de Souza Aguiar; Thiago Bernardi Vieira (Biological Conservation, 2026)

Productive, physiological, and biochemical responses of elephant grass ‘BRS Capiaçu’ (Pennisetum purpureum Schumach.) under different water regimes with brackish water in a semi-arid environment - Lara Rosa de Lima-Silva; Lady Daiane Costa de Sousa Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Wagner Martins dos Santos; Pedro Paulo Santos de Souza; Luciana Sandra Bastos de Souza; Cleber Pereira Alves; Agda Raiany Mota dos Santos; Ênio Farias de França e Silva; Hugo Rafael Bentzen Santos; Wilma Roberta dos Santos; Carlos André Alves de Souza; et al. (Physiology and Molecular Biology of Plants, 2026)
The seasonality of forage production is one of the main challenges in semi-arid regions, where environmental conditions limit agricultural productivity. One promising option is the use of elephant grass ‘BRS Capiaçu’, together with deficit irrigation. This study evaluated the impact of different irrigation depths with brackish water (50%, 75%, 100% and 125% of the reference evapotranspiration – ET 0 ) on the productive, physiological, photochemical and biochemical aspects of ‘BRS Capiaçu’ over two cycles. Irrigation with 50% of the ET 0 resulted in lower rates of net photosynthesis (P n ), with a reduction in photosystem II quantum yield (ΔF/Fm’), qP, NPQ and the electron transport rate (ETR), in addition to greater activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), indicating oxidative stress. The depths of 50% and 100% of the ET 0 resulted in greater dry matter production, for Cycles 1 and 2, respectively, demonstrating the resilience of the crop to water stress, attributed to such mechanisms of acclimatisation as a reduction in transpiration (T r ) and an increase in water use efficiency. These physiological changes were more obvious during Cycle 2, in which the crop was subjected to lower rainfall (47.8 mm), while salt stress was also more pronounced during this period, in response, the plants showed less water loss through transpiration and larger WUE inst . It was concluded that ‘BRS Capiaçu’ has a high capacity for acclimatisation to semi-arid conditions, and stands out as a viable alternative for mitigating the seasonality of forage production and promoting sustainable livestock farming in the region.

A combination of resilient practices maximizes productivity and water, carbon, and nutrient stocks in forage species systems in the Brazilian semi-arid region - Marcelo José da Silva; Wilma Roberta dos Santos; Cleber Pereira Alves; Alexandre Maniçoba da Rosa Ferraz Jardim; Agda Raiany Mota dos Santos; Álefe Chagas de Lima Costa; Carlos André Alves de Souza; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; João Pedro Alves de Souza Santos; Ênio Farias de França e Silva; Fleming Sena Campos; et al. (International Journal of Plant Production, 2026)
Adopting resilient practices is crucial to balancing food production and crop sustainability in semiarid regions. Therefore, adopting systems that provide greater stocks of water, carbon, and nutrients at the soil-plant interface is crucial. The objective of this study was to assess water, carbon, and nutrient stocks in the soil-plant systems of irrigated forage crops in the semiarid region of Brazil. The study was conducted in Serra Talhada, Pernambuco, Brazil. Four production cycles were evaluated between January 2017 and January 2022, comprising seven cropping systems: pigeon pea (S1), millet (S2), sorghum (S3), cactus forage (S4), cactus forage-sunflower-pigeon pea (S5), cactus forage-sorghum-millet (S6), and cactus forage-sorghum (S7). The following parameters were evaluated: fresh matter (FM) and dry matter (DM) productivity, as well as water, organic carbon (OC), and nutrient (N, P, K + , Ca 2+ , Mg 2+ , and Na + ) stocks in the plant and soil at depths of 0–20 and 20–40 cm. The intercropping systems presented the highest mean values for each of the plant variables. Among the single systems, forage cactus did not differ from the intercropped systems for FM, plant stocks of P, Ca 2+ , Mg 2+ , and water. The single sorghum presented higher values for plant DM (44.0 Mg ha −1 ) and plant OC (18.7 Mg ha −1 ). For soil variables, only the levels of P, K + , Na +, and OC showed significant differences ( p < 0.05). The single forage cactus had the highest average soil OC value (14.5 Mg ha −1 ). The cactus-sorghum intercrop system appears to offer the best balance between productivity and water, OC, and nutrient reserves. Among the isolated systems, forage cactus stores the largest amounts of OC in the soil, while sorghum stands out for accumulating carbon in the plants. Studies on the sustainability of forage species should be encouraged to improve the development of agricultural systems.

El Niño Reduces Beta Diversity of Fish Assemblages Across a Large Subtropical Coastal Lagoon - Yan Gonçalves Gowert; Rafael Lima Oliveira; Fabiano Correa; Thiago dos Santos Tuchtenhagen; Marcelo Bassols Raseira; Valéria Marques Lemos; Alice Marlene Grimm; Alexandre Miranda Garcia (Estuaries and Coasts, 2026)
The El Niño –Southern Oscillation (ENSO) profoundly alters climatological and hydrological conditions, reshaping environmental gradients and ecological dynamics in riverine, estuarine, and coastal ecosystems. We hypothesized that El Niño events would promote homogenization of fish assemblages and reduce β-diversity, whereas La Niña conditions would enhance habitat differentiation and increase β-diversity. To test this hypothesis, we investigated variations in fish β-diversity across a freshwater–estuarine–marine gradient in the Patos Lagoon, southern Brazil, under La Niña , El Niño , and neutral climatic conditions. We analyzed total β-diversity and its local and species contribution components in relation to environmental variability associated with ENSO phases. The results revealed a clear pattern of homogenization between the estuarine and marine environments during El Niño , characterized by increased species sharing and reduced taxonomic differentiation. Species sharing between these regions increased from 10 to 13 species during La Niña and neutral conditions, respectively, to 18 species during El Niño . In contrast, La Niña promoted stronger habitat compartmentalization, resulting in higher total β-diversity (0.558) than El Niño (0.538) and neutral conditions (0.528), indicating greater spatial heterogeneity in fish assemblages. These findings support our hypothesis that ENSO-driven changes in environmental gradients shape fish β-diversity, with El Niño promoting biotic homogenization and La Niña enhancing habitat differentiation. As ENSO events are projected to become more frequent and intense, these processes may have important implications for the biodiversity and structural organization of subtropical coastal lagoons and other estuarine ecosystems.

Cover crops legacy modulates soybean rhizosphere microbiome across phenological stages - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Rafael Lima Oliveira; Nariane de Andrade; Danilo Ferreira da Silva; Mísia Souza Vieira; Victor Lucas Vieira Prudêncio Araújo; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Applied Soil Ecology, 2026)

Endoplasmic reticulum stress is associated with cardiac effects of bisphenol S independently of a high-fat diet - Beatriz Alexandre-Santos; Guilherme dos Santos Reis; Luiza Mazzali Ferraz; Maria Eduarda Lima da Silva; Gabriel Ferreira Lima; Fernanda Carla Ferreira Brito; Milena Barcza Stockler-Pinto; Antonio Claudio Lucas da Nóbrega; Leandro Miranda-Alves; D’Angelo Carlo Magliano; Eliete Dalla Corte Frantz (Histochemistry and Cell Biology, 2026)
Obesity and endocrine disruptors (EDs) promote endoplasmic reticulum (ER) stress, a mechanism associated with cardiovascular diseases. Among EDs, BPS is widely used in consumer products. Whether BPS promotes cardiac ER stress, either alone or combined with a high-fat diet, remains unclear. Male C57BL/6 mice were assigned to a standard chow diet (SC—15 kJ/g), SC+BPS (SCB), high-fat diet (HF—21 kJ/g), or HF+BPS (HFB), receiving BPS (25 μg/kg/day) through their drinking water for 12 weeks. Body mass (BM), lipid profile, cardiac risk ratio, heart mass, and cardiac ER stress, apoptosis, and oxidative stress markers were assessed. A high-fat diet intake increased BM gain, total cholesterol, cardiac risk ratio, and heart mass compared with standard chow diet intake. These parameters were higher in the SCB group than in the SC group. ER stress (GRP78, ATF4, and CHOP protein expression), pro-apoptotic (BAX protein expression and caspase 3 immunostaining), and pro-oxidative (NOX2 and NOX4 protein expression as well as MDA levels) markers were elevated in high-fat diet-fed animals compared with standard chow-fed animals. BPS exposure increased these parameters in standard chow-fed animals. High-fat diet intake reduced BCL2 expression and increased the BAX/BCL2 ratio compared with standard chow diet intake. BPS exposure increased BCL2 expression in standard chow-fed animals and increased the BAX/BCL2 ratio in high-fat diet-fed animals. ER stress appears to play a role in the cardiac effects of BPS. BPS exposure exacerbated the high-fat diet-induced pro-apoptotic response.

From canopy to soil: subterranean galleries of arboreal termites amplify soil respiration and carbon dynamics in the Caatinga - Mário Herculano de Oliveira; Maria Avany Bezerra-Gusmão; Bartolomeu Israel de Souza; Caik Oliveira de Miranda; Derick Lira; Maria Lacerda; Alexandre Fonseca D'Andrea; Marllon Rinaldo de Lima Andrade; José João Lelis Leal de Souza (Journal of Arid Environments, 2026)

Therapeutic potential of Syzygium cumini L. extract in treating anxiety in adult zebrafish (Danio rerio): Behavioral, toxicological, and molecular evidence involving the GABAergic and serotonergic pathways - Cássia Taiane Viana Moraes; Gabriel Martins de Araújo Sousa; Ariel Falanga de Oliveira; Igor de Codes Soares; Paula Ticiani Alves de Souza; Lucca Moura de Freitas; Mário Guilherme de Paula Sales; Vitória Isabele Gomes Ferreira; Paula Alexandre de Freitas; Saulo Chaves Magalhães; Katarine Ferreira da Silva; Luís Sérgio Fonteles Duarte; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Correction: Supplementing the diet of Nile tilapia (Oreochromis niloticus) with microalgae Nannochloropsis oculata and Phaeodactylum tricornutum enhanced immune function, lipid profile, and resistance to Edwardsiella tarda infection - Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Paola Capistrano dos Santos; Maria Clara Miguel Libanori; Gracienhe Gomes dos Santos; Ana Paula de Souza; Alexandre Vaz da Silva; Cláudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Aline Brum Figueredo Ruschel; Rafael Sales; Fábio de Farias Neves; et al. (Veterinary Research Communications, 2026)

Supplementing the diet of Nile tilapia (Oreochromis niloticus) with microalgae Nannochloropsis oculata and Phaeodactylum tricornutum enhanced immune function, lipid profile, and resistance to Edwardsiella tarda infection - Domickson Silva Costa; Jucimauro de Araújo Pereira Júnior; Paola Capistrano dos Santos; Maria Clara Miguel Libanori; Gracienhe Gomes dos Santos; Ana Paula de Souza; Alexandre Vaz da Silva; Cláudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Aline Brum Figueredo Ruschel; Rafael Sales; Fábio de Farias Neves; et al. (Veterinary Research Communications, 2026)
The aim of the present study was to evaluate the effects of dietary supplementation with the microalgae Nannochloropsis oculata and Phaeodactylum tricornutum , either separately or in combination, on growth performance, lipid profile, haematoimmunological parameters, and resistance to Edwardsiella tarda infection in Nile tilapia ( Oreochromis niloticus ). A total of 960 juvenile Nile tilapia (2.87 ± 0.68 g and 5.65 ± 0.16 cm) were allocated to 24 experimental units ( n = 40) and fed six experimental diets for 60 days: DC 0% (no microalgae inclusion), DN 0.5% (0.5% N. oculata ), DN 1% (1% N. oculata ), DP 0.5% (0.5% P. tricornutum ), DP 1% (1% P. tricornutum ), and DPN 1% (0.5% N. oculata + 0.5% P. tricornutum ). After the feeding period, fish were challenged with E. tarda (2 × 10⁸ CFU mL⁻¹). Microalgal inclusion increased significantly ( p < 0.05) dietary contents of phenolic compounds, flavonoids, tannins, and antioxidant potential of diets without affecting fish growth. The DP 1% and DPN 1% diets increased significantly ( p < 0.05) eicosapentaenoic and docosahexaenoic acid levels and reduced monounsaturated fatty acids and ∑saturated fatty acids in muscle, thereby improving the lipid profile and flesh quality. Following infection, reductions in erythrocytic parameters were observed, along with increases in lymphocyte, monocyte, basophil, neutrophil, and thrombocyte counts, as well as higher ( p < 0.05) agglutination and antimicrobial titres, total plasma protein, and immunoglobulin levels in the DP 1% and DPN 1% groups. Survival was higher in the microalgae-supplemented groups, particularly in DPN 1% (91.67 ± 1.8%) compared with the control (65.0 ± 2.0%). Supplementation with DP 1% and DPN 1% improved haematoimmunological responses, lipid composition, and resistance to E. tarda in Nile tilapia.

N-acetylcysteine mitigates oxidative stress and reduces alveolar bone damage on experimental periodontitis in rats - Ana Paula de Andrade Silva; Erick Alves dos Santos; Deborah Ribeiro Frazão; Vinicius Ruan Neves dos Santos; José Mario Matos-Sousa; Beatriz Risuenho Peinado; Deiweson Souza-Monteiro; Wallacy Watson Pereira Melo; Zuleni Alexandre da Silva; Everton Luiz Pompeu Varela; Jorddy Neves da Cruz; Carina Maciel da Silva-Boghossian; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study evaluated the effect of N-acetylcysteine ​​on oxidative biochemistry and bone damage during the development of ligature-induced experimental periodontitis in rats. The rats were divided into three groups (n = 8/group): control, experimental periodontitis (EP), or experimental periodontitis plus daily N-acetylcysteine administration (EP + NA) (100 mg/kg/day). Periodontitis was induced by bilateral silk ligatures on the mandibular first molars for 14 days. The antioxidant capacity of N-acetylcysteine ​​was measured by (2,2-azinobis [3-ethylbenzothiazoline-6-sulfonate] (ABTS• +) and 1,1-dipheny-2-picrylhydrazyl (DPPH•) assays. Gingival samples were collected for analysis of oxidative parameters, while mandibles were used for histopathological evaluations of inflammation and collagen content, as well as for micro-computed tomography assessments of bone quality and vertical bone loss. Data were analyzed by Analysis of Variance (ANOVA), Multivariate Analysis of Variance (MANOVA), and Pearson’s correlation ( p

Embryo-fetal and early-life protein restriction programs pulmonary structure and molecular parameters in both dams and female offspring - Flávia Alessandra Maciel; Matheus Naia Fioretto; Luisa Annibal Barata; Isabelle Tenori Ribeiro; Vinícius Alexandre de Andrade Felipe; Lucas Sobrinho Lemos; Maycon Tavares Emílio-Silva; Tainá Dorte da Silva; Flávia Karina Delella; Clélia Akiko Hiruma Lima; Wellerson Rodrigo Scarano; Luis Antonio Justulin (Molecular and Cellular Biochemistry, 2026)
The Developmental Origins of Health and Disease (DOHaD) theory proposes that adverse conditions during critical developmental windows can increase disease susceptibility throughout life. Maternal protein restriction (MPR) is a well-established experimental model that impairs offspring lung development, affecting pulmonary structure, metabolism, and molecular pathways from early life to aging. However, little is known about its effects on maternal pulmonary health and female offspring, representing an important gap in the literature. Therefore, this study investigated the effects of MPR on lung structure and metabolism in dams at the end of lactation and in female offspring at weaning. Sprague Dawley rats were fed either a control diet (17% protein) or a low-protein diet (6% protein) throughout gestation and lactation. Dams and female offspring were euthanized at weaning, and pulmonary alterations were assessed through histological, biochemical, molecular, zymographic, and in silico analyses. MPR increased collagen deposition, mast cell density, and Acta expression, while reducing reticular fibers in maternal lungs, accompanied by a trend toward increased lipid peroxidation. In female offspring, MPR reduced alveolar diameter, mast cell density, and reticular fibers, while increasing collagen deposition, MMP-2 activity, PI3K and MyoD expression, and decreasing mTOR expression as well as Nduf transcript levels. No significant alterations in antioxidant parameters were observed in either dams or offspring. Integrative analyses indicate that MPR promotes structural remodeling in maternal lungs, potentially compromising ventilatory function. In female offspring, MPR induces delayed pulmonary development, extracellular matrix remodeling, alterations in smooth muscle-related pathways, and disturbances in energy metabolism. Together, these findings demonstrate that maternal protein resQ1triction adversely affects pulmonary health in both dams and female offspring, revealing potential mechanisms linking early-life nutritional adversity to the developmental origins of respiratory disease.

Legacy P from rock phosphate promotes growth of eucalypt coppice stands without further P application - Adam da Cruz Rodrigues; Cassio Rafael Costa dos Santos; Maria Leidiane Reis Barreto; Felipe Tavares Lima; Antonio Leite Florentino; Alexandre de Vicente Ferraz; José Leonardo de Moraes Gonçalves (Forest Ecology and Management, 2026)

A comparison of two vitrification methods and the effect of dimethyl sulfoxide in vitrification solution for cryopreservation of Euterpe edulis Martius (Arecaceae) - Débora Pellanda Fagundes; Joana Silva Costa; Ingridh Medeiros Simões; Simone Wellita Simão de Carvalho; Caroline Palacio de Araujo; Lana Laene Lima Dias; Eduardo Alves; Elias Terra Werner; Edilson Romais Schmildt; Amir Ali Khoddamzadeh; Wagner Campos Otoni; Rodrigo Sobreira Alexandre (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)
Euterpe edulis Martius (Arecaceae) is a native species of the Atlantic Forest hotspot with ecological and economic relevance. Its fruits contribute to biodiversity maintenance by feeding birds and mammals and are valued for their antioxidant properties and applications in the food and cosmetic industries. However, habitat loss and propagation constraints have contributed to the threatened status of this species, reinforcing the need for complementary ex situ conservation strategies. Thus, this study evaluated the cryopreservation of somatic embryos of E. edulis using conventional vitrification and droplet vitrification in association with a modified Plant Vitrification Solution 3 (PVS3) supplemented with different concentrations of dimethyl sulfoxide (DMSO; 0, 5, 10, and 15%). No significant differences were observed between vitrification methods regarding post-thaw recovery. However, PVS3 supplemented with 10% and 15% DMSO promoted higher survival than 0% and 5%, with maximum values recorded at 15% DMSO (67.50% in droplet vitrification and 69.50% in conventional vitrification). Scanning electron microscopy revealed greater structural alterations in somatic embryos at more advanced maturation stages after cryopreservation, whereas transmission electron microscopy showed treatment-dependent differences in cellular ultrastructure, including vacuolization, cell wall disruption, and preservation of nuclear organization in surviving cells. Elemental analysis by energy-dispersive X-ray spectroscopy (EDS) revealed differences among cryopreservation treatments, with higher carbon intensity observed in treatments showing greater post-thaw survival and lower carbon intensity associated with reduced survival. This technique demonstrates potential for preserving germplasm of endangered E. edulis adult plants and can strategically support genetic improvement programs.

Soil contamination assessment of a 19th-century abandoned Sb–Au mine in northern Portugal - Giulia Resta; Patrícia Santos; Marcus Monteiro; Rui Melo; Morgana Carvalho; Ana Carvalho; Alexandre Lima; Eric Font; José A. Ribeiro; Manuel Azenha; Thierry Adatte; Deolinda Flores (Environmental Geochemistry and Health, 2026)
Abandoned mines are among the main sources of long-term soil contamination, often leaving behind persistent concentrations of potentially toxic elements (PTE) that pose environmental and health risks. Ribeiro da Serra Sb–Au mine, in Portugal, active from 1858 to 1890, has left a significant environmental legacy. This study mapped the spatial distribution of mine processing residues, elemental characterisation distinguishing between anthropogenic and natural enrichment by determining soil sample concentrations of PTE, Hg mobility, and Total Organic Carbon (TOC) quantification. Multivariate analysis, spatial interpolation and comparison with Enrichment Factor were employed with the aim of understanding the distributions and sources of PTEs in the soils. Mercury is still present at the site, revealing high mobile (18.72 mg kg −1 ) and semi-mobile (3.58 mg kg −1 ) concentrations accumulated in waste piles, a remnant of Au amalgamation processes. High Hg concentrations (20.75 mg kg −1 ) pose significant environmental risks, even after more than a century, such as bioaccumulation potential and soil toxicity. Also, there are high concentrations of Pb (449.03 mg kg −1 ) in the waste piles from the Sb processing. This study highlights the critical importance of interpreting natural enrichment values of elements of Hg (EF = 267) and Pb (EF = 18) to discern pollution pathways resulting from mining and processing activities. Interpretation of natural enrichment values leads to a more accurate evaluation of environmental contamination and its sources. The Enrichment Factor shows that Sb (EF = 133) and Hg (EF = 267) are the elements that present extremely high enrichment (EF > 40).

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Potential of guava pulps treated by ohmic heating as a delivery vehicle for probiotic bacteria: stability, functional properties, and in vitro digestibility - Newton C. Santos; Raphael L.J. Almeida; Virgínia M. de A. Silva; Thalis L.B. de Lima; Ronildo P. de Sousa Júnior; Victor H. de A. Ribeiro; Yaroslávia F. Paiva; Francislaine S. dos Santos; Deyzi S. Gouveia; Rennan P. de Gusmão; Alexandre J. de M. Queiroz; Josivanda P. Gomes; et al. (International Journal of Food Microbiology, 2026)

Analysis of the physical and chemical characteristics of stored and fresh Leucaena leucocephala seeds - Viviane da Silva Sousa Almeida; Amanda Graziela Gonçalves Mendes; Tonicley Alexandre da Silva; Daniele Gomes Cassias Rodrigues; Ariadina Jansen Campos Fontes; José Lima Pereira-Filho; Carmem Duarte Lima Campos; Aleania Polassa Almeida Pereira; João Lucas do Carmo Lima; Kátia Danielle Araújo Lourenço Viana; Valério Monteiro-Neto (Food Research International, 2026)

Bisphenol S-induced cardiac remodeling is associated with an imbalance in the renin-angiotensin system - Guilherme dos Santos Reis; Maria Eduarda Lima da Silva; Luiza Mazzali Ferraz; Cristiane Matsuura; Antonio Claudio Lucas da Nóbrega; Leandro Miranda-Alves; D'Angelo Carlo Magliano; Eliete Dalla Corte Frantz; Beatriz Alexandre-Santos (Environmental Research, 2026)

Dietary biological silage from tambaqui by products affect performance, physiology, and egg quality of young and old laying hens - Cristiane Cunha Guimarães; João Paulo Ferreira Rufino; Alexandre Augusto Barai; Adriene Núzia de Almeida Santos; Maria Fernanda da Silva Gomes; Tiago Cabral Nóbrega; Maiko Willas Soares Ribeiro; Philip Dalbert da Silva Castro; Joana Maia Mendes; Francisco Alberto de Lima Chaves; Joel Lima da Silva Junior; Marco Antonio de Freitas Mendonça; et al. (Tropical Animal Health and Production, 2026)
This study evaluated the effects of increasing inclusion levels of biological silage produced from tambaqui ( Colossoma macropomum ) by-products (BST) in diets of commercial hens at different ages. A completely randomized design in a 2 × 5 factorial arrangement was adopted, comprising two hen ages (23 and 83 weeks) and five BST inclusion levels (0, 1, 2, 3, and 4%), with four replicates of six birds per treatment. Moderate BST inclusion (1–2%) improved egg production, egg mass, and feed efficiency, particularly in younger hens, while maintaining physiological homeostasis. In contrast, higher inclusion levels (≥ 3%) reduced feed intake and performance and negatively affected erythropoietic indicators, with more pronounced effects in older hens, highlighting age-dependent metabolic responses. Egg physical quality, including albumen height, Haugh unit, and eggshell thickness, was optimized at 2% BST, whereas excessive inclusion compromised shell quality and egg weight. Egg composition was modestly affected, mainly in lipid and moisture contents, with interactions between diet and hen age. Sensory evaluation revealed that eggs from hens fed up to 1% BST maintained high acceptability, while higher inclusion levels negatively affected taste. The observed benefits at moderate inclusion levels are likely associated with the presence of highly digestible proteins, bioactive peptides, and fermentation-derived compounds that enhance nutrient utilization and productive efficiency. Conclusively, BST represents a viable and sustainable ingredient for laying hen diets when included at moderate levels (≤ 2%), providing a novel strategy for valorizing aquaculture by-products while optimizing productive performance, physiological responses, and egg quality, considering age-related adaptability.

Molecular epidemiological surveillance of circovirus in avian and mammalian species on the Brazilian coast - Ana Julia Chaves Gomes; Yasmin Luisa Neves Lemes Garcia; Dayla Bott Geraldini; Camila Domit; Fábio Henrique de Lima; João Pessoa Araújo; Juliana Schons Gularte; Micheli Filippi; Vyctoria Malayhka de Abreu Góes Pereira; Meriane Demoliner; Alexandre Sita; Fernando Rosado Spilki; et al. (Archives of Virology, 2026)
Circoviruses (CVs) infect diverse mammals, birds, and freshwater fish and are linked to diseases causing major economic losses. Despite being well studied in psittacines, their circulation in other avian groups and mammals is poorly understood. We conducted molecular surveillance of CVs in migratory birds and mammals along the Paraná coast, southern Brazil. Sterna hirundinacea specimen tested positive by Nested-PCR for GullCV. In the GullCV-infected bird, histopathology revealed nonspecific lesions, including marked splenic lymphoid atrophy, cachexia-related changes, acute tubular necrosis, and generalized congestion. Sanger sequencing revealed 83% nucleotide identity with CV sequences previously reported in gulls from the United States, which was consistent with results obtained by NGS and Rep-based phylogenetic analysis. These findings contribute to the understanding of CV diversity, distribution, and host range.

Dispersal and Regional Diversification Reveal Tropical Mountain Systems as Cradles of Diversification for the Forking Ferns (Gleicheniaceae, Polypodiopsida) - Lucas Vieira Lima; Alexandre Salino; Michael Kessler; Germinal Rouhan; Weston Testo; André Luís de Gasper; Thaís Elias Almeida (Journal of Biogeography, 2026)
Aim To reconstruct the historical biogeography and diversification dynamics of the fern family Gleicheniaceae, testing whether (1) its main centres of diversity are the result of within‐area speciation or lineage immigration, (2) dispersal shows directionality across tropical regions and (3) shifts in geographic distribution are correlated with diversification rates. Location Tropical and subtropical regions worldwide, with a focus on tropical America and Southeast Asia. Taxon Fern family Gleicheniaceae (Polypodiopsida). Methods We used a time‐calibrated phylogeny of Gleicheniaceae combined with ancestral range reconstruction in BioGeoBEARS. Stochastic biogeographic mapping was used to estimate the frequency and directionality of biogeographic events. Diversification dynamics were evaluated using both constant‐rate (Yule and Birth–Death) and rate‐variable (BAMM) approaches, and their relationship with dispersal frequency was examined. Results Dispersal was consistently recovered as the predominant process shaping the distribution of Gleicheniaceae under the best‐fitting BAYAREALIKE+J model. Among dispersal‐related processes, range expansion was the most frequent biogeographic event, particularly between the Andes and Brazil, and between Asia and Oceania. Founder‐event dispersal contributed secondarily, enabling long‐distance colonisation. Within‐area cladogenetic events were also frequent, especially in Sticherus . Diversification rates varied across clades: Sticherus and Dicranopteris showed the highest net diversification, coinciding with Neogene peaks in dispersal and climatic changes, whereas geographically restricted genera ( Rouxopteris , Stromatopteris ) exhibited the lowest diversification rates. Main Conclusions The evolutionary history of Gleicheniaceae was dominated by dispersal, with the Andes and Asia representing important centres of lineage accumulation and redistribution within their respective regions. Dispersal directionality and its correlation with diversification highlight tropical montane systems as key drivers of lineage radiation. Although complementary analyses indicate that historical geographic isolation may also have contributed to deep divergences, the overall biogeographic pattern remained dominated by dispersal in this ancient fern lineage.

miRNA-mRNA integrative profiling in canine tubulopapillary mammary carcinoma - Nayra Cristina Herreira do Valle; Matheus Fujimura Soares; Natália Francisco Scaramele; Amanda de Oliveira Furlan; Maria Fernanda da Silva Lopes; Juliana de Souza Felix; Fernando Vissani Fernandes; Vinicius Aquiles Gomes Zamboni; Igor Luiz Salardani Senhorello; Alexandre Lima de Andrade; Flavia Lombardi Lopes (Research in Veterinary Science, 2026)

Schools as drivers of food education: Stakeholder perceptions on unconventional food plants in Serra Negra da Mantiqueira, Minas Gerais, Brazil - Carlos Alexandre de Lima; Luiz Fernando de Sousa Antunes; Anelise Dias; Mariella Camardelli Uzeda (Food and Humanity, 2026)

Food use, behavioral and cultural significance of the wood-boring mollusc Turu (Teredo sp.) in the Brazilian Amazon - Danilo Vitor Vilhena Batista; Larissa Aparecida Moreira de Castro; Adriana Fernandes de Barros; Caio Francisco Santana Farias; Ana Paula de Souza; Alexandre Vaz da Silva; Carolina Cerqueira Lima Dittrich; Emilly Monteiro Lopes; Elenice Martins Brasil; Marco Shizuo Owatari; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Food and Humanity, 2026)

Sex-specific cardiac responses to subacute exposure to tributyltin in rats - Ana Beatriz Araújo Mendes; Nadia Alice Vieira Motta; Gabriel Ferreira Lima; Lis Jappour Autran; Stephani Correia Brazão; Nikolas Cunha de Assis Pereira; Ana Rebecca da Silveira de Souza; Beatriz Alexandre-Santos; D'Angelo Carlo Magliano; Leandro Miranda-Alves; Fernanda Carla Ferreira Brito (Chemico-Biological Interactions, 2026)

Enhancing water management and natural resource use in tropical grassland systems under semi-arid conditions: Dual Kc approach - Cleber Pereira Alves; Danielle da Silva Eugenio; Luciana Sandra Bastos de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Gabriel Italo Novaes da Silva; João Pedro Alves de Souza Santos; Wilma Roberta dos Santos; Álefe Chagas de Lima Costa; Leonardo Francelino de Souza; Jandis Ferreira Nunes de Araujo; Ênio Farias de Franca e Silva; et al. (Biomass and Bioenergy, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Tree planting in public squares in an Amazonian capital: are morphometric and ecological aspects considered for decision-making? - Hiago Felipe Cardoso Pacheco; Walmer Bruno da Rocha Martins; Julia Isabella de Matos Rodrigues; Joathan Cipriano Castro; Paula Daniele Martins Moraes; José Rozendo de Lima Silva; Marcos Alexandre Vieira Nascimento Filho; Lucas Lopes da Silva (Trees, 2026)
Key message This study highlights native species’ potential for urban landscaping in the Amazon region, prioritizing safety and ecosystem benefits. Abstract Public squares can be important elements for sustainable urban development and adaptation to climate change, for which an adequate tree composition is key. In the Amazon region, despite the high tree biodiversity, it is common to select unfitted species to compose public squares’ landscaping. Therefore, this research aimed to evaluate the suitability of species used for landscaping of public squares in an Amazonian state capital, based on 4 morphometric and 3 ecological features. 50 public squares were selected and inventoried, tree species were evaluated and classified according to morphometric features (crown projection, slenderness, overhang index, and coverage index), as well as ecological features (leaf habit, fruit weight, and species origin). Species were ranked from the most to the least suitable using weighted values based upon the 7 features employed. The results indicated that, within species currently in used in Belém public squares, Andira inermis (W.Wright) DC. (Cabbage bark) and Ceiba pentandra (L.) Gaertn. (Kapok tree), native to the Amazon region, were the most fitted for public squares landscaping among all the species encountered. Native species such as Bertholletia excelsa Bonpl. (Brazil nut) and Swietenia macrophylla King (Brazilian mahogany), although promising, showed limitations due to their high weighted fruits. This study highlights the need for further research on the use of native Amazonian flora in public squares, especially on its regulating and cultural ecosystem services provision in urban contexts. Additionally, it emphasizes that the implementation of some species should be discontinued due to risks to the safety of urban square visitors and possible damage to urban infrastructure.

Living Near the Surface: Dive Behavior of Sei Whales ( Balaenoptera borealis ) in the Southwestern Atlantic Ocean - Clarêncio Gomes Baracho‐Neto; Leonardo Liberali Wedekin; David Haas; Lucas Lima de Oliveira; Marta Jussara Cremer; Alexandre Novaes Zerbini (Marine Mammal Science, 2026)
Understanding the diving behavior of baleen whales in tropical breeding areas is essential for evaluating both ecological functions and anthropogenic threats. In this study, we combined satellite transmitters and generalized additive mixed models (GAMMs) to investigate the dive behavior of sei whales ( Balaenoptera borealis ) in Santos Basin (SB), off southeastern Brazil. A total of 9963 dives were analyzed, revealing a dominance of shallow dives, with 93% of dives occurring at depths ≤ 20 m. Environmental variables such as sea surface temperature, local bathymetry, and chlorophyll concentration significantly influenced dive depth and duration. Cooler waters and deeper offshore areas were associated with longer and deeper dives, while higher surface productivity (indicated by increased chlorophyll a levels) shortened dive times. Behavioral and temporal covariates, including diel period, lunar phase, and dive shape, further modulated diving patterns. The prevalence of shallow diving behavior within the depth range of vessel drafts (≤ 20 m) raises significant conservation concerns, particularly regarding the risk of ship strikes in high‐traffic areas like the Santos Basin. Our findings highlight the behavioral plasticity of sei whales in tropical low‐latitude habitats and emphasize the importance of integrating dive behavior data into marine spatial planning and mitigation strategies. Reducing vessel speed and rerouting traffic in high‐density whale habitats should be considered in the future with further studies to reduce the risk of anthropogenic impacts on this threatened species.

What percentage of neuromuscular strength reduction in older adults determines the decline in walking speed? - Yasmin Oliveira Machado; Mariane Marques Luiz; Roberta de Oliveira Máximo; Sara Souza Lima; Andrew Steptoe; Cesar de Oliveira; Tiago da Silva Alexandre (GeroScience, 2026)
Background/Objective Although different neuromuscular strength (NS) cutoff points have been proposed to identify low walking speed (WS) in older adults, the extent to which NS changes predict long-term WS decline remains unclear. This study aimed to determine the percentage of NS change associated with WS decline in older adults. Methods A longitudinal analysis was conducted using data from 4,541 participants aged ≥ 60 years in the ELSA Study. Changes in NS over four, eight, and twelve years of follow-up, compared to baseline, were categorised into nine groups: maintenance of NS within ± 5%, increases of 5–10%, 10–15%, 15–20%, or more than 20%, and reductions in the same ranges. Generalised linear mixed models were used to evaluate WS trajectories (m/s) as a function of NS changes, adjusted for sociodemographic, behavioural, and clinical factors. Results Participants who experienced a 15–20% (-0.007 m/s per year; 95% CI: -0.013 to -0.002) and more than 20% (-0.004 m/s per year; 95% CI: -0.007 to -0.001) reduction in NS had greater WS decline compared to those with stable NS (± 5%). Over 12 years, these reductions corresponded to WS declines of -0.189 m/s and -0.144 m/s, respectively. Conclusion Losing 15% or more of neuromuscular strength reduces walking speed over time. Therefore, monitoring the percentage change in NS can serve as a useful tool for early detection of the risk of WS decline, allowing for more personalised clinical investigations and timely neuromuscular strengthening interventions to minimise adverse effects on mobility in older adults. Graphical Abstract

Deciphering geochemical variations driven by metasomatism around a lithium pegmatite at the Gonçalo deposit, Portugal: implications for rare-metal exploration in granitic terranes of the European Variscan Belt - Jon Errandonea-Martin; Encarnación Roda-Robles; Idoia Garate-Olave; Sonia García de Madinabeitia; Fernando Sarrionandia; Nora Santos-Loyola; Alexandre Lima (Mineralium Deposita, 2026)
Geochemical halos surrounding Li-rich pegmatites represent a potentially effective vectoring tool for the exploration of concealed deposits. To determine the petrochemical processes triggered by fluids derived from evolved pegmatitic melts in granitic host rocks, this work investigates the geochemical anomalies around a lepidolite-rich pegmatite at Gonçalo (Portugal). The study combines EMPA and LA-ICP-MS analyses of rock-forming minerals from the pegmatite and host monzogranite, along with whole-rock geochemistry. Results indicate that fluid exsolution and infiltration into the monzogranite occurred prior to, or coeval with, the onset of pegmatite crystallization. Boron, W, Mo, and As (± Cs, ± Sn) show preferential incorporation into the fluid phase over remaining in the pegmatitic melt, while F, Be, Li, Ta, Rb, Tl, and Ge likely incorporated into metasomatizing fluids due to their strong enrichment in the melt, rather than a preferential incorporation. Greisenization, zinnwalditization and tourmalinization reactions led to the formation of metasomatic Li-rich micas, quartz, apatite, fluorite, rutile, ilmenite, schorl, and sulfides in the variably metasomatized monzogranite. The Li halo in whole-rock extends 4–5 m from the contact and, together with F, B, As, and Cs enrichments, serves as a reliable pathfinder for buried Li-rich pegmatites, detectable up to twice the dyke thickness. Mica chemistry may offer a more sensitive alternative, with Li, Cs, Sn, and Be representing key components of the geochemical fingerprint associated with Li-rich pegmatites. These results may be applicable to the exploration of rare-element pegmatite deposits in granitic terranes, particularly within the Li-metallogenic province of the European Variscides.

Annatto concentrate supplementation improves systemic redox balance and modulates placental FGF-2 expression in ewes - Leonardo Lima Salata; Calie Castilho; Isabella Guartieri da Silva; Leticia Jalloul Guimarães; Isabella Pereira Azoia; Ines Cristina Giometti; Dionísio Pedro Lopes Kuhn Pinheiro; Alexandre Martins Olivete; Marilice Zundt (Reproductive Biology, 2026)

First or best? Contrasting approaches reveal different outcomes in tadpole (Hypsiboas lundii) escape performance under acute chlorpyrifos exposure - David Sánchez-Domene; Alba Navarro Lozano; Alexandre Vidotto Barboza Lima; Camila Nomura Pereira Boscolo; Amanda Huga Magrini; Eduardo Alves de Almeida (Behavioural Processes, 2026)

So close and unnoted: a new host plant of Cerataphis brasiliensis (Hempel) (Hemiptera: Aphididae) - Nyeppson de Sousa Soares; Alexandre Santos Araújo; Leonardo Souza Duarte; Frederico Hickmann; Thiago Henrique dos Reis Pádua; Mateus Souza Lima Aurélio; Sinval Silveira Neto; Roberto Antonio Zucchi; Marcoandre Savaris (International Journal of Tropical Insect Science, 2026)
Cerataphis brasiliensis (Hempel) (Hemiptera: Aphididae), the palm aphid, is native to Asia and, in several countries, has been associated with some economically important palm trees (Arecaceae). This study aims to document, for the first time, the occurrence of C. brasiliensis on Butia odorata (Barb. Rodr.) Noblick (Arecaceae) in the municipality of Piracicaba, São Paulo State, Brazil. The identity of the specimens was verified through both morphological and molecular analyses, specifically examining the mitochondrial gene cytochrome c oxidase subunit I (COI). The haplotype of the specimen collected on Butia palm tree exhibited over 99% homology with other sequences of C. brasiliensis , thereby confirming the species identity. Observations indicated a clear preference of the aphid for the rachillae and fruits of B. odorata . Additionally, for the first time, a mutualistic interaction between Camponotus crassus Mayr (Hymenoptera: Formicidae) and the palm aphid was documented. Currently, C. brasiliensis is known to associate with species from four botanical families, with a predominant occurrence in Arecaceae throughout South America.

Multiproxy evidence of environmental phases leading to podzolization in semi-arid soils of Northeastern Brazil - Analice Nunes Clarindo; Sara Ramos dos Santos; David Lukas de Arruda; Danilo de Lima Camêlo; Alexandre Tavares da Rocha; Valdomiro Severino de Souza Junior; Heloisa Helena Gomes Coe; Carlos Eduardo de Rezende; Marcelo Metri Corrêa (CATENA, 2026)

Therapeutic Drug Monitoring of Itraconazole in Endemic Paracoccidioidomycosis: Real-World Data - Wdson Luis Lima Kruschewsky; Vera Lucia Teixeira de Freitas; Mariane Taborda; Isabela Antonini Alves Oliveira Quadros; Mônica Scarpelli Martinelli Vidal; Tiago Alexandre Cocio; Gil Benard; Nilo José Coêlho Duarte; Vítor Falcão de Oliveira; Adriana Satie Gonçalves Kono Magri; Marcello Mihailenko Chaves Magri (Mycopathologia, 2026)

Therapeutic Efficacy of Monoterpenes in Nile Tilapia Infected With Edwardsiella tarda : A Phytogenic Alternative to Oxytetracycline - Danilo Vitor Vilhena Batista; Adolfo Jatobá; Alexandre Vaz da Silva; Ana Paula de Souza; Caio Francisco Santana Farias; Emilly Monteiro Lopes; Marco Shizuo Owatari; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Silvia Terra Fontes; Fernando Yugo Yamamoto; Maurício Laterça Martins; et al. (Journal of Fish Diseases, 2026)
The purpose of this research was to assess the effectiveness of a combination of monoterpenes (thymol and carvacrol) in treating juvenile Nile tilapia ( Oreochromis niloticus ) infected with Edwardsiella tarda as a potential substitute for the antibiotic oxytetracycline. The study utilised different concentrations of the monoterpenes blend (MTs): 0.4, 0.6 and 0.8 g kg −1 of feed. A negative control group received a diet without the additive, while a positive control group was given medicated feed containing oxytetracycline (OTC) (11.85 g kg −1 ) for a 10‐day treatment period. Cumulative mortality (%), haematological and immunological parameters were assessed after the feed administration. The negative control group experienced a mortality rate of 53%, while fish treated with medicated feed had a significantly lower mortality rate of 3%. The addition of MTs at concentrations of 0.4 g kg −1 (13% mortality), 0.6 g kg −1 (8% mortality) and 0.8 g kg −1 (0% mortality) also resulted in reduced mortality rates, with the highest concentration showing survival rates comparable to the oxytetracycline group. Following the 10‐day treatment period, no mortality was observed in the treated groups, indicating the efficacy of MTs‐supplemented feed in alleviating the clinical symptoms of Edwardsiellosis. The haematological parameters indicated that as the dosage of MTs increased, the mean corpuscular volume (MCV) decreased. The MCV was significantly lower in the 0.6 and 0.8 g kg −1 treatments compared to the control. Mean corpuscular haemoglobin initially increased with the 0.4 g kg −1 MTs treatment but then decreased with higher doses. The mean corpuscular haemoglobin concentration was higher in the treated groups compared to the control. Red blood cell levels were higher in the 0.8 g kg −1 MTs treatment and lower in the 0.4 g kg −1 treatment. Ht was higher in the control group and lower in the 0.4 g kg −1 MTs treatment. Haemoglobin levels followed a similar trend, with higher values in the control group. The 0.8 g kg −1 MTs treatment had the highest number of total leucocytes and lymphocytes. The control group had the highest number of neutrophils, while the 0.8 g kg −1 MTs group had higher numbers of monocytes, eosinophils, basophils and thrombocytes. The negative control exhibited the lowest antimicrobial titre compared to the OTC and the various concentrations of MTs. The concentrations of MTs (0.4, 0.6 and 0.8 g kg −1 ) demonstrated similar average values and were more effective than the control and OTC. There was no significant difference in agglutinating titre among MTs, control and OTC. Thymol and carvacrol notably decreased the mortality of tilapia infected with E. tarda , with a dosage as high as 0.8 g kg −1 showing equivalent effectiveness to oxytetracycline. Furthermore, they enhanced haematological and immunological parameters, indicating that MTs could be a promising alternative to antibiotic use.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Monitoring tailings remobilization after the VALE S.A. Dam failure in Brumadinho: Impacts of extreme floods assessed through remote sensing - Hugo Henrique Cardoso de Salis; Alexandre de Lima Chumbinho; Irla Paula Stopa Rodrigues; Marilia Andrade Fontes (Remote Sensing Applications: Society and Environment, 2026)

Seasonal patterns and atmospheric modulators of erythemal UV radiation in a sensitive region of the Brazilian Amazon: Implications for environmental health risk assessment - Pericles Vale Alves; Vandoir Bourscheidt; Damaris Kirsch Pinheiro; Rodrigo Martins Moreira; Marcos André Braz Vaz; Mônica Santos; Marcos Antônio Lima Moura; Carlos Alexandre Santos Querino; Paula Regina Humbelino de Melo; Maria Adriana Moreira (Remote Sensing Applications: Society and Environment, 2026)

Multiple ecotoxicological effects of sublethal exposures to atmospheric particulate matter in two neotropical benthic species - Diego Ferreira Gomes; Thandy Junio da Silva Pinto; David Silva Alexandre; Michelly Pereira Soares; Raquel Aparecida Moreira; Hevelyn Plácido Gomes; Maira Rodrigues Lima; Evaldo Luiz Gaeta Espíndola; Odete Rocha; Marisa Narciso Fernandes (Journal of Hazardous Materials, 2026)

Multistage Ag-Hg-Cu mineralization hosted in Ediacaran-Cambrian rocks at the Tassafte mining district, NE edge of the Saghro inlier (eastern Anti-Atlas, Morocco): structural controls and ore textures - Zakarya Yajioui; Lakhlifi Badra; Alexandre Lima; Sabine Gilbricht; Brahim Karaoui; Amar Karaoui; Abdelkader Mahmoudi (Journal of African Earth Sciences, 2026)

Law 22017/2023: a dire threat to the Cerrado's survival and Brazil's environmental leadership - Luciane Martins de Araújo; Manuel Eduardo Ferreira; José Antônio Tietzmann e Silva; Giovanni Martins de A. Mascarenhas; Altair Sales Barbosa; Mariana Pires de Campos Telles; José Alexandre Felizola Diniz-Filho; Ludgero Cardoso Galli Vieira; Geraldo Wilson Fernandes; Stephannie Fernandes; José Aluízio Ferreira Lima; Flávia de Figueiredo Machado (Environmental Development, 2026)

Evaluation of growth and chemical composition of forage consortia of grasses with tree species - Yamid Andres Perilla Melo; Alexandre Fernandes Perazzo; Shirlenne Ferreira Silva; Maysa Callado Moura; João Paulo Matos Pessoa; Walyson Alves de Araújo; Joana Floribella Lima da Silva; Ricardo Loiola Edvan (Agroforestry Systems, 2026)

Preliminary pre-formulation studies of novel mexiletine analogs: Focus on solid-state characterization - Michelle A. Sarcinelli; Thalita M. Silva; Cinira Fandaruff; Viviane S. Vaiss; Larissa L. Lima; Emerson T. da Silva; Marcus V.N. de Souza; Alexandre A. Leitão; Fabio F. Ferreira; Jorge C.S. Costa; Marco A. Martins; Helvécio V.A. Rocha (Next Research, 2025)

Characterization of the physicochemical, nutritional and mineral composition of Curriola (Pouteria ramiflora) and Marmelada bola (Alibertia edulis) pulp, peel and seed at different maturation stages - Maria da Graça Tomás; Carlos Alexandre Rocha da Costa; Hanna Elisia Araújo de Barros; Caio Vinicius Lima Natarelli; Luíz Guilherme Malaquias da Silva; Elisangela Elena Nunes Carvalho; Katiuchia Pereira Takeuchi; Flávia Matias Oliveira da Silva; Eduardo Valério de Barros Vilas Boas; Francisco de Almeida Lobo; Luiz José Rodrigues (Food and Humanity, 2025)

Monitoring soil conservation techniques via UAV for sustainable production of intercropped forage cactus with reuse water in the Brazilian semiarid region - Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel G.P. Isidoro; Thieres George Freire da Silva; Thayná Alice Brito Almeida; João Luis Mendes Pedroso de Lima; Pedro Rogério Giongo; Alexandre Maniçoba da Rosa Ferraz Jardim; Marcos Vinícius da Silva; Ênio Farias de França e Silva; Breno Leonan de Carvalho Lima (Field Crops Research, 2025)

Greenhouse gases emissions and energy efficiency in ewe lambs fed hay from native Pantanal grasses - Jaine de Sousa Santos; Sandra Aparecida Santos; Roberto Cláudio Fernandes Franco Pompeu; Olivardo Facó; Alexandre Lima Ferreira; Delano de Sousa Oliveira; Arnaud Azevedo Alves; Alexandre Ribeiro Araújo; Marcos Cláudio Pinheiro Rogério (Tropical Animal Health and Production, 2025)

Epstein-barr virus (EBV) in cervical carcinoma detected by in situ hybridization targeting ebers and the viral genome - Álife Diêgo Lima Silva; Julia Graziele Alves Marelli; Maria Willaiara Lira Lopes; Myrella Tavares Rodrigues; Cecília Paz Lopes; José Nairton Coelho Silva; Sávio Samuel Feitosa Machado; Racquel Oliveira da Silva Souza; Maria Aparecida Tibúrcio; Alexandre Quental Sampaio; Isabelle Joyce de Lima Silva Fernandes; Claudia do Ó Pessoa; et al. (Brazilian Journal of Microbiology, 2025)

Traditional ecological knowledge of scorpions in human communities in a Brazilian semiarid region - Luiza Eulália de Azevedo Gonzaga; José Rivaldo de Lima; Meykson Alexandre da Silva; Geraldo Jorge Barbosa de Moura; André Felipe de Araujo Lira (International Journal of Tropical Insect Science, 2025)

Experimental assessment of beauvericin toxicity in tadpoles of Dendropsophus minutus (Anura: Hylidae) - Monica Chacon de Vicente; Luiza Gabriella Ferreira de Paula; Renata Maria Pereira de Freitas; Adieli dos Anjos Almeida; Diego da Silva Lima; Rebeca dos Santos Gabriel; Nathany Geraldino Nogueira; Nádya Raquel dos Santos Batista; Alexandre Có Mangoni Barros; Marcelino Benvindo de Souza; Rogério Pereira Bastos; Pedro Vale de Azevedo Brito; et al. (Toxicon, 2025)

Exposure to bisphenol S promotes renal damage via aryl hydrocarbon receptor and NF-κB pathways in a mice model of obesity - Michele Lima Brito; Joana Ramos de Araujo; Patricia Pereira Almeida; Beatriz Alexandre-Santos; Beatriz Gouvêa de Luca; Kauet de Matos Gama e Souza; Denise Pires de Carvalho; Denise Mafra; Eliete Dalla Corte Frantz; Clarice Machado-Santos; Leandro Miranda-Alves; D'Angelo Carlo Magliano; et al. (Environmental Research, 2025)

Substituting grass hay and ground corn with forage cactus genotypes on mineral status of lambs - Luiz Carlos Leal Torres; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Roberto Germano Costa; Daurivane Rodrigues Sousa; Ângela Maria Vieira Batista; Diana Valadares Pessoa; Ihasmyn dos Santos Nunes; Ana Paula Silveira Paim; Dorgival Morais de Lima Júnior; Pierre Castro Soares; Francisco Fernando Ramos de Carvalho (Tropical Animal Health and Production, 2025)

Carbon-related processes as indicators of soil health in a degraded dryland area under long-term restoration: Responses of a 21-year grazing exclusion system - Antonio Y.V. Lima; Maurício R. Cherubin; Danilo F. Silva; Ademir S.F. Araujo; Diogo P. Costa; Jaedson C.A. Mota; Ícaro V. Nascimento; Alexandre S. Queiroz; Erika V. Medeiros; Kaio G.V. Garcia; Gabriel N. Nóbrega; Geocleber G. Sousa; et al. (Applied Soil Ecology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Effects of floating macrophytes on open-water evaporation in a Brazilian tropical reservoir - Italo Sampaio Rodrigues; Carlos Alexandre Gomes Costa; Adunias dos Santos Teixeira; Iran Eduardo Lima Neto; Fernando Bezerra Lopes; José Carlos de Araújo (Journal of South American Earth Sciences, 2025)

Kinetics-thermodynamics of the antioxidant activity of propolis extracts in pork pâté - José Dilson Francisco da Silva; Fernanda Cristina Breda; Lucila Cendon Ribeiro; Jessica Aparecida de Lima; Andresa Berretta; Osmar Damian Prestes; Renato Zanella; Alexandre José Cichoski; Renius de Oliveira Mello (Food Research International, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Lectins of algal origin: 25 years of progress in structural insights and biotechnological applications - Manoel Ferreira da Costa Filho; Ellen Maria Lima Gonçalves; Renata Pinheiro Chaves; Rômulo Farias Carneiro; Alexandre Holanda Sampaio; Celso Shiniti Nagano (Journal of Applied Phycology, 2025)

Genomic selection in Passiflora breeding for CABMV resistance and agronomic performance - Débora Souza Mendes; Alexandre Pio Viana; Flavia Alves da Silva; Natan Ramos Cavalcante; Joameson Antunes Lima; Janeo Eustáquio de Almeida Filho; Orzenil Bonfim da Silva Júnior; Dario Grattapaglia (Euphytica, 2025)

Synthesis and characterization of Ba and Sr celsian ceramics from zeolites obtained from amazonian bauxite waste clay - Nayara Aparecida Fonseca Couto; Bruno Apolo Miranda Figueira; Igor Alexandre Rocha Barreto; Patricia Teresa Souza da Luz; Oscar Jesus Choque Fernandez; Marcondes Lima da Costa (Applied Clay Science, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Single-dose recombinant FSH as a viable alternative to multi-dose porcine FSH in commercial superovulation protocols in cows - Monique Mazzarollo Frata; Wagner Marques de Lima; Monique Tomazele Rovani; Rogério Ferreira; Alexandre Hênryli de Souza; Rafael Gianella Mondadori; Paulo Bayard Dias Gonçalves; Vilceu Bordignon; Bernardo Garziera Gasperin (Theriogenology, 2025)

Redox structure of a saline lake during the Barremian-Aptian, Sanfranciscana Basin, southeast Brazil - Willian Alexandre Lima de Moura; Gabriel Jubé Uhlein; Fabricio de Andrade Caxito; Jonathas S. Bittencourt; René Rodrigues; Alcides N. Sial; Egberto Pereira (Journal of South American Earth Sciences, 2025)

Polymetallic interactions of Zn-Pb-Cu in blue/green-colored speleothems from Malaval Cave (France) - Martin Vlieghe; Gaëtan Rochez; Stéphane Pire-Stevenne; Alexandre Felten; Marie Dechamps; Sébastien R. Mouchet; Francesca Cecchet; Olivier Bruguier; Jean-Louis Galéra; Gipsi Lima-Mendez; Marc Llirós Dupré; Johan Yans (Geochemistry, 2025)

Impacts of Exogenous Carnitine on the Ripening and Quality of Tomato and Strawberry Fruit - Juliane Maciel Henschel; Rodrigo Della Libera; Alexandre Lima Oliveira; Rodrigo Ribeiro da Silva; Vanessa de Azevedo Soares; Anna Izaura Balbino dos Santos; Damiana Justino Araujo; Adriano Salviano Lopes; Oziel Nunes da Cruz; Diego Silva Batista (Journal of Plant Growth Regulation, 2025)

Correction: Tetramethylpyrazine alleviates hepatic fibrosis induced by experimental mansonic schistosomiasis - Ana Carolina Campos dos Santos; Daniel Figueiredo-Vanzan; Josiane Bentes; Juliana Maria Motta; Hilton Antônio Mata-Santos; Alexandre dos Santos Pyrrho; Morgana Teixeira Lima Castelo-Branco (Inflammopharmacology, 2025)

Correction: Renin–Angiotensin System Role in Cardiovascular Effects of Plasticizers: A Systematic Review - Guilherme dos Santos Reis; Luiza Mazzali Ferraz; Maria Eduarda Lima da Silva; Luiza da França Losito; Gabriel Ximenes de Oliveira; Antonio Claudio Lucas da Nóbrega; D.’Angelo Carlo Magliano; Eliete Dalla Corte Frantz; Beatriz Alexandre-Santos (Cardiovascular Toxicology, 2025)

Is it safe to use bone tissue for transplants stored for more than five years in a human tissue bank? - Carlos Alexandre Curylofo Corsi; Katia Carmen Gabriel Scarpelini; Rodolfo Leandro Bento; Joel Bel Del Pádua; Luis Fernando Zitei-Baptista; Alan Vinicius Assunção-Luiz; Álefe Saloum Cintra; Denissani Aparecida Ferrari Santos dos Lima; Flávio Luís Garcia; Celso Herminio Ferraz Picado; Luís Gustavo Gazoni Martins (Cell and Tissue Banking, 2025)

A synopsis of Senna ser. Bacillares (Leguminosae, Caesalpinioideae, Cassieae) in Brazil, including a remarkable new species from Amazonia - Alexandre Gibau De Lima; Vidal De Freitas Mansano; Marcelo Trovó Lopes De Oliveira; Gwilym Peter Lewis; Christine D. Bacon; Vinicius Castro Souza (Brittonia, 2025)
Senna (Leguminosae, Cassieae) comprises ca. 300 species mainly distributed throughout the Americas. Although the genus is speciose and taxonomically problematic, very few studies have addressed the systematics of Senna in recent years, and many taxonomic and nomenclatural issues remain unresolved. Senna sect. Chamaefistula ser. Bacillares is the most speciose of the American series of Senna and is the most problematic series in the genus. Based on fieldwork and extensive analysis of herbarium collections, we document the occurrence of 29 species of Senna ser. Bacillares in Brazil. This total includes Senna rionegrensis , which is newly described from Amazonia and distinguished by its short abaxial stamens. We provide a synopical treatment of the taxa of Senna ser. Bacillares occurring in Brazil, including identification keys, short morphological descriptions, taxonomic notes, and distributional and phenological data. This work contributes to the taxonomic knowledge of Senna ser. Bacillares in Brazil and serves as a baseline for our ongoing taxonomic revision.

Deposition, seasonality and the effect of climate on litterfall and its components in Caatinga, a tropical dry forest: A five-year study - Wilma Roberta dos Santos; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Luciana Sandra Bastos de Souza; Gabriel Ítalo Novaes da Silva; José Edson Florentino de Morais; George do Nascimento Araújo Júnior; Cleber Pereira Alves; Alanderson Firmino de Lucas; Lara Rosa de Lima e Silva; Pedro Paulo Santos de Souza; Leonor Patrícia Cerdeira Morellato; et al. (Agricultural and Forest Meteorology, 2025)

Indigenous land is the keystone to protecting Brazilian bat (Mammalia: Chiroptera) biodiversity and their ecosystem services - Bruna Nascimento de Oliveira; Rafaela Jemely Rodrigues Alexandre; Simone Almeida Pena; Letícia Lima Correia; Allysson Moura Luz; Thiago Bernardi Vieira (Biological Conservation, 2025)

Dietary supplementation with açai (Euterpe oleracea) improved the haemato-immunological parameters and growth performance of koi carp (Cyprinus Carpio Linnaeus, 1758) - Alexandre Vaz da Silva; Emilly Monteiro Lopes; Domickson Silva Costa; Gracienhe Gomes dos Santos; Caio Francisco Santana Farias; Paola Capistrano dos Santos; Ana Paula de Souza; Gabriele Bueno dos Anjos; Manoela Clemente Fernandes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Marco Shizuo Owatari; et al. (Veterinary Research Communications, 2025)

Comparison of the nephroprotective effect of [6]-gingerol and the [6]-gingerol-β-cyclodextrin complex against cisplatin-induced AKI - Dayara de Oliveira Silva; Mikael Almeida Lima; Thiago Miranda de Freitas; Francisco Cleber Silva Ferreira; Antônio Klingem Leite de Freitas; Mário Rogério Lima Mota; James Almada da Silva; Marco Antonio de Freitas Clementino; Alexandre Havt (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Streamflow prediction based on data-scarce river-aquifer dynamics estimated by a simplified modelling framework in a dryland catchment - Arthur Jordan Azevedo Toné; Alexandre Cunha Costa; Mário Ubirajara G. Barros; Iran Eduardo Lima Neto (Modeling Earth Systems and Environment, 2025)

Renin–Angiotensin System Role in Cardiovascular Effects of Plasticizers: A Systematic Review - Guilherme dos Santos Reis; Luiza Mazzali Ferraz; Maria Eduarda Lima da Silva; Luiza da França Losito; Gabriel Ximenes de Oliveira; Antonio Claudio Lucas da Nóbrega; D.’Angelo Carlo Magliano; Eliete Dalla Corte Frantz; Beatriz Alexandre-Santos (Cardiovascular Toxicology, 2025)

Dispersal, Isolation and Local Adaptation Promote Speciation in South American Savannas as Indicated by a Phylogenomic Analysis of a Passerine - Alejandro Manuel Ferreiro; Renato Caparroz; Alexandre Aleixo; Luís Fábio Silveira; Samira Rezende Duarte; Cássia Alves Lima‐Rezende; Martín Carboni; Gustavo Sebastián Cabanne (Molecular Ecology, 2025)
South American savannas are a disjunct biome with an unclear evolutionary history. We tested hypotheses about their Quaternary history and the evolution of savanna cores through fragmentation or dispersal from the Cerrado. We used genomic data (genotyping‐by‐sequencing) and ecological niche models of the Burnished‐buff Tanager ( Stilpnia cayana Linnaeus 1766) to evaluate intraspecific differentiation, gene flow, past range shifts and landscape genomics association. We found clear genomic differences between populations on each side of the Amazon basin and high admixture in Marajó Island and Bolivia. Landscape genomics analysis indicated that the Amazon River, isolation by distance and temperature predict genomic differentiation in this bird. Taken together, the results suggest that a combination of dispersal from the Cerrado, isolation due to geographic distance, and the Amazon River basin, and local adaptation shaped species diversification.

Stridulation sounds of the pacamã Lophiosilurus alexandri S teindachner, 1876 ( P seudopimelodidae), a threatened endemic B razilian catfish - Xavier Raick; Gregório Kurchevski; Alexandre Lima Godinho (Journal of Fish Biology, 2025)
Pseudopimelodidae comprises 49 species of freshwater catfish endemic to South America, with limited research on their acoustic behaviour. This study focuses on the pacamã Lophiosilurus alexandri Steindachner, 1876, a vulnerable catfish species endemic to the São Francisco River basin, known for its ecological and economic importance. Sound production by this species was analysed for the first time. Three individuals were recorded while being held underwater revealing the production of two distinct sound types ( type I and type II ) associated with pectoral fin movements (abduction and adduction). Sounds were 85–135 ms long with a variable number of pulses or peaks. Type II sounds were longer and louder than type I sounds , with both types showing a similar peak frequency ranging between 200 and 500 Hz. The sounds were produced alternately by the pectoral fins, with occasional lateralization. More research is needed to determine whether these sounds can be used for monitoring or if they lack sufficient species‐specific characteristics.

Mulching in irrigated forage cactus promotes early harvest and improves the economic indices of the crop - Thieres George Freire da Silva; Renan Matheus Cordeiro Leite; Cleber Pereira Alves; George do Nascimento Araújo Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; José Edson Florentino de Morais; Maria Madalena Lima de Barros; Jandis Ferreira Nunes de Araújo; Vinícius Santos do Nascimento; Alexsandro Claudio dos Santos Almeida; Hugo Rafael Bentzen Santos; et al. (Irrigation and Drainage, 2025)
To mitigate the negative effects of climate, the use of resilient agriculture is essential. This study evaluated the impact of different levels of biotic mulch on irrigated forage cactus yield, phenology and economic indices. The ‘Orelha de Elefante Mexicana’ clone was used and subjected to four levels of biotic mulch—BM (0, 5, 10 and 15 Mg ha −1 ) in a randomised block design with four repetitions. The treatments consisted of growing forage cactus with 0, 5, 10 and 15 Mg ha −1 mulch. The experiment was carried out in a semi‐arid environment in Brazil (Serra Talhada, Pernambuco State) over two successive cycles (August 2020 to August 2022). The yield, cutting time, and morphophysiological, economic and water use indicators were evaluated. There was no effect of the BM level on the final forage yield. In the first experimental cycle, the treatment with 10 Mg ha −1 BM brought the cutting time forward by 103°C day. The application of 15 Mg ha −1 BM prolonged phenophase 2, causing an increase of 236°C day in the cycle compared with the treatment with 10 Mg ha −1 BM. We concluded that mulch improved crop water and economic indicators, contributing to sustainable forage production in semiarid environments.

Adsorption of cadmium by brewery waste - Izabela Gouveia Nascimento; Erica Souto Abreu de Lima; Clenya Carla Leandro de Oliveira; Nelson Moura Brasil do Amaral Sobrinho; Farley Alexandre da Fonseca Breda; David Vilas Boas de Campos; Érika Flávia Machado Pinheiro (Bioresource Technology Reports, 2025)

Tissue distribution of Ocimum basilicum essential oil in Nile tilapia Oreochromis niloticus after anesthesia - Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Caio Francisco Santana Farias; Domickson Silva Costa; Ana Paula de Souza; Danilo Vitor Vilhena Batista; Silvia Terra Fontes; Gabriela Tomas Jerônimo; José Luiz Pedreira Mouriño; Maurício Laterça Martins (Veterinary Research Communications, 2025)

Use of Vermicompost Modulates Physiological and Growth Responses of Paricá Seedlings more than Mineral Fertilization - Maria Leidiane Reis Barreto; Maria Bruna de Lima Oliveira; Milena de Cassia Silba Borges; Milton Garcia Costa; Renato de Mello Prado; Alexandre de Vicente Ferraz; Adam da Cruz Rodrigues; Felipe Tavares Lima; Jesus de Nazaré Santos Oliveira; Marta Oliveira da Silva; Eric Victor de Oliveira Ferreira; Cassio Rafael Costa dos Santos (Journal of Soil Science and Plant Nutrition, 2025)

Maternal malnutrition induces inflammatory pathways and oxidative stress in the dorsolateral prostate of male offspring rats - Renato Mattos; Matheus Naia Fioretto; Sérgio Alexandre Alcantara dos Santos; Isabelle Tenori Ribeiro; Maycon Tavares Emílio-Silva; Luiz Marcos Frediani Portela; Clélia Akiko Hiruma Lima; Fabio Rodrigues Ferreira Seiva; Luis A. Justulin (Biogerontology, 2025)

Correction: First Transcriptome Analysis of Hepatoblastoma in Brazil: Unraveling the Pivotal Role of Noncoding RNAs and Metabolic Pathways - Talita Ferreira Marques Aguiar; Maria Prates Rivas; Edson Mario de Andrade Silva; Sara Ferreira Pires; Gustavo Dib Dangoni; Taiany Curdulino Macedo; Alexandre Defelicibus; Bruna Durães de Figueiredo Barros; Estela Novak; Lilian Maria Cristofani; Vicente Odone; Monica Cypriano; et al. (Biochemical Genetics, 2025)

First Transcriptome Analysis of Hepatoblastoma in Brazil: Unraveling the Pivotal Role of Noncoding RNAs and Metabolic Pathways - Talita Ferreira Marques Aguiar; Maria Prates Rivas; Edson Mario de Andrade Silva; Sara Ferreira Pires; Gustavo Dib Dangoni; Taiany Curdulino Macedo; Alexandre Defelicibus; Bruna Durães de Figueiredo Barros; Estela Novak; Lilian Maria Cristofani; Vicente Odone; Monica Cypriano; et al. (Biochemical Genetics, 2025)

Elastic thickness and residual gravity anomaly applied to the northern Brazilian basins: Unravelling the volcanic-sedimentary history linked to the Central Atlantic Ocean opening - Gabriel Leal Rezende; Afonso Cesar Rodrigues Nogueira; Nelson de Lima Ribeiro-Filho; Alexandre Ribeiro Cardoso; Renato Sol Paiva de Medeiros; Cristiano Mendel Martins; Davis Carvalho de Oliveira (Gondwana Research, 2025)

Substitution of silage by soybean hulls in tropical forage-based dairy cow production system during the dry season - Jéssica Coutinho Mezzomo da Silva; Carlos Eduardo Avelino Cabral; Isis Scatolin de Oliveira; Alexandre Lima de Souza; Camila Fernandes Domingues Duarte; Rodrigo Schaurich Mativi Righi; Eduarda Caroline Kichel Cuff; Lucas Gimenes Mota; Carla Heloisa Avelino Cabral (Tropical Animal Health and Production, 2025)

The Role of Ion-Transporting Proteins on Crosstalk Between the Skeletal Muscle and Central Nervous Systems Elicited by Physical Exercise - Judit Borràs Bertomeu; Letícia Paiva Fioravanço; Thiago Rozales Ramis; Douglas Buchmann Godinho; Alexandre Seixas Nascimento; Gabriel Corrêa Lima; Ana Flavia Furian; Mauro Schneider Oliveira; Michele Rechia Fighera; Luiz Fernando Freire Royes (Molecular Neurobiology, 2025)

Tetramethylpyrazine alleviates hepatic fibrosis induced by experimental mansonic schistosomiasis - Ana Carolina Campos dos Santos; Daniel Figueiredo-Vanzan; Josiane Bentes; Juliana Maria Motta; Hilton Antônio Mata-Santos; Alexandre dos Santos Pyrrho; Morgana Teixeira Lima Castelo-Branco (Inflammopharmacology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Antifungal resistance in yeasts from One Health perspective: A Brazilian study - Rafael Wesley Bastos; Nalu Teixeira de Aguiar Peres; Kássia Jéssica Galdino da Silva; Ludmila Gouveia Eufrasio; Daniel Santana de Carvalho; Gabriela Silva Cruz; Fabíola Lucini; Lorena Souza Silva; Sthefany Emanuelle Silva; Hareton Teixeira Vechi; Manoella do Monte Alves; Luciana Rodrigues Ferreira Ribeiro; et al. (Science of The Total Environment, 2025)

Treatment with cyclosporine attenuates the inflammatory process and severity of bisphosphonate-induced osteonecrosis of the jaws in rats - Camila Costa Dias; Caio Ferreira Freire Caetano; Gabriella Alves Julião Costa; Antônio Alexandre Coelho; José Vitor Mota Lemos; Dayrine Silveira de Paula; Juliana Paiva Marques Lima; Paulo Goberlânio de Barros Silva (Inflammopharmacology, 2025)

Potentiating-antibiotic and antibacterial properties of Luetzelburgia auriculata (ALLEMÃO) Ducke against MDR bacterial strains - Thiago S. Freitas; Janaina E. Rocha; Marcos J. F. Lima; Carla F. A. Nonato; Cicera J. Camilo; Cicera L. R. Paulo; Maria A. S. Alencar; Isaac M. Araújo; Karla S. T. G. Belém; Selvina P. Silva; Francisco N. Pereira Junior; Hélcio S. Santos; et al. (Vegetos, 2025)

Using native soil to cultivate seedlings of the threatened Melanoxylon brauna Schott (Fabaceae): A path for ex-situ conservation - Nayara Mesquita Mota; Bárbara Emanuelly Santos Souza Sales; Juliano Cezar Zonzini Borin; Eduardo Euclydes de Lima e Borges; Evandro Alexandre Fortini (Journal for Nature Conservation, 2025)

Microencapsulating Lacticaseibacillus rhamnosus GG by spray drying using pea protein, pectin, and tapioca flour: Probiotic viability, digestibility and thermal stability - Newton Carlos Santos; Raphael Lucas Jacinto Almeida; Shênia Santos Monteiro; Thalis Leandro Bezerra de Lima; Alexandre da Silva Lúcio; Lídia Paloma da Silva Nogueira; Yaroslávia Ferreira Paiva; Mailson Gonçalves Gregório; Ana Carla de Oliveira Brito; Luanna Amado da Silva; Douglas Vinicius Pinheiro de Figueiredo; Rosenildo dos Santos Silva; et al. (Food and Bioproducts Processing, 2025)

Blanching, cooking, and ethanol are effective strategies for preserving biofunctional compounds in purple-fleshed sweet potato powder - Gabriel Monteiro da Silva; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Eugênia Telis de Vilela Silva; Henrique Valentim Moura; Aline Priscila de França Silva; Newton Carlos Santos; Flávia Carolina Alonso Buriti; Ana Júlia de Brito Araújo Carvalho; Marcos dos Santos Lima (Food and Bioproducts Processing, 2025)

Molecular detection of respiratory viruses: an observational study on respiratory co-infections in children and adults - Tereza de Jesus Pinheiro Gomes Bandeira; Ana Leticia Sousa de Oliveira; Luis Fernando Pontes Martins; Rodrigo Moreira Matos; Sheryda Raynna Nobre Guedes dos Santos; Mateus Cedro Lopes; Raimundo Tadeu Pires Sobreira; Hermano Alexandre Lima Rocha (Brazilian Journal of Microbiology, 2025)

Soybean2035: A decadal vision for soybean functional genomics and breeding - Zhixi Tian; Alexandre Lima Nepomuceno; Qingxin Song; Robert M. Stupar; Bin Liu; Fanjiang Kong; Jianxin Ma; Suk-Ha Lee; Scott A. Jackson (Molecular Plant, 2025)

Engineering effects of hydrocolloids on drying kinetics, powder characteristics, and antioxidant preservation in grape powder - Amanda Nascimento; Alexandre Lúcio; Ana Nery; Rogério Andrade; Ana Maria Sarinho; Janaina Lima; Leonardo Batista; Hugo M. Lisboa (Journal of Food Engineering, 2025)

Adult cell reprogramming in Euterpe edulis Martius: breakthrough in cloning of an endangered species - Débora Pellanda Fagundes; Joana Silva Costa; Lana Laene Lima Dias; Caroline Palacio de Araujo; Ingridh Medeiros Simões; Eduardo Santos Cade; Tadeu Ériton Caliman Zanardo; Marcello Zatta Péres; Tamyris de Mello; Edilson Romais Schmildt; Amir Ali Khoddamzadeh; Claudete Santa-Catarina; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Mixed models in the selection of interspecific crosses of Psidium spp. resistant to myrtle rust - Letícia da Silva Araújo; Alexandre Pio Viana; Silvaldo Felipe da Silveira; Beatriz Murizini Carvalho; Débora Souza Mendes; Joameson Antunes Lima (European Journal of Plant Pathology, 2025)

Biodiversity Patterns Redefined in Environmental Space - Catherine H. Graham; Matheus Lima Araujo; Elisa Barreto; Christian S. Dambros; José Alexandre Felizola Diniz‐Filho; Niklaus E. Zimmermann; Thiago F. Rangel; Marco Túlio Pacheco Coelho (Ecology Letters, 2025)
Ecological and evolutionary questions addressing diversity‐environment relationships have been evaluated almost entirely in geographic space, yet most hypotheses are formulated in terms of environmental conditions. Recent examples evaluating macroecological patterns directly in environmental space suggest that such refocusing provides different perspectives on the mechanisms driving broad‐scale patterns of diversity. Yet, we lack both conceptual frameworks and targeted studies to fully evaluate the potential contribution of such a refocus. Here, we focus on the concept of environmental space by briefly reviewing its use in ecology and evolution and suggesting avenues for further development. We encourage a re‐evaluation of hypotheses and frameworks that have dominated ecological theory since the foundations of ecology with a very simple shift in the lens, that is, from geographical to environmental space. Focusing on environmental space also provides a crucial lens for climate change research, enabling a comprehensive evaluation of biodiversity dynamics and offering a holistic view of the interplay between species and their evolving environments. This shift enhances our ability to predict and adapt to future changes, enriching our understanding of biodiversity beyond more commonly done geographic analyses.

Alpha and beta diversity patterns of the reef fishes’ early life stages and conservation implications in the Abrolhos Bank, Brazil - André L.R. Lima; Carlos W. Hackradt; Ramón Hernandez-Andreu; Germano H.C. Barrilli; Alexandre Schiavetti; Fabiana C. Félix-Hackradt (Regional Studies in Marine Science, 2025)

Comprehensive analysis of antioxidant, phenolic thermal stability, mineral profile and hygroscopic properties in germinated faba bean flours - Lumara Tatiely Santos Amadeu; Alexandre José de Melo Queiroz; Rossana Maria Feitosa de Figueirêdo; Eugênia Telis de Vilela Silva; Yaroslávia Ferrreira Paiva; Carolaine Gomes dos Reis; João Paulo de Lima Ferreira; Francislaine Suelia dos Santos; Ana Júlia de Brito Araújo Carvalho; Marcos dos Santos Lima; Antônio Daniel Buriti de Macedo; Ana Regina Nascimento Campos (Food Bioscience, 2025)

Biological silage from tambaqui (Colossoma macropomum) by-products on the productive performance, hematological parameters and egg quality of older commercial hens - Cristiane Cunha Guimarães; Tiago Cabral Nóbrega; Adriene Núzia de Almeida Santos; Alexandre Augusto Barai; Lígia dos Santos Mourão; Maria Fernanda da Silva Gomes; Wilson de Souza Ferreira; Francisco Alberto de Lima Chaves; Joel Lima da Silva Junior; Marco Antonio de Freitas Mendonça; Antônio José Inhamuns da Silva; João Paulo Ferreira Rufino; et al. (Tropical Animal Health and Production, 2025)

Temperature-induced changes in the hematological and biochemical parameters of Nile tilapia anesthetized with Ocimum basilicum - Paola Capistrano dos Santos; Emilly Monteiro Lopes; Arlene Sobrinho Ventura; Claudia Andrea Lima Cardoso; Alexandre Vaz da Silva; Domickson Silva Costa; Marília Tedesco; Gabriela Tomas Jerônimo; Maurício Laterça Martins (Aquaculture International, 2025)

Temporal trends in global reptile species descriptions over three decades - Jhonny J. M. Guedes; Hidalgo Valentim Gomes De Lima; Lucas R. Mendonça; Rosana Chen-Zhao; José Alexandre F. Diniz-Filho; Mario R. Moura (Systematics and Biodiversity, 2024)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Morphometric and taxonomic studies of Senna ser. Coriaceae (Leguminosae, Caesalpinioideae, Cassieae), including a new species from Chapada Diamantina, Bahia, Brazil - Alexandre Gibau de Lima; Vidal de Freitas Mansano; Marcelo Trovó; Christine D. Bacon (Brazilian Journal of Botany, 2024)
Senna sect. Chamaefistula ser. Coriaceae is restricted to Brazil and is predominantly distributed in savanna habitat. The species are morphologically characterized by their shrub or treelet habit, usually reniform stipules, extrafloral nectaries usually positioned on the middle or distal part of the petiole, zygomorphic corolla and laterally compressed fruits with the seeds parallel to the fruit valves. Previous taxonomic studies have recognized only three species and one variety, nevertheless, they provided the groundwork for a more comprehensive treatment, presented here. Based on fieldwork and on the analysis of herbarium specimens, we recognize five species belonging to Senna ser. Coriaceae including one new species from the seasonally dry areas in the Chapada Diamantina, Senna diamantinensis . We carried out a morphometric analyses and here recognize S. caesia as a distinct species rather than a variety of S. corifolia . We propose a new combination for Cassia kuhlmannii and recognize it under the genus Senna . In addition, we propose two first-step lectotypifications and one second-step lectotypification. The taxonomic treatment provided here includes an identification key, morphological descriptions, taxonomic notes, illustrations, preliminary conservation assessments, and habitat and phenology data for each species.

Arsenic, cadmium, and chromium concentrations in contrasting phosphate fertilizers and their bioaccumulation by crops: Towards a green label? - Mariana Rocha de Carvalho; Thiago Adorno de Almeida; Gustavo Avelar Zorgdrager Van Opbergen; Fábio Henrique Alves Bispo; Lívia Botelho; Alexandre Boari de Lima; Paulo Eduardo Ribeiro Marchiori; Luiz Roberto Guimarães Guilherme (Environmental Research, 2024)

Geostatistical modeling of the rainfall patterns and monthly multiscale characterization of drought in the South Coast of the Northeast Brazilian via Standardized Precipitation Index - Marcos Vinícius da Silva; Jhon Lennon Bezerra da Silva; Maria Beatriz Ferreira; Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel Guieiro Pereira Isidoro; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Helena Maria Neto Paixão Vazquez Fernandez; Fernando Miguel Granja-Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; et al. (Atmospheric Research, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Lithium exploration targeting through robust variable selection and deep anomaly detection: An integrated application of sparse principal component analysis and stacked autoencoders - Saeid Esmaeiloghli; Alexandre Lima; Behnam Sadeghi (Geochemistry, 2024)

Pseudoplagiostoma humilis sp. nov., a New Fungal Species Causing Shoot Blight and Dieback in Anacardium humile in Brazil - Luiz Pedro Pereira Magalhães; Nilza de Lima Pereira Sales; Patrícia Doerl Barroso; Rildo Alexandre Fernandes da Silva; Danilo Batista Pinho; José Cola Zanuncio; André Costa da Silva (Current Microbiology, 2024)

Which protected areas should be prioritized for prevention and early detection of biological invasions? A new methodological approach - Rafaela Guimarães Silva; Victor Vinícius F. de Lima; Pedro H. C. Pereira; Tainah Correa Seabra Guimarães; Alexandre Bonesso Sampaio; Rafael D. Zenni (Biological Invasions, 2024)

Improving preservation of bioactive compounds in mangosteen peel flour through pre-treatment with bleaching, ethanol, and vacuum pulse - Eugênia Telis de Vilela Silva; Alexandre José Melo de Queiroz; Rossana Maria Feitosa de Figueirêdo; Henrique Valentim Moura; Aline Priscila de França Silva; Gabriel Monteiro da Silva; Inácia dos Santos Moreira; Marcos dos Santos Lima; Ana Julia de Brito Araújo; Francislaine Suelia dos Santos (Food Bioscience, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

NaAlO2/CuFe2O4 as a novel basic magnetic heterogeneous catalyst for effective biodiesel production: Synthesis, characterization, and optimization via RSM-FCCD modeling approach - Hiarla Cristina Lima dos Santos; Matheus Arrais Gonçalves; Vicente da Silva Lima; Alexandre da Cas Viegas; Geraldo Narciso da Rocha Filho; Leyvison Rafael Vieira da Conceição (Process Safety and Environmental Protection, 2024)

Corrigendum: The Brazilian Santos basin underwater soundscape monitoring project (PMPAS-BS) - José Antonio Moreira Lima; William Soares Filho; Fabio C. Xavier; Thiago Pires de Paula; Angela Spengler; Fernando Gonçalves de Almeida; Diogo Peregrino Correa Pereira; Valéria Souza Rego; Cátia Galotta; Carlos Corrêa Junior; Alexandre Bazyl (Frontiers in Marine Science, 2024)

A new cyclodipeptide from Tetragonisca angustula honey active against Neospora caninum and in silico study - Ângela Cristina de Oliveira Lima; Matheus Nolasco; Luciana dos Santos Freitas; Alexandre Moraes Pinheiro; Carlos Alfredo Lopes de Carvalho; Humberto Fonseca de Freitas; Samuel Silva da Rocha Pita; Ivo José Curcino Vieira; Raimundo Braz Filho; Alexsandro Branco (Natural Product Research, 2024)

Reproductive, productive and financial consequences of chronic Trypanosoma vivax infection in a dairy cattle herd in a region without a cyclic vector - Luiz Fellipe Monteiro Couto; Thiago Souza Azeredo Bastos; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Ricardo Backstron Falavigna; José Felipe Warmling Spricigo; Rinaldo Aparecido Mota; Breno Cayero Cruz; Marcos Henrique Alcantara Colli; Alexandre Braga Scarpa; Vando Edesio Soares; et al. (Veterinary Parasitology, 2024)

Quantification and spatial distribution of the bioenergetic potential from slaughterhouses effluents biogas generation across Brazil - Jessica Aline Menezes Lima; Edinéia Lazarotto Formagini; Mateus Tavares da Costa; Jamil Alexandre Ayach Anache (Journal of Cleaner Production, 2024)

Relationships between morphological facies and the evolutionary processes of petroplinthites in the Southern Espinhaço Range (SE-Brazil) - Daniela Schievano de Campos; Danilo de Lima Camêlo; Alexandre Christófaro Silva; Marcilene dos Santos; Pablo Vidal-Torrado (CATENA, 2024)

Evaluation of different supportive treatments during packed cell volume replacement in calves naturally infected with tick fever agents - Alexandre Braga Scarpa; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Igor Maciel Lopes de Morais; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina María Beltrán Zapa; Lídia Mendes de Aquino; Daniel de Castro Rodrigues; Nicolas Jalowitzki de Lima; Vando Edésio Soares; Lorena Lopes Ferreira; et al. (Veterinary Research Communications, 2024)

Impact of self-pollination on the genetic diversity of inbred families of Psidium guajava L - Joameson Antunes Lima; Alexandre Pio Viana; Caio Cézar Guedes Correa; Debora Souza Mendes; Eileen Azevedo Santos; Flávia Alves da Silva; Letícia da Silva Araújo; Luis Carlos Loose Coelho; Mariana Zandomênico Mangeiro; Natália Veras Reis; Natan Ramos Cavalcante; Rogério Figueiredo Daher; et al. (Euphytica, 2024)

Antibacterial and Antibiofilm Activity of Croton urticifolius Lam. Essential Oil Via Membrane Disruption - Ellen Araújo Malveira; Aluska Kelly A. Nunes; Alexandre Lopes Andrade; Gabriel Lucas Carvalho Melo; Wildson Max Barbosa da Silva; Selene Maia de Morais; Hélcio Silva dos Santos; Leandro Bezerra de Lima; Cynthia Cavalcanti de Albuquerque; Diego Nathan do Nascimento Souza; Edson Holanda Teixeira; Mayron Alves de Vasconcelos (Current Microbiology, 2024)

Multiple events determine the distribution of fishes’ early life stages in the Abrolhos Bank, Southwestern Atlantic - André L.R. Lima; Cristiano Macedo Pereira; Alexandre Schiavetti; Carlos Werner Hackradt; Fabiana Cézar Félix-Hackradt (Marine Environmental Research, 2024)

The role of time to positive blood cultures in enhancing the predictive capability of DENOVA score for diagnosing infective endocarditis in patients with Enterococcus faecalis bacteremia - M Teresa Pérez-Rodríguez; Olalla Lima; Martín Garrido; Anniris Rincón; Lucía Martínez-Lamas; Alexandre Pérez-González; Alejandro Araújo; Antía Amoedo; Adrián Sousa; Ana López; Xurxo Cabrera; Martín Rubianes (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The Brazilian Santos basin underwater soundscape monitoring project (PMPAS-BS) - José Antonio Moreira Lima; William Soares Filho; Fabio C. Xavier; Thiago Pires de Paula; Angela Spengler; Fernando Gonçalves de Almeida; Diogo Peregrino Correa Pereira; Valéria Souza Rego; Cátia Galotta; Carlos Corrêa Junior; Alexandre Bazyl (Frontiers in Marine Science, 2024)
This paper describes the Santos Basin Underwater Soundscape Monitoring Project (PMPAS-BS), a Brazilian ocean soundscape monitoring initiative. The main objective of the project is to quantify and assess hydroacoustic noise of anthropogenic origin in a large sedimentary basin extending from 23° S to 28° S on the southeastern Brazilian continental margin of the South Atlantic Ocean. Noise associated with oil and gas (O&G) exploration and production activities is the primary target, but this oceanic region also has busy shipping lanes for commercial, military, and fishing vessels. The two main hubs of Brazil’s export and import of goods by sea are located in this region: Santos and Rio de Janeiro ports. The project has three measurement components: mobile monitoring based on gliders and drifting acoustic profilers, fixed shallow-water monitoring based on acoustic measurements at coastal stations near shipping lanes associated with exploration and production activities in the Santos Basin, and fixed oceanic monitoring based on deep-water mooring lines equipped with passive autonomous acoustic recorders near production units, shipping lanes, and areas with lower intensity of O&G activities (pristine or reference sites). Numerical modeling of anthropogenic underwater acoustic noise has also been included as a fourth project component. The PMPAS-BS covers an area of more than 251,000 km 2 and uses several instruments with different methods and sensors for acoustic measurements. Its results provide current sound levels over a very large region of the western South Atlantic, both in areas more and less affected by anthropogenic activities.

Pervasive transcription of plant organelle genomes: functional noncoding transcriptomes? - Matheus Sanita Lima; Alexandre Rossi Paschoal; Douglas Silva Domingues; David Roy Smith (Trends in Plant Science, 2024)

Anaplasmosis outbreaks in taurine and zebu cattle in Brazil: causes, treatments, and Anaplasma marginale genetic diversity - Luccas Lourenzzo Lima Lins Leal; Alliny Souza de Assis Cavalcante; Igor Maciel Lopes de Moraes; Vanessa Salvador; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina Maria Beltrán Zapa; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Eduardo Lima; Alexandre Braga Scarpa; Ricardo Antônio Amaral de Lemos; et al. (Tropical Animal Health and Production, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Why does identification matter? Thrips species (Thysanoptera: Thripidae) found in soybean in southern Brazil show great geographical and interspecific variation in susceptibility to insecticides - Luiz F. Warpechowski; Eduardo A. Steinhaus; Rafaella P. Moreira; Daniela N. Godoy; Venicius E. Preto; Luiz E. Braga; Amanda de F. Wendt; Alexandre C. Reis; Élison F.B. Lima; Juliano R. Farias; Oderlei Bernardi (Crop Protection, 2024)

New Perspectives in Stem Cell Transplantation and Associated Therapies to Treat Retinal Diseases: From Gene Editing to 3D Bioprinting - Gabrieli Bovi dos Santos; Théo Henrique de Lima-Vasconcellos; Marília Inês Móvio; Alexander Birbrair; Carolina Beltrame Del Debbio; Alexandre Hiroaki Kihara (Stem Cell Reviews and Reports, 2024)

Intraarticular monomethyl fumarate as a perspective therapy for osteoarthritis by macrophage polarization - Douglas Menezes de Souza; Kauê Franco Malange; Catarine Massucato Nishijima; Bruno Henrique de Melo Lima; Vinicius Cooper Capetini; Alexandre L. R. de Oliveira; Gabriel Forato Anhê; Claudia Herrera Tambeli; Carlos Amilcar Parada (Inflammopharmacology, 2024)

Facies analysis and paleoenvironment of the Poti Formation in the Itaueira and Floriano region: Contribution to the Carboniferous depositional history of the Parnaíba basin - João Vicente Tavares Calandrini de Azevedo; Zenilda Vieira Batista; Mário Ferreira de Lima Filho; Sonia Maria Oliveira Agostinho; Emmanuel Franco Neto; Willian Alexandre Lima de Moura; Thamara Welle Rodrigues Barbosa Van (Journal of South American Earth Sciences, 2024)

Quaternary sedimentation over the Precambrian basement of Borborema Province (NE, Brazil): Tectonic and climatic controls - Rizelda Regadas de Carvalho; Viviane Khoury Asfora; Willian Alexandre Lima de Moura; José Antonio Barbosa; Germano Mário Silva Ramos; Virgínio Henrique de Miranda Lopes Neumann (Journal of South American Earth Sciences, 2024)

Enzymatic stoichiometry in degraded soils after two decades of restoration in a Brazilian semiarid region - Danilo F. Silva; Ademir S.F. Araujo; Antonio Y.V. Lima; Jaedson C.A. Mota; Ícaro V. Nascimento; Alexandre S. Queiroz; Erika V. Medeiros; Diogo P. Costa; Vania M.M. Melo; Elke J.B.N. Cardoso; Jay P. Verma; Gabriel R. Smith; et al. (CATENA, 2024)

Nutritional strategies, performance, digestibility, and carcass traits of Santa Ines and Rabo Largo breeds in a tropical climate - Anderson Lopes Pereira; Michelle de Oliveira Maia Parente; Edegleicia Alves de Sousa; Arnaud Azevedo Alves; Anderson de Moura Zanine; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Francisca Cláudia da Silva de Sousa; Luana França dos Anjos; Hyanne Costa Lima; Miguel Arcanjo Moreira Filho; Hactus Souto Cavalcanti; et al. (Tropical Animal Health and Production, 2024)

Nutrient intake, productive and metabolic parameters of Nellore bulls feed a forage free diet using cottonseed cake as a fiber source - Angelo Herbet Moreira Arcanjo; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Alexandre Menezes Dias; Gelson dos Santos Difante; Vanessa Zirondi Longhini; Camila Soares Cunha; Antonio Leandro Chaves Gurgel; Eduardo de Assis Lima; Juliana Caroline Santos Santana; Manoel Gustavo Paranhos da Silva (Tropical Animal Health and Production, 2024)

Method for identification of hydrological seasons in the semi-arid Caatinga biome, Brazil - Nazaré Suziane Soares; Carlos Alexandre Gomes Costa; José Brenno Carneiro de Lima; Till Francke; José Carlos de Araújo (Hydrological Sciences Journal, 2024)

Concentrations, sources and risks of polycyclic aromatic hydrocarbons in sediments from the Parnaiba Delta basin, Northeast Brazil - Analine D.C. Andrade; Gabrielle M. Fernandes; Davi A. Martins; Rivelino M. Cavalcante; Michel R.B. Chaves; Alexandre A. de Souza; Jeremias P. da S. Filho; Ronaldo F. Nascimento; Sidney G. de Lima (Chemosphere, 2024)

Local attitudes towards conservation governance in a large tropical multiple-use Marine Protected Area in Brazil - José Gilmar Cavalcante de Oliveira Júnior; Ana Paula de Oliveira Santos; Ana Claudia Mendes Malhado; Carolina Neves Souza; Chiara Bragagnolo; Aline Olímpio dos Santos; Evelynne Letícia dos Santos Farias Cardoso de Barros; Felipe Alexandre Santos Vieira; Inaê Farias Vieira Dantas; Jacqueline Costa Aldabalde; João Vitor Campos-Silva; Johnny Antonio da Silva Lima; et al. (Ocean & Coastal Management, 2024)

A Fucose-Containing Sulfated Polysaccharide from Spatoglossum schröederi Potentially Targets Tumor Growth Rather Than Cytotoxicity: Distinguishing Action on Human Melanoma Cell Lines - Maíra Barbosa e Reis; Açucena Imparato Maximo; Jessica Maria Magno; Daniel de Lima Bellan; João Luiz Aldinucci Buzzo; Fernanda Fogagnoli Simas; Hugo Alexandre Oliveira Rocha; Edvaldo da Silva Trindade; Carolina Camargo de Oliveira (Marine Biotechnology, 2024)

Exploring the neuroprotective potential of antimicrobial peptides from Dinoponera quadriceps venom against pentylenetetrazole-induced seizures in vivo - Livia Correia Fernandes Paes; Dânya Bandeira Lima; Daniel Moreira Alves da Silva; José Tiago Valentin; Pedro Everson Alexandre de Aquino; Alicia Belén García-Jareño; Mar Orzaéz; Marta Maria de França Fonteles; Alice Maria Costa Martins (Toxicon, 2024)

Water security threats and solutions in the Grande River basin – One of the Brazilian agricultural frontiers - Alexandre Lima de F. Teixeira; Anik Bhaduri; Cesar Augusto Crovador Siefert; Md Sayed Iftekhar; Stuart E. Bunn; Saulo Aires de Souza; Marco Vinicius Castro Gonçalves; Larissa Corteletti da Costa (Science of The Total Environment, 2024)

Multivariate modeling and optimization of the reverse cationic flotation process of iron ore using depressant-modified starch - Matheus Furlan Pinheiro; José Izaquiel Santos da Silva; Clarissa Nascimento de Oliveira; Edilailsa Januário de Melo; Alexandre Boscaro França; Gisella Lamas Samanamud; Mateus de Souza Amaral; Renata Carolina Zanetti Lofrano; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Minerals Engineering, 2024)

Paleosol marked by contrasting formation processes: A pilot study using digital morphometrics in Southeastern Brazil - Fernanda Almeida Bócoli; Sérgio Henrique Godinho Silva; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Alexandre Uezu; Marco Aurélio Carbone Carneiro; Marta Vasconcelos Ottoni; et al. (CATENA, 2024)

Understanding the Water Quality Dynamics in a Large Tropical Reservoir Under Hydrological Drought Conditions - Maria Aparecida Melo Rocha; Mário U. G. Barros; Alexandre C. Costa; Francisco de Assis de Souza Filho; Iran Eduardo Lima Neto (Water, Air, & Soil Pollution, 2024)

Brominated flame retardants and natural organobrominated compounds in a vulnerable delphinid species along the Brazilian coast - Lara G. Vidal; Nara De Oliveira-Ferreira; João Paulo M. Torres; Alexandre F. Azevedo; Ana Carolina O. Meirelles; Leonardo Flach; Camila Domit; Ana Bernadete L. Fragoso; Flávio J. Lima Silva; Vítor Luz Carvalho; Milton Marcondes; Lupércio A. Barbosa; et al. (Science of The Total Environment, 2023)

Cryopreservation efficiency of red-rumped agouti (Dasyprocta leporina) sperm obtained from different origins through epididymal retrograde flushing or electroejaculation - Thibério de Sousa Castelo; Andréia Maria da Silva; Gislayne Christianne Xavier Peixoto; Ana Liza Paz Souza; Lívia Batista Campos; Gabriela Liberalino Lima; Maiko Roberto Tavares Dantas; João Batista Freire de Souza-Junior; Alexandre Rodrigues Silva (Cryobiology, 2023)

Detoxified castor seed meal replaces soybean meal in the supplement for Holstein-Zebu crossbred steers finished on tropical pasture during the rainy season - Silvia Layse Mendes Machado; Fabiano Ferreira da Silva; Gleidson Giordano Pinto de Carvalho; Laize Vieira Santos; João Wilian Dias Silva; Tarcísio Ribeiro Paixão; Vanessa Alexandre Vieira; Ana Paula Gomes da Silva; Marceliana da Conceição Santos; Dorgival Morais de Lima Júnior; Robério Rodrigues Silva (Tropical Animal Health and Production, 2023)

Effects of monensin in supplements for beef cattle in tropical grazing systems during the rainy season - Marina Pereira Souza Coutinho; Alyce Monteiro; Carlos Eduardo Avelino Cabral; Rodrigo Junqueira Pereira; Lívia Vieira de Barros; Lucas Gimenes Mota; Alexandre Lima de Souza; Carla Heloisa Avelino Cabral (Tropical Animal Health and Production, 2023)

The influence of marine protected areas on the patterns and processes in the life cycle of reef fishes - André L. R. Lima; Linda M. Eggertsen; Jessyca L. S. Teixeira; Alexandre Schiavetti; Fabiana C. Félix-Hackradt; Carlos W. Hackradt (Reviews in Fish Biology and Fisheries, 2023)

Forecasting effects of climate changes on the population genetic structure of Anacardium occidentale in the Cerrado biome, Brazil - Jacqueline Souza Lima; Rosane Garcia Collevatti; Leciane Kárita de Oliveira; Lázaro José Chaves; Ronaldo Veloso Naves; Thannya Nascimento Soares; José Alexandre Felizola Diniz Filho; Mariana Pires de Campos Telles (Genetica, 2023)

Energetic responses of head-out water immersion at different temperatures during post-exercise recovery and its consequence on anaerobic mechanical power - Marcelo Coertjens; Patricia Chaves Coertjens; Marcus Peikriszwili Tartaruga; Tatiane Gorski; Adriano Eduardo Lima-Silva; Lorival José Carminatti; Paulo Otto Beyer; Ana Paula Viola de Almeida; Jeam Marcel Geremia; Leonardo Alexandre Peyré-Tartaruga; Luiz Fernando Martins Kruel (European Journal of Applied Physiology, 2023)

Identification of pegmatites zones in Muiane and Naipa (Mozambique) from Sentinel-2 images, using band combinations, band ratios, PCA and supervised classification - Ubaldo Gemusse; Joana Cardoso-Fernandes; Alexandre Lima; Ana Teodoro (Remote Sensing Applications: Society and Environment, 2023)

Antioxidant potential of acerola by-product along the enterohepatic axis of rats fed a high-fat diet - Kamila Sabino Batista; Marcos dos Santos Lima; Adriano Francisco Alves; Hassler Clementino Cavalcante; Danielle Melo de Souza; Guilherme Costa de Oliveira; Lydiane Tavares Toscano; Alexandre Sérgio Silva; Josuel Feitosa Rodrigues; Bruno Raniere Lins de Albuquerque Meireles; Angela Maria Tribuzy de Magalhães Cordeiro; Darlene Camati Persuhn; et al. (Food Research International, 2023)

Advances in genomic characterization of Urochloa humidicola: exploring polyploid inheritance and apomixis - Aline da Costa Lima Moraes; Marcelo Mollinari; Rebecca Caroline Ulbricht Ferreira; Alexandre Aono; Letícia Aparecida de Castro Lara; Marco Pessoa-Filho; Sanzio Carvalho Lima Barrios; Antonio Augusto Franco Garcia; Cacilda Borges do Valle; Anete Pereira de Souza; Bianca Baccili Zanotto Vigna (Theoretical and Applied Genetics, 2023)

Spatiotemporal river–aquifer interactions of a large tropical dryland river with high anthropic intervention - Arthur Jordan de Azevedo Toné; Alexandre Cunha Costa; Mário Ubirajara Gonçalves Barros; Hermilson Barros de Freitas; José Rodrigo Vasconcelos Cavalcante; Iran Eduardo Lima Neto (Hydrological Sciences Journal, 2023)

Polymeric Nanocapsules Containing Ozonated Oil and Terbinafine Hydrochloride as a Potential Treatment Against Dermatophytes - Francielli Lima dos Santos; Júlia Capp Zilles; Andressa Urbano Machado; Morgana Souza Marques; Bárbara Souza da Costa; Irene Clemes Kulkamp Guerreiro; Alexandre Meneghello Fuentefria; Renata Vidor Contri (AAPS PharmSciTech, 2023)

Behavioural compensation of extruded urea level and the effects of supplementation presencefor finished lambs in tropical grass pastures - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Roberto Germano Costa; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Alexandre Menezes Dias; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Neila Lidiany Ribeiro; Antonio Leandro Chaves Gurgel; Gabriela Oliveira de Aquino Monteiro; et al. (Small Ruminant Research, 2023)

Spray-chilling system in the initial cooling process of swine half carcasses - Alessandra Pereira dos Santos; Fabiana Ribeiro Caldara; Alexandre Rodrigo Mendes Fernandes; Maria Fernanda de Castro Burbarelli; Bruna de Souza Eberhart; Jean Kaique Valentim; Ibiara Correia de Lima Almeida Paz; Rodrigo Garófallo Garcia; Agnês Markiy Odakura (Meat Science, 2023)

Sink or carbon source? how the Opuntia cactus agroecosystem interacts in the use of carbon, nutrients and radiation in the Brazilian semi-arid region - Alexandre Maniçoba da Rosa Ferraz Jardim; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; Fabio Ricardo Marin; Magna Soelma Beserra de Moura; Leonor Patricia Cerdeira Morellato; Abelardo Antônio de Assunção Montenegro; Jean Pierre Henry Balbaud Ometto; João L.M.P. de Lima; José Carlos Batista Dubeux Júnior; Thieres George Freire da Silva (Journal of Hydrology, 2023)

Campomanesia guazumifolia infusion decreases human platelet aggregation by reducing cyclooxygenase 1 activity and its underlying mechanisms - Caroline Honaiser Lescano; Fernando Freitas de Lima; Taline Baganha Stefanello Catelan; Victor Hugo Dantas Guimarães; Ulisses Alves Pereira; Charles Martins Aguilar; Cláudia Andrea Lima Cardoso; Sérgio Henrique Sousa Santos; Alexandre Borges; Ivan Pires de Oliveira (Food Bioscience, 2023)

6-Nitrodopamine potentiates contractions of rat isolated vas deferens induced by noradrenaline, adrenaline, dopamine and electric field stimulation - José Britto-Júnior; Antonio Tiago Lima; Rafael Campos; Alexandre Asturiano Gião; Gustavo Duarte Mendes; Luiza P. Ferreira-Novaes Silva; Adriano Fregonesi; André Sampaio Pupo; Edson Antunes; Gilberto De Nucci (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

High cold tolerance and differential population response of third instars from the Zeugodacus tau complex to phytosanitary cold treatment in navel oranges - Vanessa S. Dias; Guy J. Hallman; Alexandre S. Araújo; Inajara V.G. Lima; Fabio L. Galvão-Silva; Luis A. Caravantes; Martha N.G. Rivera; Jhonatan S. Aguilar; Carlos E. Cáceres-Barrios; Marc J.B. Vreysen; Scott W. Myers (Postharvest Biology and Technology, 2023)

Li-rich pegmatites and related peraluminous granites of the Fregeneda-Almendra field (Spain-Portugal): A case study of magmatic signature for Li enrichment - Encarnación Roda-Robles; Romeu Vieira; Alexandre Lima; Jon Errandonea-Martin; Alfonso Pesquera; Joana Cardoso-Fernandes; Idoia Garate-Olave (Lithos, 2023)

COVID-19 and candiduria: an investigation of the risk factors and immunological aspects - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; Ana C. Lyon; Olindo A. Martins-Filho; et al. (Brazilian Journal of Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Mineralogy and geochemistry of ferromanganese nodules in semiarid calcareous soils from Northeastern Brazil - Rodrigo Santana Macedo; Alexandre Pereira de Bakker; Letícia Moro; Victor Junior Lima Felix; Raphael Moreira Beirigo (Journal of South American Earth Sciences, 2023)

From waste to the gut: Can blackcurrant press cake be a new functional ingredient? Insights on in vivo microbiota modulation, oxidative stress, and inflammation - Amanda dos Santos Lima; Rômulo Dias Novaes; Lucas Cezar Pinheiro; Leonardo Augusto de Almeida; Hercia Stampini Duarte Martino; Alexandre Giusti-Paiva; Nora Pap; Daniel Granato; Luciana Azevedo (Food Research International, 2023)

Spodosol formation on sandy ruins in a semi-arid climate in the Catimbau National Park, Northeast Brazil - Arnaldo Joaquim de Souza Junior; Danilo de Lima Camêlo; David Lukas de Arruda; Valdomiro Severino de Souza Junior; Alexandre Tavares da Rocha; Marcelo Metri Corrêa (CATENA, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Phylogenomic evolutionary insights in the fern family Gleicheniaceae - Lucas Vieira Lima; Alexandre Salino; Michael Kessler; Germinal Rouhan; Weston L. Testo; Caio Suzart Argolo; GoFlag Consortium; Thaís Elias Almeida (Molecular Phylogenetics and Evolution, 2023)

Vaginal temperature modeling in Holstein cows and cluster analysis by the cophenetic correlation coefficient - Marcos Vinícius da Silva; Héliton Pandorfi; Maria Simone Mendes Peixoto; José Antonio Delfino Barbosa Filho; Gledson Luiz Pontes de Almeida; Iran José Oliveira da Silva; Kenio Patrício Lima de Oliveira; Vinícius de Sena Sales Viana; José Francisco de Oliveira-Júnior; Cristiane Guiselini; Gabriel Thales Barboza Marinho; Marcio Mesquita; et al. (Journal of Thermal Biology, 2023)

Do wave exposure and drifting algae drive the functional diversity of fishes in tropical ocean-exposed sandy beaches? - Alexandre da Gama Fernandes Vieira Júnior; Éden Hávila Lima Guedes; Gitá Juan Soterorudá Brito; Juan Alves Pereira; Marina Dolbeth; e André Luiz Machado Pessanha (Estuarine, Coastal and Shelf Science, 2023)

Geochemical soil dynamics on a bimodal post-collisional intrusive complex - Kargean Vianna Barbosa; Diego Lang Burak; Carlos Eduardo Veiga de Carvalho; Filipe Altoé Temporim; Danilo de Lima Camêlo; Alexandre Rosa dos Santos (Environmental Monitoring and Assessment, 2023)

Germination, cytotoxicity, and mutagenicity in Lactuca sativa L. and Passiflora alata Curtis in response to sewage sludge application - Allan Rocha de Freitas; Nathália Aparecida Bragança Fávaris; Rodrigo Sobreira Alexandre; Tatiana da Silva Souza; Iasmini Nicoli Galter; Julcinara Oliveira Baptista; Paula Aparecida Muniz de Lima; Tamyris de Mello; Wagner Campos Otoni; José Carlos Lopes (Ecotoxicology, 2023)

A systematic review of energy and mass fluxes, and biogeochemical processes in seasonally dry tropical forests and cactus ecosystems - Alexandre Maniçoba da Rosa Ferraz Jardim; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; Daniela de Carvalho Lopes; Marcos Vinícius da Silva; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Jhon Lennon Bezerra da Silva; Antonio José Steidle Neto; Leonor Patricia Cerdeira Morellato; João L.M.P. de Lima; Thieres George Freire da Silva (Journal of South American Earth Sciences, 2023)

Comparative ABA-Responsive Transcriptome in Soybean Cultivars Submitted to Different Levels of Drought - Mayla Daiane Correa Molinari; Renata Fuganti-Pagliarini; Daniel de Amorim Barbosa; Elton Gargioni Grisoste Barbosa; João Matheus Kafer; Daniel Rockenbach Marin; Silvana Regina Rockenbach Marin; Liliane Marcia Mertz-Henning; Alexandre Lima Nepomuceno (Plant Molecular Biology Reporter, 2023)

Effects of rainfall and land use on nutrient responses in rivers in the Brazilian semiarid region - Letícia L. Freire; Alexandre C. Costa; Iran E. Lima Neto (Environmental Monitoring and Assessment, 2023)

Non-self glycan structures as possible modulators of cancer progression: would polysaccharides from Cryptococcus spp. impact this phenomenon? - Israel Diniz-Lima; Leonardo Marques da Fonseca; Jhenifer Santos Dos Reis; Debora Decote-Ricardo; Alexandre Morrot; Jose Osvaldo Previato; Lucia Mendonça Previato; Celio Geraldo Freire-de-Lima; Leonardo Freire-de-Lima (Brazilian Journal of Microbiology, 2023)

Modeling and optimization of the pyrolysis oil production process from polypropylene for the production of aviation kerosene - Heraclito Alexandre dos Santos; Igor José Boggione Santos; Cristiane Medina Finzi Quintão; Vagner Fernandes Knupp; Renata Carolina Zanetti Lofrano; Eliane Cristina de Oliveira; Gisella Lamas Samanamud; Mateus de Souza Amaral; Alexandre Boscaro França; Mariana Arruda Pereira; Matheus Teixeira Araújo Silva; Carla Cristina Almeida Loures; et al. (Clean Technologies and Environmental Policy, 2023)

Use of a product based on wood vinegar of Eucalyptus clone I144 used in the control of bovine mastitis - Bismark Alves da Silva; Francisco Marlon Carneiro Feijó; Nilza Dutra Alves; Alexandre Santos Pimenta; Leon Denner Moreira Benicio; Enilson Claudio da Silva Júnior; Caio Sérgio Santos; Alexsandra Fernandes Pereira; Yasmin Beatriz França Moura; Gil Sander Prospero Gama; Evilasio de Souza Lima Neto (Veterinary Microbiology, 2023)

Genotoxic effects of anthropogenic environments in the leaf litter-dwelling scorpion Tityus pusillus Pocock, 1893 (Scorpiones; Buthidae) - Aleson Aparecido da Silva; Érima Maria de Amorim; Maria Gislaine Pereira; Samuel Lima de Santana; Meykson Alexandre da Silva; André Felipe de Araujo Lira; Claudia Rohde (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Dwarf and tall elephant grass silages: intake, nutrient digestibility, nitrogen balance, ruminal fermentation, and ingestive behavior in sheep - Luciana Felizardo Pereira Soares; Adriana Guim; Alexandre Carneiro Leão de Mello; Marcelo de Andrade Ferreira; Francisco Fernando Ramos de Carvalho; Janaina de Lima Silva; Ana Caroline Cerqueira de Melo Vasco; Tomás Guilherme Pereira da Silva; Maria Luciana Menezes Wanderley Neves (Tropical Animal Health and Production, 2023)

Vitamin D3 improves spatial memory and modulates cytokine levels in aged rats - Tatiani Bellettini-Santos; Michelle Lima Garcez; Francielle Mina; Natália Quadros Magnus; Nathalia de Souza Pereira; Ariandne de Oliveira Marques; Gabriela Serafim Keller; Gabriel Casagrande Zabot; Natália Baltazar do Nascimento; Eduarda Behenck Medeiros; Lisienny Campoli Tono Rempel; Ewa Kucharska; et al. (Metabolic Brain Disease, 2023)

Spatial non-stationarity in the distribution of fish species richness of tropical streams - Thiago Bernardi Vieira; Jorge Iván Sánchez-Botero; Danielle Sequeira Garcez; Sergio Maia Queiroz Lima; Carla Simone Pavanelli; Lilian Casatti; Welber Senteio Smith; Evanilde Benedito; Rosana Mazzoni; Paulo Santos Pompeu; Carlos Sérgio Agostinho; Luciano Fogaça de Assis Montag; et al. (Community Ecology, 2023)

West–east diversification model explains pattern phylogeography of the Band-tailed Manakin Pipra fasciicauda - Dnilson Oliveira Ferraz; Larissa Sampaio; Keila de Araújo Lima; Juliana Araripe; Fernando Sequeira; Alexandre Aleixo; Pablo Vieira Cerqueira; Lincoln S. Carneiro; Péricles Sena do Rêgo (Journal of Ornithology, 2023)

Later prehistoric tin mining in the Ervedosa mine (Vinhais, Portugal): evidence and context - Emmanuelle Meunier; Filipa Dias; João Fonte; Alexandre Lima; Alexandra Rodrigues; Carlo Bottaini; Rui J. C. Silva; João P. Veiga; Manuel F. C. Pereira; Elin Figueiredo (Archaeological and Anthropological Sciences, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Application of artificial intelligence for tree risk assessment optimization in Itanhaém – São Paulo, Brazil - Tamara Ribeiro Botelho de Carvalho Maria; Daniela Biondi; Alexandre Behling; Allan Rodrigo Nunho dos Reis; Kendra Zamproni; Tatiane Lima Ho (Urban Forestry & Urban Greening, 2023)

Strategies to improve the competitiveness of an agroindustrial system for a macauba based oil production in Minas Gerais State, Brazil - Pâmela da Costa Lima Pires; Aldara da Silva César; Alexandre Nunes Cardoso; Simone Palma Favaro; Marco Antonio Conejero (Land Use Policy, 2023)

Tracing the origin of deposited sediments: A study applying proximal sensing in a drainage subbasin - Wellington de Lima; Marcelo Mancini; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Salvador Francisco Acuña-Guzman; José Alexandre Melo Demattê; Nilton Curi (Journal of South American Earth Sciences, 2023)

Structural characterization of exopolysaccharides obtained from Porphyridium cruentum exhausted culture medium - Nathana L. Cristofoli; Alexandre R. Lima; Ana M. Rosa da Costa; Dmitry Evtyugin; Carlos Silva; João Varela; Margarida C. Vieira (Food and Bioproducts Processing, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Biochar, compost, and their mixtures influence the dry mass of the shoot of Marandu palisade grass and soil nutritional status - Ivan Eusébio da Silva; Alexandre Santos Pimenta; Claudivan Feitosa de Lacerda; Neyton de Oliveira Miranda; Nayane da Silva Lima; Gustavo Cardoso Dias (Arabian Journal of Geosciences, 2023)

Effect of space allowance during transport of Dorper x Santa Inês lambs on biochemical stress parameters and meat quality - Fredson Vieira e Silva; Iran Borges; Simone Koprowski Garcia; Hemilly Cristina Menezes de Sá; Vandenberg Lira Silva; Alexandre Ribeiro Araújo; Jeânio Alexandre de Lima; Laura Lúcia dos Santos Oliveira; Aylle Medeiros Matos; Fabio Luiz Buranelo Toral (Small Ruminant Research, 2023)

Biological activities of organic extracts and specialized metabolites from different parts of Cryptomeria japonica (Cupressaceae) – A critical review - Ana Lima; Filipe Arruda; Alexandre Janeiro; Jorge Medeiros; José Baptista; João Madruga; Elisabete Lima (Phytochemistry, 2023)

Cattle tick and gastrointestinal nematodes strategic control in dairy 31/32 Gyr x Holstein and beef ½ Brangus: is the same way? - Artur Siqueira Nunes Trindade; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina María Beltrán Zapa; Lídia Mendes de Aquino; Lorena Lopes Ferreira; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Maycon Araújo Ruivo; Alexandre Braga Scarpa; Octaviano Pereira Neto; et al. (Livestock Science, 2023)

Chemical composition and prebiotic activity of baru (Dipteryx alata Vog.) pulp on probiotic strains and human colonic microbiota - Aline Medeiros Alves-Santos; Karoliny Brito Sampaio; Marcos dos Santos Lima; Alexandre Siqueira Guedes Coelho; Evandro Leite de Souza; Maria Margareth Veloso Naves (Food Research International, 2023)

Sugarcane yeast with urea in replace of soybean meal in the diet of Murrah buffaloes does not cause metabolic, endocrine, and mineral disorders - Bruna Higino de Souza Silva; Rebeka Menezes Pontes; Ayna Arramis Apolinário da Silva; Esdras Lima de Carvalho Gueiros; Emanuel Felipe de Oliveira Filho; Daniel da Silva Praia; Daniel Nunes de Araújo Gonçalves; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Cláudio Coutinho Bartolomeu; Pierre Castro Soares (Tropical Animal Health and Production, 2023)

Does Exogenous Vitamins Improve the Morphophysiological Condition of Sugarcane Subjected to Water Deficit? - Emanuel Bispo Ramos; Samuel Bispo Ramos; Sérgio Bispo Ramos; Paulo Alexandre Monteiro de Figueiredo; Ronaldo da Silva Viana; Eduardo Pradi Vendruscolo; Sebastião Ferreira de Lima (Sugar Tech, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

Correction to: Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Inter-comparison of optical and SAR-based forest disturbance warning systems in the Amazon shows the potential of combined SAR-optical monitoring - Juan Doblas Prieto; Lucas Lima; Stephane Mermoz; Alexandre Bouvet; Johannes Reiche; Manabu Watanabe; Sidnei Sant Anna; Yosio Shimabukuro (International Journal of Remote Sensing, 2023)

The Late Jurassic–Early Cretaceous lacustrine facies and ichnofossils of the Parnaíba Basin, Brazil: A record of bioactivity in response to post-CAMP thermal subsidence in West Gondwana - Argel de Assis Nunes Sodré; Joelson Lima Soares; Afonso César Rodrigues Nogueira; Alexandre Ribeiro Cardoso; Renan Fernandes dos Santos (Sedimentary Geology, 2023)

Egg production by the exotic shrimp Athanas dimorphus (Caridea: Alpheidae) in a harbor area in northeastern Brazil - Renata Fernanda Lima-Silva; Guidomar Oliveira Soledade; Régis Augusto Pescinelli; Alexandre Oliveira Almeida (Regional Studies in Marine Science, 2023)

Hydrogelled emulsion from linseed oil and pea protein as a strategy to produce healthier pork burgers with high technological and sensory quality - Leticia de Lima Guterres; Mariana Basso Pinton; Bibiana Alves dos Santos; Leticia Pereira Correa; Madison Willy Silva Cordeiro; Roger Wagner; Alexandre José Cichoski; José Manuel Lorenzo; Paulo Cezar Bastianello Campagnol (Meat Science, 2023)

High-power ultrasound, micronized salt, and low KCl level: An effective strategy to reduce the NaCl content of Bologna-type sausages by 50% - Jordana Lima da Rosa; Juan Dario Rios-Mera; Carmen Josefina Contreras Castillo; José Manuel Lorenzo; Mariana Basso Pinton; Bibiana Alves dos Santos; Leticia Pereira Correa; Alessandra Schneider Henn; Alexandre José Cichoski; Erico Marlon Moraes Flores; Paulo Cezar Bastianello Campagnol (Meat Science, 2023)

Environmental degradation of vegetation cover and water bodies in the semiarid region of the Brazilian Northeast via cloud geoprocessing techniques applied to orbital data - Jhon Lennon Bezerra da Silva; Geber Barbosa de Albuquerque Moura; Marcos Vinícius da Silva; José Francisco de Oliveira-Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Daiana Caroline Refati; Ricardo da Cunha Correia Lima; Ailton Alves de Carvalho; Maria Beatriz Ferreira; José Ivaldo Barbosa de Brito; Roni Valter de Souza Guedes; Pabrício Marcos Oliveira Lopes; et al. (Journal of South American Earth Sciences, 2023)

Comparative study of the production of cellulose nanofibers from agro-industrial waste streams of Salicornia ramosissima by acid and enzymatic treatment - Alexandre R. Lima; Nathana L. Cristofoli; Ana M. Rosa da Costa; Jorge A. Saraiva; Margarida C. Vieira (Food and Bioproducts Processing, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Inclusion of palm kernel cake in the supplement reduces nutrient digestibility but does not interfere with the performance of steers finished on tropical pasture - Michelle Patrícia Fraser Salt; Fabiano Ferreira da Silva; Gleidson Giordano Pinto de Carvalho; Laize Vieira Santos; Sinvaldo Oliveira de Souza; Vanessa Alexandre Vieira; Tarcísio Ribeiro Paixão; João Wilian Dias Silva; Dorgival Morais de Lima Júnior; Robério Rodrigues Silva (Tropical Animal Health and Production, 2022)

Canopy defoliation by leaf-cutting ants in eucalyptus plantations inferred by unsupervised machine learning applied to remote sensing - Alexandre dos Santos; Isabel Carolina de Lima Santos; Jeffersoney Garcia Costa; Zakariyyaa Oumar; Mariane Camargo Bueno; Tarcísio Marcos Macedo Mota Filho; Ronald Zanetti; José Cola Zanuncio (Precision Agriculture, 2022)

The impact of COVID-19 on antimicrobial prescription and drug resistance in fungi and bacteria - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Nalu T. A. Peres; Rachel B. Caligiorne; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; et al. (Brazilian Journal of Microbiology, 2022)

A novel in vitro propagation system for West Indian elm [Guazuma ulmifolia Lam. (Malvaceae)]: a valuable medicinal woody species - Mayla de Jesus Santana; Sebastião Martins Barbosa-Júnior; Lana Laene Lima Dias; Lázara Aline Simões Silva; Givanildo Zildo da Silva; Evandro Alexandre Fortini; Diego Silva Batista; Wagner Campos Otoni; Antônio Paulino da Costa Netto; Diego Ismael Rocha (In Vitro Cellular & Developmental Biology - Plant, 2022)

In vitro and in silico cytotoxicity of hinokinin-loaded PLGA microparticle systems against tumoral SiHa cells - Regiane G. de Lima; Flavia C. R. Lisoni; Thais B. Picão; Fransérgio F. dos Santos; Renato P. Orenha; Alexandre Borges; Eduardo F. Molina; Renato L. T. Parreira; Márcio L. A. e Silva; Mario F. C. Santos; Rosangela da S. de Laurentiz (Natural Product Research, 2022)

Techniques for monitoring dairy calves against the tick fever agents: a comparative analysis - Luciana Maffini Heller; Dina María Beltrán Zapa; Luiz Fellipe Monteiro Couto; Lídia Mendes de Aquino Gontijo; João Eduardo Nicaretta; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Lorena Lopes Ferreira; Hariye Victória Iuasse; Alexandre Braga Scarpa; João Ricardo de Souza Martins; et al. (Veterinary Research Communications, 2022)

Genetic gains in Passiflora for resistance to cowpea aphid-borne mosaic virus using recurrent selection - Débora Souza Mendes; Alexandre Pio Viana; Eileen Azevedo Santos; Natan Ramos Cavalcante; Cleidiane Alves Rodrigues; Joameson Antunes Lima; Ravena Ferreira Vidal; Fernando Henrique de Barros Walter; Luan Baritiello da Silva Bezerra; Marcelo Eiras; Huarrisson Azevedo Santos (Euphytica, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Ruminal kinetics and nutritive value of Zuri grass silage harvested at different ages and added with powder molasses - Omar Ali; Luciana Junges; Eva Nara Oliveira Gomes; Juliana Oliveira Batistoti; Anderson Ramires Candido; Fernanda de Kássia Gomes; Rafael de Oliveira Lima; Amarildo Pedro da Silva; Jeniffer da Cruz Siqueira; Luís Carlos Vinhas Ítavo; Elson Martins Coelho; Gelson dos Santos Difante; et al. (Tropical Animal Health and Production, 2022)

MicroRNAs expression profiles in early responses to different levels of water deficit in Setaria viridis - Karoline Estefani Duarte; Marcos Fernando Basso; Nelson Geraldo de Oliveira; José Cleydson Ferreira da Silva; Bruno de Oliveira Garcia; Bárbara Andrade Dias Brito Cunha; Thiago Bergamo Cardoso; Alexandre Lima Nepomuceno; Adilson Kenji Kobayashi; Thaís Ribeiro Santiago; Wagner Rodrigo de Souza; Hugo Bruno Correa Molinari (Physiology and Molecular Biology of Plants, 2022)

Trichoderma as a biological agent of Fusarium oxysporum species complex and Vigna unguiculata growth promoter - Ana Cláudia Tenório do Amaral; Marília de Holanda Cavalcanti Maciel; Alexandre Reis Machado; Luciana Gonçalves de Oliveira; Cristiano Souza Lima; Antonio Félix da Costa; Neiva Tinti de Oliveira (European Journal of Plant Pathology, 2022)

Cilostazol attenuates cardiac oxidative stress and inflammation in hypercholesterolemic rats - Rosane de Oliveira Lopes; Gabriel Ferreira Lima; Ana Beatriz Araújo Mendes; Lis Jappour Autran; Nikolas Cunha de Assis Pereira; Stephani Correia Brazão; Beatriz Alexandre-Santos; Eliete Dalla Corte Frantz; Christianne Brêtas Vieira Scaramello; Fernanda Carla Ferreira Brito; Nadia Alice Vieira Motta (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Role of 5-HT2A receptors in the effects of ayahuasca on ethanol self-administration using a two-bottle choice paradigm in male mice - Yasmim A. Serra; Thaísa Barros-Santos; Alexia Anjos-Santos; Natali D. Kisaki; Caio Jovita-Farias; João P. C. Leite; Maria C. E. Santana; João P. S. A. Coimbra; Nailton M. S. de Jesus; Agnieszka Sulima; Paulo C. R. Barbosa; Elena L. A. Malpezzi-Marinho; et al. (Psychopharmacology, 2022)

Evaluation of the antifungal activity of α, β, and δ-damascone and inclusion complexes in β-cyclodextrin against Candida spp - Maria Rayane Correia de Oliveira; Maria Gabriely de Lima Silva; Antonia Thassya Lucas dos Santos; Francisco Lucas Alves Batista; Roger Henrique Sousa da Costa; Anita Oliveira Brito Pereira Bezerr Martins; Beatriz Gonçalves da Cruz; Maria Flaviana Bezerra Morais-Braga; Henrique Douglas Melo Coutinho; Francisco Ernani Alves Magalhães; Diniz Maciel de Sena Junior; Alexandre Magno Rodrigues Teixeira; et al. (Folia Microbiologica, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Eugenia uniflora, Melaleuca armillaris, and Schinus molle essential oils to manage larvae of the filarial vector Culex quinquefasciatus (Diptera: Culicidae) - Júlia Assunção de Castro Oliveira; Lorena Sales Ferreira; Israel Pereira Garcia; Hérica de Lima Santos; Gustavo Sales Ferreira; João Pedro Miranda Rocha; Stênio Alves Nunes; Alexandre Alves de Carvalho; José Eduardo Brasil Pereira Pinto; Suzan Kelly Vilela Bertolucci (Environmental Science and Pollution Research, 2022)

Cadmium and lead transfer factors to kale plants (Brassica oleracea var. acephala) grown in mountain agroecosystem and its risk to human health - Rafael Gomes da Mota Gonçalves; Carlos Antônio dos Santos; Farley Alexandre da Fonseca Breda; Erica Souto Abreu Lima; Margarida Goréte Ferreira do Carmo; Camila da Costa Barros de Souza; Nelson Moura Brasil do Amaral Sobrinho (Environmental Monitoring and Assessment, 2022)

Importance of pneumatophore fringe-mudflat continuum for an estuary-dependent fish species - Juan Alves Pereira; Alexandre da Gama Fernandes Vieira Júnior; Éden Hávila Lima Guedes; Bianca de Freitas Terra; André Luiz Machado Pessanha (Marine Biology Research, 2022)

Cotton cake as an economically viable alternative fibre source of forage in a high-concentrate diet for finishing beef cattle in feedlots - Angelo Herbet Moreira Arcanjo; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Gumercindo Loriano Franco; Alexandre Menezes Dias; Gelson dos Santos Difante; Eduardo de Assis Lima; Juliana Caroline Santos Santana; Antonio Leandro Chaves Gurgel (Tropical Animal Health and Production, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Modulation of structural carbohydrates, phenol compounds and lignin content in Eucalyptus urophylla cuttings grown under boron, copper and zinc induced-deficiency - Liamara Santos Masullo; Vitória Duarte Derisso; Gislene Roberta Manarim; Alexandre de Vicente Ferraz; José Henrique Tertulino Rocha; Patrícia Andressa de Ávila; Antonio Leite Florentino; Claudio Lima de Aguiar; José Lavres; José Leonardo de Moraes Gonçalves (New Forests, 2022)

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Assessing ZWD models in delay and height domains using data from stations in different climate regions - Thainara Munhoz Alexandre de Lima; Marcelo Santos; Daniele Barroca Marra Alves; Thalia Nikolaidou; Tayná Aparecida Ferreira Gouveia (Applied Geomatics, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Ergogenic potential of foods for performance and recovery: a new alternative in sports supplementation? A systematic review - Matheus S. Costa; Luciana T. Toscano; Lydiane de Lima Tavares Toscano; Vanessa R. Luna; Rayanne A. Torres; Janilson A. Silva; Alexandre S. Silva (Critical Reviews in Food Science and Nutrition, 2022)

Reserve mobilization and in vitro germination of Euterpe edulis (Martius) seeds at different maturation stages - Tamyris de Mello; Thuanny Lins Monteiro Rosa; Ingridh Medeiros Simões; Paula Aparecida Muniz de Lima; Breno Benvindo dos Anjos; Caroline Palacio de Araujo; Clovis Eduardo Nunes Hegedus; Heloisa Oliveira dos Santos; Wagner Campos Otoni; Rodrigo Sobreira Alexandre; José Calos Lopes (Trees, 2022)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of three methods for manually counting fish in dam turbines using DIDSON - Lorrana Thaís Máximo Durville Braga; Alejandro Giraldo; Alexandre Lima Godinho (Hydrobiologia, 2022)

Evaluation of cytotoxic, immunomodulatory effects, antimicrobial activities and phytochemical constituents from various extracts of Passiflora edulis F. flavicarpa (Passifloraceae) - Georon Ferreira de Sousa; Dayane Kelly Dias do Nascimento Santos; Ricardo Sérgio da Silva; Bárbara Rafaela da Silva Barros; Iranildo José da Cruz-Filho; Bárbara de Azevedo Ramos; Túlio Diego da Silva; Pérsio Alexandre da Silva; Reginaldo Gonçalves de Lima-Neto; Norma Buarque de Gusmão; Marcia Silva do Nascimento; Cristiane Moutinho Lagos de Melo (Natural Product Research, 2021)

Rumen fermentation and metabolic profile of rams fed with diets amended cottonseed cake - Fagton de Mattos Negrão; Anderson de Moura Zanine; Marinaldo Divino Ribeiro; Daniele de Jesus Ferreira; Alexandre Lima de Souza; Michelle de Oliveira Maia Parente; Henrique Nunes Parente; Rafael Henrique Pereira dos Reis; Túlio Otávio Jardim D.’Almeida Lins; Anny Graycy Vasconcelos de Oliveira Lima (Tropical Animal Health and Production, 2021)

Unmanned aerial vehicle to evaluate frost damage in coffee plants - Diego Bedin Marin; Gabriel Araújo e Silva Ferraz; Felipe Schwerz; Rafael Alexandre Pena Barata; Rafael de Oliveira Faria; Jessica Ellen Lima Dias (Precision Agriculture, 2021)

Endocannabinoid System Attenuates Oxaliplatin-Induced Peripheral Sensory Neuropathy Through the Activation of CB1 Receptors - Anamaria Falcão Pereira; Mario Roberto Pontes Lisboa; Bruno Wesley de Freitas Alves; Cristiane Maria Pereira da Silva; Diego Bernarde Souza Dias; Karoline Luanne Santos de Menezes; Francisco Rafael Alves Santana Cesário; Jonas Costa de França; Amanda Rocha de Oliveira; Jaime Eduardo Cecilio Hallak; Antonio Waldo Zuardi; José Alexandre Crippa; et al. (Neurotoxicity Research, 2021)

Heat Stress Affects the Physiological and Biochemical Quality of Dalbergia nigra Seeds in vitro - Ingridh Medeiros Simões; Julcinara Oliveira Baptista; Thuanny Lins Monteiro Rosa; Tamyris de Mello; Caroline Palacio de Araujo; Paula Aparecida Muniz de Lima; Breno Benvindo dos Anjos; João Paulo Bestete de Oliveira; Marcos Vinicius Winckler Caldeira; Wagner Campos Otoni; Rodrigo Sobreira Alexandre; José Carlos Lopes (Forest Science, 2021)
The jacaranda of Bahia (Dalbergia nigra (Vell.) Allemão ex Benth) is an endemic tree of a Brazilian neotropical biodiversity hotspot and is of great ecological and economic interest. Given the threat of extinction due to timber overexploitation and climate change, the present study aimed to analyze the physiological and biochemical quality of D. nigra seeds exposed to heat stress. The seeds were sown in a test tube containing woody plant culture medium, kept in a biochemical oxygen demand chamber at 45°C for 0, 24, 48, 72, and 96 hours, and then maintained in the same chamber at 25°C for 30 days. Physiological analyses of moisture, electrical conductivity, germination speed index, normal and abnormal seedlings, seedling length, root length, hypocotyl length, collar diameter, seedling and root dry mass, and Dickson quality index revealed a drop in germination and vigor with prolonged heat stress, dropping from 95% to 0% between 0 and 96 hours. This was accompanied by a reduction in the content of carbohydrates, lipids, and proteins. Therefore, the vigor and quality of seedlings is negatively influenced by exposure to heat stress at 45°C.

Haemogregarine of Genus Dactylosoma (Adeleorina: Dactylosomatidae) in Species of Rhinella (Anura: Bufonidae) from the Brazilian Amazon - Tássio Alves Coêlho; Darlison Chagas De Souza; Evelyn da Costa Oliveira; Lincoln Lima Correa; Lúcio André Viana; Ricardo Alexandre Kawashita-Ribeiro (Acta Parasitologica, 2021)

Using leaf-based hyperspectral reflectance for genotype classification within a soybean germplasm collection assessed under different levels of water availability - Luís Guilherme Teixeira Crusiol; Patricia Braga; Marcos Rafael Nanni; Renato Herrig Furlanetto; Rubson Natal Ribeiro Sibaldelli; Everson Cezar; Liang Sun; José Salvador Simonetto Foloni; Liliane Marcia Mertz-Henning; Alexandre Lima Nepomuceno; Norman Neumaier; José Renato Bouças Farias (International Journal of Remote Sensing, 2021)

Spatio-temporal Patterns of River Water Quality in the Semiarid Northeastern Brazil - Letícia Lacerda Freire; Alexandre Cunha Costa; Iran Eduardo Lima Neto (Water, Air, & Soil Pollution, 2021)

Reproductive and Stress Response Hormones of the Critically Endangered Southern Muriqui (Brachyteles arachnoides: Atelidae) Under Captive Conditions - Alexandre Bastos Fernandes Lima; Gisela Sobral; Gabriela Siqueira Martins; Alcides Pissinatti; Priscila Viau; Claudio Alvarenga de Oliveira (International Journal of Primatology, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Assessing the potential of using high spatial resolution daily NDVI-time-series from planet CubeSat images for crop monitoring - Luís Guilherme Teixeira Crusiol; Liang Sun; Ruiqing Chen; Zheng Sun; Dejun Zhang; Zhongxin Chen; Deji Wuyun; Marcos Rafael Nanni; Alexandre Lima Nepomuceno; José Renato Bouças Farias (International Journal of Remote Sensing, 2021)

Soybean yield and nutrition after tropical forage grasses - Nídia Raquel Costa; Marcelo Andreotti; Carlos Alexandre Costa Crusciol; Cristiano Magalhães Pariz; João William Bossolani; Isabô Melina Pascoaloto; César Gustavo da Rocha Lima; Carolina dos Santos Batista Bonini; André Michel de Castilhos; Juliano Carlos Calonego (Nutrient Cycling in Agroecosystems, 2021)

JM-20 Treatment After Mild Traumatic Brain Injury Reduces Glial Cell Pro-inflammatory Signaling and Behavioral and Cognitive Deficits by Increasing Neurotrophin Expression - Andrezza Bond Vieira Furtado; Debora Farina Gonçalves; Diane Duarte Hartmann; Aline Alves Courtes; Gustavo Cassol; Yanier Nunez-Figueredo; Deivison Silva Argolo; Ravena Pereira do Nascimento; Silvia Lima Costa; Victor Diogenes Amaral da Silva; Luiz Fernando Freire Royes; Félix Alexandre Antunes Soares (Molecular Neurobiology, 2021)

Assessment of Natural and Post-Extraction Biomass from Acrocomia totai leaves: a Renewable Source of Energy - Gredson Keiff Souza; Alexandre Diório; Hugo Henrique Carline de Lima; Rogerio dos Santos Maniezzo; Andrelson Wellington Rinaldi; Nehemias Curvelo Pereira; Armando Mateus Pomini (BioEnergy Research, 2021)

Improved cotton transformation protocol mediated by Agrobacterium and biolistic combined-methods - Thuanne Pires Ribeiro; Isabela Tristan Lourenço-Tessutti; Bruno Paes de Melo; Carolina Vianna Morgante; Alvaro Salles Filho; Camila Barrozo Jesus Lins; Gilanna Falcão Ferreira; Glênia Nunes Mello; Leonardo Lima Pepino Macedo; Wagner Alexandre Lucena; Maria Cristina Mattar Silva; Osmundo Brilhante Oliveira-Neto; et al. (Planta, 2021)

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Dietary nutrient restrictions in the post-weaning period change Santa Inês ewe lamb nutritional metabolic profile - Clésio dos Santos Costa; Marcos Cláudio Pinheiro Rogério; Alexandre Lima Ferreira; Fernanda Samarini Machado; Roberto Cláudio Fernandes Franco Pompeu; Francisco Gleyson da Silveira Alves; João Paulo Arcelino do Rêgo; Patrícia Guimarães Pimentel; James Pierre Muir; José Neuman Miranda Neiva (Tropical Animal Health and Production, 2021)

Co-occurrences of tropical trees in eastern South America: disentangling abiotic and biotic forces - Emma-Liina Marjakangas; Otso Ovaskainen; Nerea Abrego; Vidar Grøtan; Alexandre A. de Oliveira; Paulo I. Prado; Renato A. F. de Lima (Plant Ecology, 2021)
Species co-occurrences in local communities can arise independent or dependent on species’ niches. However, the role of niche-dependent processes has not been thoroughly deciphered when generalized to biogeographical scales, probably due to combined shortcomings of data and methodology. Here, we explored the influence of environmental filtering and limiting similarity, as well as biogeographical processes that relate to the assembly of species’ communities and co-occurrences. We modelled jointly the occurrences and co-occurrences of 1016 tropical tree species with abundance data from inventories of 574 localities in eastern South America. We estimated species co-occurrences as raw and residual associations with models that excluded and included the environmental effects on the species’ co-occurrences, respectively. Raw associations indicate co-occurrence of species, whereas residual associations indicate co-occurrence of species after accounting for shared responses to environment. Generally, the influence of environmental filtering exceeded that of limiting similarity in shaping species’ co-occurrences. The number of raw associations was generally higher than that of the residual associations due to the shared responses of tree species to the environmental covariates. Contrary to what was expected from assuming limiting similarity, phylogenetic relatedness or functional similarity did not limit tree co-occurrences. The proportions of positive and negative residual associations varied greatly across the study area, and we found a significant tendency of some biogeographical regions having higher proportions of negative associations between them, suggesting that large-scale biogeographical processes limit the establishment of trees and consequently their co-occurrences.

Tectona grandis canopy cover predicted by remote sensing - Isabel Carolina de Lima Santos; Alexandre dos Santos; Jerffersoney Garcia Costa; Anderson Melo Rosa; Antonio José Vinha Zanuncio; Ronald Zanetti; Zakariyyaa Oumar; José Cola Zanuncio (Precision Agriculture, 2021)

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

Variability factors of heavy metals in soils and transfer to pasture plants of Mayabeque in Cuba - Yusimí Pérez Lopéz; Farley Alexandre da Fonseca Breda; Erica Souto Abreu Lima; Camila da Costa Barros de Souza; José Manoel Febles González; Nelson Moura Brasil do Amaral Sobrinho (Environmental Monitoring and Assessment, 2021)

Dwarf versus tall elephant grass in sheep feed: which one is the most recommended for cut-and-carry? - Jordânia Kely Barbosa da Silva; Márcio Vieira da Cunha; Mércia Virgínia Ferreira dos Santos; André Luiz Rodrigues Magalhães; Alexandre Carneiro Leão de Mello; José Ricardo Coelho da Silva; Clóves Isaack da Rocha Souza; Adriana Lima de Carvalho; Evaristo Jorge Oliveira de Souza (Tropical Animal Health and Production, 2021)

Application of remote sensing data in gold exploration: targeting hydrothermal alteration using Landsat 8 imagery in northern Portugal - Rui Frutuoso; Alexandre Lima; Ana Cláudia Teodoro (Arabian Journal of Geosciences, 2021)

Ethylene Signaling Causing Tolerance of Arabidopsis thaliana Roots to Low pH Stress is Linked to Class III Peroxidase Activity - Jonathas Pereira Graças; Joni Esrom Lima; Lázaro Eustáquio Pereira Peres; Elisabeth Jamet; Christophe Dunand; Victor Alexandre Vitorello; Christian Chervin (Journal of Plant Growth Regulation, 2021)

Trade‐offs between ontogenetic changes and food consumption in Brazilian silverside Atherinella brasiliensis from two tropical estuaries - Alexandre da Gama Fernandes Vieira Júnior; Diele Emele Pontes Carvalho de Lima; Natalice dos Santos Sales; Bianca de Freitas Terra; André Pessanha (Journal of Fish Biology, 2021)
Salinity variation in estuarine environments influences the distribution of fish species as well as the availability of food resources to be used by them. This study examines the effect of the range of salinity on the trade‐off between growth and feeding intensity of Atherinella brasiliensis from two tropical estuaries (positive and hypersaline). To investigate the effects of salinity, we hypothesized that hypersalinity negatively affects foraging intensity, consumption and prey selection by the Brazilian silverside, leading to differences in body condition . Sampling was carried out using the beach seine method in two areas of the estuaries (upper and lower zone) during rainy and dry periods. A total of 2549 stomachs (1124 for the positive estuary and 1425 for the hypersaline estuary) were examined, and the results indicated a dissimilarity of 92.7% of the diet between environments. In the positive estuary, there was more predation on Calanoida, Gastropoda, Hymenoptera, Ceratopogonidae larvae and Decapoda larvae, while Alga and plant‐material characterized the diet in the hypersaline estuary. Significant correlations between the volume of food and salinity were observed in both estuaries. The vacuity index indicated that hypersaline environments presented higher contributions of semifull stomachs, indicating an intense consumption of algae. On the other hand,in the positive estuary, these values were less intense, but the stomachs were always with animal items. The variation found for both environments reinforces the effect of salinity on the physiological mechanism of the populations once the higher proportions of filled stomachs in the hypersaline environment indicate the need for constant and high ingestion of prey to guarantee the pronounced energy expenditure with osmoregulation.

Cascade screening and genetic diagnosis of familial hypercholesterolemia in clusters of the Southeastern region from Brazil - Júnea Paolucci de Paiva Silvino; Cinthia Elim Jannes; Mauricio Teruo Tada; Isabella Ramos Lima; Iêda de Fátima Oliveira Silva; Alexandre Costa Pereira; Karina Braga Gomes (Molecular Biology Reports, 2020)

New lectins from Codium isthmocladum Vickers show unique amino acid sequence and antibiofilm effect on pathogenic bacteria - Rômulo Farias Carneiro; Philippe Lima Duarte; Renata Pinheiro Chaves; Suzete Roberta da Silva; Ramon Rodrigues Feitosa; Bruno Lopes de Sousa; Antônio Willame da Silva Alves; Mayron Alves de Vasconcelos; Bruno Anderson Matias da Rocha; Edson Holanda Teixeira; Alexandre Holanda Sampaio; Celso Shiniti Nagano (Journal of Applied Phycology, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Guanosine Neuroprotection of Presynaptic Mitochondrial Calcium Homeostasis in a Mouse Study with Amyloid-β Oligomers - Jussemara Souza da Silva; Yasmine Nonose; Francieli Rohden; Pâmela C. Lukasewicz Ferreira; Fernanda Urruth Fontella; Andréia Rocha; Andressa Wigner Brochier; Rodrigo Vieira Apel; Thais Martins de Lima; Bianca Seminotti; Alexandre Umpierrez Amaral; Antonio Galina; et al. (Molecular Neurobiology, 2020)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Algrizea Minor Sobral, Faria & Proença (Myrteae, Myrtaceae): chemical composition, antinociceptive, antimicrobial and antioxidant activity of essential oil - Bruno Oliveira de Veras; Yago Queiroz dos Santos; Fernanda Granja da Silva Oliveira; Jackson Roberto Guedes da Silva Almeida; Alexandre Gomes da Silva; Maria Tereza dos Santos Correia; Katharina Marques Diniz; João Ricardhis Saturnino de Oliveira; Vera Lúcia de Menezes Lima; Daniela Maria do Amaral Ferraz Navarro; Júlio César Ribeiro de Oliveira Farias de Aguiar; Maria Betânia Melo de Oliveira; et al. (Natural Product Research, 2020)

Phenolic compounds: antioxidant and larvicidal potential of Smilax brasiliensis Sprengel leaves - Paula Avelar Amado; Ana Hortência Fonsêca Castro; Stênio Nunes Alves; Denise Brentan Silva; Carlos Alexandre Carollo; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2020)

Seroepidemiological study of Caseous lymphadenitis in sheep from the Northeast region of Brazil using an indirect ELISA - José Romero Alexandre Alves; Areano Ethério Moreira de Farias; Denize Monteiro dos Anjos; Ana Milena Cézar Lima; Patrícia Yoshida Faccioli-Martins; Carlos José Hoff de Souza; Raymundo Rizaldo Pinheiro; Francisco Selmo Fernandes Alves; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2020)

Geographic variation in the whistles of bottlenose dolphins ( Tursiops spp.) in the southwestern Atlantic Ocean - Isabela M. S. Lima; Rihel Venuto; Carolina Menchaca; Lilian S. Hoffmann; Luciano Dalla Rosa; Rodrigo Genoves; Pedro F. Fruet; Andrea Milanelli; Paula Laporta; Bettina Tassino; Stephanie M. Bueno; Thales R. O. Freitas; et al. (Marine Mammal Science, 2020)

Data-space inversion with ensemble smoother - Mateus M. Lima; Alexandre A. Emerick; Carlos E. P. Ortiz (Computational Geosciences, 2020)

Humidity effects on avian blood parasites in the Caatinga of Brazil - Regina Carolina Ferreira de Souza Gomes; Bárbara Luiza Barbosa Teixeira; Cássia Lima Silva Gusmão; Alexandre M. Fernandes (Ornithology Research, 2020)

UAV-based thermal imaging in the assessment of water status of soybean plants - Luís Guilherme Teixeira Crusiol; Marcos Rafael Nanni; Renato Herrig Furlanetto; Rubson Natal Ribeiro Sibaldelli; Everson Cezar; Liliane Marcia Mertz-Henning; Alexandre Lima Nepomuceno; Norman Neumaier; José Renato Bouças Farias (International Journal of Remote Sensing, 2020)

Differential expression of the inflammasome complex genes in systemic lupus erythematosus - Heidi Lacerda Alves da Cruz; Catarina Addobbati Jordão Cavalcanti; Jaqueline de Azêvedo Silva; Camilla Albertina Dantas de Lima; Thiago Sotero Fragoso; Alexandre Domingues Barbosa; Andréa Tavares Dantas; Henrique de Ataíde Mariz; Angela Luzia Branco Pinto Duarte; Alessandra Pontillo; Sergio Crovella; Paula Sandrin-Garcia (Immunogenetics, 2020)

Concentration of Traces Metals in Underground Dams in the Semi-Arid of the Rio Grande do Norte State, Brazil: Case Study of the Sub-Basin of the Cobras River - Alexandre de Oliveira Lima; Nildo da Silva Dias; Cleyton dos Santos Fernandes; Francisco Pinheiro Lima Filho; Rene Chipana Rivera; Yago Leopoldo Eleuterio Gurgel de Sousa; Líssia Letícia de Paiva Oliveira; José Darcio Abrantes Sarmento; Hozano de Souza Lemos Neto (Water, Air, & Soil Pollution, 2020)

Novel specific primers for rapid identification of Macrophomina species - Kledson M. Santos; Graziele S. Lima; Ana P. O. Barros; Alexandre R. Machado; Cristina M. Souza-Motta; Kamila C. Correia; Sami Jorge Michereff (European Journal of Plant Pathology, 2020)

Implications of the post hoc blocking row–col technique on the intrapopulational improvement of the passion fruit - Roberta Flávia Cipriano Machado; Willian Krause; Celice Alexandre Silva; Leandro Rafael Fachi; Fernando Higino de Lima e Silva; Alexandre Pio Viana (Euphytica, 2020)

“Modern agriculture” transfers many pesticides to watercourses: a case study of a representative rural catchment of southern Brazil - José Augusto Monteiro de Castro Lima; Jérôme Labanowski; Marília Camotti Bastos; Renato Zanella; Osmar Damian Prestes; Jocelina Paranhos Rosa de Vargas; Leslie Mondamert; Eugenie Granado; Tales Tiecher; Mohsin Zafar; Alexandre Troian; Thibaut Le Guet; et al. (Environmental Science and Pollution Research, 2020)

Overcoming the worst of both worlds: integrating climate change and habitat loss into spatial conservation planning of genetic diversity in the Brazilian Cerrado - José Alexandre Felizola Diniz-Filho; Ana Clara de Oliveira Ferraz Barbosa; Lázaro José Chaves; Kelly da Silva e Souza; Ricardo Dobrovolski; Ludmila Rattis; Levi Carina Terribile; Matheus Souza Lima-Ribeiro; Guilherme de Oliveira; Fernanda Thiesen Brum; Rafael Loyola; Mariana Pires de Campos Telles (Biodiversity and Conservation, 2020)

Combination of pelleting and monensin does not affect antioxidant properties and fatty acids in milk of grazing dairy cows supplemented with a concentrate containing soybean seeds - Luiza Pozzi Marins Costa; Luciano Soares De Lima; Júlio Cesar Damasceno; Francilaine Eloise De Marchi; Fernanda Granzotto; Fabio Seiji dos Santos; Alexandre Leseur Dos Santos; Geraldo Tadeu dos Santos (Tropical Animal Health and Production, 2020)

β2 adrenergic interaction and cardiac autonomic function: effects of aerobic training in overweight/obese individuals - Jhennyfer Aline Lima Rodrigues; Gustavo Duarte Ferrari; Átila Alexandre Trapé; Vitor Nolasco de Moraes; Thiago Correa Porto Gonçalves; Simone Sakagute Tavares; Arnt Erik Tjønna; Hugo Celso Dutra de Souza; Carlos Roberto Bueno Júnior (European Journal of Applied Physiology, 2020)

Mapping defoliation by leaf-cutting ants Atta species in Eucalyptus plantations using the Sentinel-2 sensor - Alexandre dos Santos; Isabel Carolina de Lima Santos; Nubia da Silva; Ronald Zanetti; Zakariyyaa Oumar; Lucas Fernando Resende Guimarães; Mariane Bueno de Camargo; José Cola Zanuncio (International Journal of Remote Sensing, 2020)

Lawsone, a 2-hydroxy-1,4-naphthoquinone from Lawsonia inermis (henna), produces mitochondrial dysfunctions and triggers mitophagy in Saccharomyces cerevisiae - Mariana Rodrigues Xavier; Manuella Maria Silva Santos; Maise Gomes Queiroz; Mariza S. de Lima Silva; Alexandre José S. Goes; Marcos Antonio De Morais Jr (Molecular Biology Reports, 2020)

Physical–mechanical properties of wood panel composites produced with Qualea sp. sawdust and recycled polypropylene - Daiane Cristina Lima; Rafael Rodolfo de Melo; Alexandre Santos Pimenta; Talita Dantas Pedrosa; Maila Janaína Coelho de Souza; Elias Costa de Souza (Environmental Science and Pollution Research, 2020)

Cytochrome P450 2A6 and 2B6 polymorphisms and smoking cessation success in patients treated with varenicline - Paulo Roberto Xavier Tomaz; Mariana Soares Kajita; Juliana Rocha Santos; Jaqueline Scholz; Tânia Ogawa Abe; Patrícia Viviane Gaya; José Eduardo Krieger; Alexandre Costa Pereira; Paulo Caleb Júnior Lima Santos (European Journal of Clinical Pharmacology, 2019)

Origin and thermometry of graphites from Itapecerica supracrustal succession of the southern Sao Francisco Craton by C isotopes, X-ray diffraction, and Raman spectroscopy - Daniel Andrade Miranda; Alexandre de Oliveira Chaves; Marcos Santos Campello; Sérgio Luís Lima de Moraes Ramos (International Geology Review, 2019)

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

Zika Virus Infection of Human Mesenchymal Stem Cells Promotes Differential Expression of Proteins Linked to Several Neurological Diseases - Walter O. Beys-da-Silva; Rafael L. Rosa; Lucélia Santi; Markus Berger; Sung Kyu Park; Alexandre R. Campos; Paula Terraciano; Ana Paula M. Varela; Thais F. Teixeira; Paulo M. Roehe; André Quincozes-Santos; John R. Yates; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Optimization of treating phenol from wastewater through the TiO2-catalyzed advanced oxidation process and response surface methodology - Camila Oliveira Guimarães; Alexandre Boscaro França; Gisella Rossana Lamas Samanamud; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Seroepidemiological characterization and risk factors associated with seroconversion to Corynebacterium pseudotuberculosis in goats from Northeastern Brazil - Areano Ethério Moreira de Farias; José Romero Alexandre Alves; Francisco Selmo Fernandes Alves; Raymundo Rizaldo Pinheiro; Patrícia Yoshida Faccioli-Martins; Ana Milena César Lima; Sérgio Santos de Azevedo; Clebert José Alves (Tropical Animal Health and Production, 2019)

Detection of Enterobacterales resistant to polymyxins using Rapid Polymyxins NP test - Tanise Vendruscolo Dalmolin; Graziela Ávila Dias; Luiza Peres de Castro; Helena Ávila; Cibele Massotti Magagnin; Alexandre Prehn Zavascki; Daiana de Lima-Morales; Afonso Luís Barth (Brazilian Journal of Microbiology, 2019)

Standard area diagrams to aid assessments of the severity of blight leaf spot symptoms on cassava leaves - Iris Carolina Henrique Lima Leite; Francisco Alberto Sousa Lima Filho; Rejane Livramento Freitas-Lopes; Sami Jorge Michereff; Alexandre Sandri Capucho; Ueder Pedro Lopes (Journal of Plant Pathology, 2019)

Accuracy and efficiency of assessments of cassava brown leaf spot aided by standard area diagram sets based on whole compound leaves or single central leaflets - Francisco Alberto Sousa Lima Filho; Íris Carolina Henrique Lima Leite; Alexandre Sandri Capucho; Sami Jorge Michereff; Rejane Livramento Freitas-Lopes; Ueder Pedro Lopes (European Journal of Plant Pathology, 2019)

Invasive Melinis minutiflora outperforms native species, but the magnitude of the effect is context-dependent - Rafael D. Zenni; Alexandre B. Sampaio; Yara P. Lima; Marco Pessoa-Filho; Tulio C. L. Lins; Vania R. Pivello; Curtis Daehler (Biological Invasions, 2019)

Milk production and composition, food consumption, and energy balance of postpartum crossbred Holstein-Gir dairy cows fed two diets of different energy levels - Gustavo Bervian dos Santos; Felipe Zandonadi Brandão; Lilian dos Santos Ribeiro; Alexandre Lima Ferreira; Mariana Magalhães Campos; Fernanda Samarini Machado; Bruno Campos de Carvalho (Tropical Animal Health and Production, 2019)

An integrated analysis of mRNA and sRNA transcriptional profiles in Coffea arabica L. roots: insights on nitrogen starvation responses - Tiago Benedito dos Santos; João D. M. Soares; Joni E. Lima; Juliana C. Silva; Suzana T. Ivamoto; Viviane Y. Baba; Silvia G. H. Souza; Alan P. R. Lorenzetti; Alexandre R. Paschoal; Anderson R. Meda; Milton Y. Nishiyama Júnior; Úrsula C. de Oliveira; et al. (Functional & Integrative Genomics, 2019)

Layer-specific reduced neuronal density in the orbitofrontal cortex of older adults with obsessive–compulsive disorder - Katia Cristina de Oliveira; Lea Tenenholz Grinberg; Marcelo Queiroz Hoexter; Helena Brentani; Claudia Kimie Suemoto; Fabiano Gonçalves Nery; Luzia Carreira Lima; Ana Tereza Di Lorenzo Alho; José Marcelo Farfel; Renata Eloah de Lucena Ferretti-Rebustini; Renata Elaine Paraizo Leite; Ariane Cristine Moretto; et al. (Brain Structure and Function, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Antioxidant and antidepressant-like effects of Eugenia catharinensis D. Legrand in an animal model of depression induced by corticosterone - Sara Cristiane Barauna; Débora Delwing-Dal Magro; Maitê Beatriz Brueckheimer; Thayná P. Maia; Geraldo Antonio Bunick Neto Sala; André Wolff Döhler; Mateus Campestrini Harger; Dayse Fabiane Machado de Melo; André Luís de Gasper; Michele Debiasi Alberton; Diogo Alexandre Siebert; Gustavo Amadeu Micke; et al. (Metabolic Brain Disease, 2018)

Decreased PGC1-α levels and increased apoptotic protein signaling are associated with the maladaptive cardiac hypertrophy in hyperthyroidism - Rayane Brinck Teixeira; Tatiane Evelyn Barboza; Carla Cristina de Araújo; Rafaela Siqueira; Alexandre Luz de Castro; Jéssica Hellen Poletto Bonetto; Bruna Gazzi de Lima-Seolin; Cristina Campos Carraro; Adriane Belló-Klein; Pawan K Singal; Alex Sander da Rosa Araujo (Journal of Biosciences, 2018)

Impact of incorporating ABCB1 and CYP4F2 polymorphisms in a pharmacogenetics-guided warfarin dosing algorithm for the Brazilian population - Letícia C. Tavares; Nubia E. Duarte; Leiliane R. Marcatto; Renata A. G. Soares; Jose E. Krieger; Alexandre C. Pereira; Paulo Caleb Junior Lima Santos (European Journal of Clinical Pharmacology, 2018)

Comparing the Effects of Ferulic Acid and Sugarcane Aqueous Extract in In Vitro and In Vivo Neurotoxic Models - Aline Colonnello; Ilan Kotlar; María Eduarda de Lima; Alma Ortíz-Plata; Rodolfo García-Contreras; Félix Alexandre Antunes Soares; Michael Aschner; Abel Santamaría (Neurotoxicity Research, 2018)

Campylobacter jejuni virulence genes and immune-inflammatory biomarkers association with growth impairment in children from Northeastern Brazil - Herlice do Nascimento Veras; Pedro H. Q. S. Medeiros; Samilly A. Ribeiro; Thiago M. Freitas; Ana K. S. Santos; Marília S. M. G. Amaral; Mariana D. Bona; Alexandre Havt; Ila F. N. Lima; Noélia L. Lima; Alessandra Di Moura; Álvaro M. Leite; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Evaluation of the effectiveness of red mud-supported catalysts in combination with ozone and TiO2 in the treatment of solution containing benzene, toluene, and xylene - Bernardo Alves de Lima; Pedro Paulo Rocha de Castro; Alexandre Boscaro França; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Gisella Rossana Lamas Samanamud; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Short-term treatment with metformin reduces hepatic lipid accumulation but induces liver inflammation in obese mice - Alexandre Abilio de Souza Teixeira; Camila O. Souza; Luana A. Biondo; Loreana Sanches Silveira; Edson A. Lima; Helena A. Batatinha; Adriane Pereira Araujo; Michele Joana Alves; Sandro Massao Hirabara; Rui Curi; José Cesar Rosa Neto (Inflammopharmacology, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

A review of the palm genus Acrocomia: Neotropical green gold - Natácia Evangelista de Lima; Alexandre Assis Carvalho; Alan William Meerow; Maura Helena Manfrin (Organisms Diversity & Evolution, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Endophytic bacterial microbiome associated with leaves of genetically modified (AtAREB1) and conventional (BR 16) soybean plants - Katiúscia Kelli Montanari-Coelho; Alessandra Tenório Costa; Julio Cesar Polonio; João Lúcio Azevedo; Silvana Regina Rockenbach Marin; Renata Fuganti-Pagliarini; Yasunari Fujita; Kazuko Yamaguchi-Shinozaki; Kazuo Nakashima; João Alencar Pamphile; Alexandre Lima Nepomuceno (World Journal of Microbiology and Biotechnology, 2018)

Chemical composition, antioxidant and cytotoxic activities of extracts from the leaves of Smilax brasiliensis Sprengel (Smilacaceae) - Paula Avelar Amado; Vany Ferraz; Denise Brentan da Silva; Carlos Alexandre Carollo; Ana Hortência Fonsêca Castro; Luciana Alves Rodrigues dos Santos Lima (Natural Product Research, 2018)

Normal boundary intersection applied as multivariate and multiobjective optimization in the treatment of amoxicillin synthetic solution - Deberton Moura; Vithor Barcelos; Gisella Rossana Lamas Samanamud; Alexandre Boscaro França; Renata Lofrano; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Mateus Souza Amaral; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Comparison of the Toxic Effects of Quinolinic Acid and 3-Nitropropionic Acid in C. elegans: Involvement of the SKN-1 Pathway - Ilan Kotlar; Aline Colonnello; María Fernanda Aguilera-González; Daiana Silva Avila; María Eduarda de Lima; Rodolfo García-Contreras; Alma Ortíz-Plata; Félix Alexandre Antunes Soares; Michael Aschner; Abel Santamaría (Neurotoxicity Research, 2018)

Antiproliferative Activity and VEGF Expression Reduction in MCF7 and PC-3 Cancer Cells by Paclitaxel and Imatinib Co-encapsulation in Folate-Targeted Liposomes - Marco Júnio Peres-Filho; Alexandre Pereira dos Santos; Thais Leite Nascimento; Renato Ivan de Ávila; Fabrícia Saba Ferreira; Marize Campos Valadares; Eliana Martins Lima (AAPS PharmSciTech, 2018)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Erratum to: VOSalophen: a vanadium complex with a stilbene derivative—induction of apoptosis, autophagy, and efficiency in experimental cutaneous leishmaniasis - Patrícia de A. Machado; Jessica O. F. Moraes; Gustavo S. G. Carvalho; Wallace P. Lima; Gilson C. Macedo; Elizandra A. Britta; Celso V. Nakamura; Adilson D. da Silva; Alexandre Cuin; Elaine S. Coimbra (JBIC Journal of Biological Inorganic Chemistry, 2017)

Implementing genomic selection in sour passion fruit population - Alexandre Pio Viana; Fernando Higino de Lima e Silva; Leonardo Siqueira Glória; Rodrigo Moreira Ribeiro; Willian Krause; Marcela Santana Bastos Boechat (Euphytica, 2017)

Washout of Fine Sand Particles From a Ceramic Tile Roof: Laboratory Experiments Under Simulated Rainfall - Alexandre Silveira; João L. M. P. de Lima; João R. C. B. Abrantes; Babar Mujtaba (Water, Air, & Soil Pollution, 2017)

NDVI variation according to the time of measurement, sampling size, positioning of sensor and water regime in different soybean cultivars - Luis Guilherme Teixeira Crusiol; Josirley de Fátima Corrêa Carvalho; Rubson Natal Ribeiro Sibaldelli; Walkyria Neiverth; Alexandre do Rio; Leonardo Cesar Ferreira; Sergio de Oliveira Procópio; Liliane Márcia Mertz-Henning; Alexandre Lima Nepomuceno; Norman Neumaier; José Renato Bouças Farias (Precision Agriculture, 2017)

VOSalophen: a vanadium complex with a stilbene derivative—induction of apoptosis, autophagy, and efficiency in experimental cutaneous leishmaniasis - Patrícia de A. Machado; Jessica O. F. Morais; Gustavo S. G. Carvalho; Wallace P. Lima; Gilson C. Macedo; Elizandra A. Britta; Celso V. Nakamura; Adilson D. da Silva; Alexandre Cuin; Elaine S. Coimbra (JBIC Journal of Biological Inorganic Chemistry, 2017)

Tidal effects on phytoplankton assemblages in a near‐pristine estuary: a trait‐based approach for the case of a shallow tropical ecosystem in Brazil - Gleyci A. O. Moser; Fernanda Reinhardt Piedras; Anna Beatriz J. Oaquim; Daiana S. Souza; Suzana G. Leles; Domênica T. de Lima; Ana Beatriz A. Ramos; Cássia de O. Farias; Alexandre M. Fernandes (Marine Ecology, 2017)
The study of near‐pristine estuaries can be used as a tool for mitigation projects of harmful effects in anthropogenic eutrophic systems, since one can analyze the effect of temporal and spatial variations generated mainly by natural forces. Phytoplankton taxonomy has been used as a classical indicator to assess changes in transitional water communities, however alternative methods based on morphological, behavioral and physiological traits offer the opportunity to compare sites or moments with different taxonomic compositions. Our goal, in this context, is to evaluate phytoplankton community short‐term and seasonal variability in a near‐pristine estuary, Barra Grande estuary (Ilha Grande, RJ , Brazil), through species functional traits and thus community functional diversity. Samplings were carried out in a mooring in complete tidal cycles, seasonally during 2012. Our results showed a diverse phytoplankton community with 38 frequent and abundant taxa, marked by density variation (1.2 × 10.4–2 × 10.7 cell L −1 ) in depth, with abundance inversely related to tidal currents. The functional structure of the phytoplankton community measured by functional diversity ( FD ), varied seasonally in and across a gradient of tidal energy. A core community, mainly represented by flagellates and dinoflagellates, occurred in all observations and was highly functional (high FD ), exploiting a variety of habitats. The chain‐forming diatoms were associated with high tidal energy, and occurred in higher densities during summer. Phytoplankton cell size, cell shape, and the ability to form colonies are extremely plastic traits that can be regulated by the environment, however, isolated tychopelagic diatoms were present in the study area across all seasons, with higher contributions in autumn and winter, reflecting the shallow characteristic of this system. During the winter, an exposed sandbar was formed, and the lack of connection with the ocean resulted in an abundance of riverine and brackish water taxa. In this near‐pristine estuary the densities and occurrences of HAB phytoplankton are low. Trait‐based analyses add information about community structure, which can be impacted by anthropogenic actions in urbanized coastal systems. Thus the information provided by this study regarding phytoplankton functional diversity and its relation to nutrients and hydrography in Barra Grande Estuary can be applied as a baseline model for the development of public policies.

Inheritance of resistance to Meloidogyne enterolobii and individual selection in segregating populations of Psidium spp - Vicente Martins Gomes; Rodrigo Moreira Ribeiro; Alexandre Pio Viana; Ricardo Moreira de Souza; Eileen Azevedo Santos; Daniele Lima Rodrigues; Odimar Ferreira de Almeida (European Journal of Plant Pathology, 2017)

Spawning calls by zulega, Prochilodus argenteus, a Brazilian riverine fish - Alexandre Lima Godinho; Clarissa Chalub Fonseca Silva; Boyd Kynard (Environmental Biology of Fishes, 2017)

Determination of the Lead, Cadmium, and Chromium Concentration in Mineral Feeds and Supplements for Cattle Produced in the Mato Grosso State, Brazil - Keyla dos Santos Sigarini; Adriana Paiva de Oliveira; Daiane Lima Martins; Alexandre Silva Brasil; Kamila Cristina de Oliveira; Ricardo Dalla Villa (Biological Trace Element Research, 2017)

Capuchin monkey biogeography: understanding Sapajus Pleistocene range expansion and the current sympatry between Cebus and Sapajus - Marcela G. M. Lima; Janet C. Buckner; José de Sousa e Silva‐Júnior; Alexandre Aleixo; Amely B. Martins; Jean P. Boubli; Andrés Link; Izeni P. Farias; Maria Nazareth da Silva; Fabio Röhe; Helder Queiroz; Kenneth L. Chiou; et al. (Journal of Biogeography, 2017)
Aim Our aim was to examine gracile capuchin ( Cebus ) and robust capuchin monkey ( Sapajus ) diversification, with a focus on recent Sapajus expansion within Amazonia. We wanted to reconstruct the biogeographical history of the clade using statistical methods that model lineages’ occupation of different regions over time in order to evaluate recently proposed ‘Out of Amazonia’ and ‘Reinvasion of Amazonia’ hypotheses as alternative explanations for the extensive geographical overlap between reciprocally monophyletic gracile ( Cebus ) and robust ( Sapajus ) capuchin monkeys. Location Central and South America. Methods We reconstructed a time‐calibrated molecular phylogeny for capuchins under Bayesian inference from three mitochondrial genes. We then categorized 12 capuchin clades across four Neotropical centres of endemism and reconstructed the biogeographical history of the capuchin radiation using six models implemented in ‘BioGeo BEARS ’. We performed a phylogeographical analysis for a robust capuchin clade that spans the Atlantic Forest, Cerrado, Caatinga and Amazonia. Results We find support for a late Miocene vicariant Cebus‐Sapajus divergence and a Pleistocene Sapajus invasion of Amazonia from the Atlantic Forest. Our new analyses confirm Sapajus diversified first in the Atlantic Forest, with subsequent range expansion into widespread sympatry with Cebus in Amazonia, as well as multiple expansions into drier savanna‐like habitats. We do not find mitochondrial molecular congruence with morphological species distinctions for Sapajus flavius , S. cay , S. macrocephalus , S. libidinosus and S. apella ; instead, these five morphological types together form a single widespread clade (Bayesian posterior probability = 1) with geographical substructure and shared ancestry during the Pleistocene. Main conclusions Our results support vicariance dividing ancestral capuchin populations in Amazonia versus the Atlantic Forest, and a Pleistocene ‘Amazonian invasion’ by Sapajus to explain the present‐day sympatry of Cebus and Sapajus .

Assessment of loose and adhered urban street sediments and trace metals: a study in the city of Poços de Caldas, Brazil - Alexandre Silveira; José A. Pereira; Cristiano Poleto; João L. M. P. de Lima; Flávio A. Gonçalves; Livia A. Alvarenga; Jorge M. P. G. Isidoro (Journal of Soils and Sediments, 2016)

Connectivity maintain mammal assemblages functional diversity within agricultural and fragmented landscapes - Marcelo Magioli; Katia Maria Paschoaletto Micchi de Ferraz; Eleonore Zulnara Freire Setz; Alexandre Reis Percequillo; Michelle Viviane de Sá Santos Rondon; Vanessa Villanova Kuhnen; Mariana Cristina da Silva Canhoto; Karen Evelyn Almeida dos Santos; Claudia Zukeran Kanda; Gabriela de Lima Fregonezi; Helena Alves do Prado; Mitra Katherina Ferreira; et al. (European Journal of Wildlife Research, 2016)

Extraction process optimization of sulfated galactan-rich fractions from Hypnea musciformis in order to obtain antioxidant, anticoagulant, or immunomodulatory polysaccharides - Monique Gabriela das Chagas Faustino Alves; Jailma Almeida-Lima; Almino Afonso Oliveria Paiva; Edda Lisboa Leite; Hugo Alexandre Oliveira Rocha (Journal of Applied Phycology, 2016)

Characterization of Molecular and Physiological Responses Under Water Deficit of Genetically Modified Soybean Plants Overexpressing the AtAREB1 Transcription Factor - Juliane Prela Marinho; Norihito Kanamori; Leonardo Cesar Ferreira; Renata Fuganti-Pagliarini; Josirley de Fátima Corrêa Carvalho; Rafaela Alves Freitas; Silvana Regina Rockenbach Marin; Fabiana Aparecida Rodrigues; Liliane Márcia Mertz-Henning; José Renato Bouças Farias; Norman Neumaier; Maria Cristina Neves de Oliveira; et al. (Plant Molecular Biology Reporter, 2016)

Anti-inflammatory Effect and Toxicology Analysis of Oral Delivery Quercetin Nanosized Emulsion in Rats - Gabriela Hädrich; Gustavo Richter Vaz; Michelle Maidana; Jadel Muller Kratz; Gecioni Loch-Neckel; Daniely Cornélio Favarin; Alexandre de Paula Rogerio; Flávio Manoel Rodrigues da Silva; Ana Luiza Muccillo-Baisch; Cristiana Lima Dora (Pharmaceutical Research, 2016)

Resistance to Fusarium solani and characterization of hybrids from the cross between P. mucronata and P. edulis - Jôsie Cloviane de Oliveira Freitas; Alexandre Pio Viana; Eileen Azevedo Santos; Claudia Lougon Paiva; Fernando Higino de Lima e Silva; Antônio Teixeira do Amaral; Margarete Magalhães Souza; Vicente Musse Dias (Euphytica, 2016)

Intake, performance, and carcass characteristics of lambs fed spineless cactus replacing wheat bran - Sabrina Carla Rodrigues Felix; Ricardo Alexandre Silva Pessoa; Marcelo de Andrade Ferreira; Luciana Felizardo Pereira Soares; Janaina de Lima Silva; Karen Santos Felix de Abreu; Ana Caroline Cerqueira de Melo (Tropical Animal Health and Production, 2016)

Spatial autocorrelation analysis and ecological niche modelling allows inference of range dynamics driving the population genetic structure of a Neotropical savanna tree - José Alexandre F. Diniz‐Filho; Ana Clara O. F. Barbosa; Rosane G. Collevatti; Lázaro J. Chaves; Levi Carina Terribile; Matheus S. Lima‐Ribeiro; Mariana P. C. Telles (Journal of Biogeography, 2016)
Aim Spatial autocorrelation analysis of genetic diversity was combined with ecological niche modelling ( ENM ) to better infer how ecological and evolutionary processes underlie population structure in Eugenia dysenterica, a widely distributed tree in the ‘Cerrado’ region of Central Brazil. Location ‘Cerrado’ region, Central Brazil. Methods Data were derived from 11 microsatellite loci in 23 populations of E. dysenterica , totalling 249 allele frequencies. The expected heterozygosity ( He ) within populations and the first principal coordinates extracted from pairwise F ST and from the difference between R ST and F ST among populations were correlated with shifts in suitability from ENM . Frequencies were then analysed using a spatial autocorrelation analysis based on Moran's I and Mantel tests to contrast population differentiation for mean allele frequencies, allele size and shifts in suitability since the Last Glacial Maximum inferred from ENM . Results Spatial correlograms based on Moran's I and Mantel tests showed a linear decrease in autocorrelation with distance, which revealed north‐west–south‐east gradients in allele frequencies, genetic diversity and differences between R ST and F ST . These spatial patterns varied among loci and alleles, and the strongest spatial patterns were found for more common alleles with higher levels of differentiation among populations and for those correlated with shifts in ENM suitability. Main conclusions Current genetic diversity and population structure in E. dysenterica can be explained by geographical range shifts associated with Quaternary climate dynamics, thus demonstrating the value of applying spatial analyses to study the ecological and evolutionary processes underlying differentiation even within populations possessing a continuous distribution.

CYP2B6 rs2279343 polymorphism is associated with smoking cessation success in bupropion therapy - Paulo Roberto Xavier Tomaz; Juliana Rocha Santos; Jaqueline Scholz Issa; Tânia Ogawa Abe; Patrícia Viviane Gaya; José Eduardo Krieger; Alexandre Costa Pereira; Paulo Caleb Júnior Lima Santos (European Journal of Clinical Pharmacology, 2015)

Resistance to Cowpea aphid-borne mosaic virus in species and hybrids of Passiflora: advances for the control of the passion fruit woodiness disease in Brazil - Eileen Azevedo Santos; Alexandre Pio Viana; Josie Cloviane de Oliveira Freitas; Fernando Higino de Lima e Silva; Rosana Rodrigues; Marcelo Eiras (European Journal of Plant Pathology, 2015)

How much do we know about the endangered Atlantic Forest? Reviewing nearly 70 years of information on tree community surveys - Renato A. F. de Lima; Danilo P. Mori; Gregory Pitta; Melina O. Melito; Carolina Bello; Luiz F. Magnago; Victor P. Zwiener; Daniel D. Saraiva; Márcia C. M. Marques; Alexandre A. de Oliveira; Paulo I. Prado (Biodiversity and Conservation, 2015)

Genotype selection by REML/BLUP methodology in a segregating population from an interspecific Passiflora spp. crossing - Eileen Azevedo Santos; Alexandre Pio Viana; Josie Cloviane de Oliveira Freitas; Daniele Lima Rodrigues; Rulfe Ferreira Tavares; Claudia Lougon Paiva; Margarete Magalhães Souza (Euphytica, 2015)

Biological control of Glycaspis brimblecombei (Hemiptera: Aphalaridae) in eucalyptus plantations - Pedro José Ferreira Filho; Carlos Frederico Wilcken; Alexandre Coutinho Vianna Lima; Luiz Alexandre Nogueira de Sá; Janaina Braga do Carmo; Julio Cesar Guerreiro; José Cola Zanuncio (Phytoparasitica, 2015)

Differential effects of temperature change and human impact on European Late Quaternary mammalian extinctions - Sara Varela; Matheus Souza Lima‐Ribeiro; JosÉ Alexandre Felizola Diniz‐Filho; David Storch (Global Change Biology, 2015)
Species that inhabited Europe during the Late Quaternary were impacted by temperature changes and early humans, resulting in the disappearance of half of the European large mammals. However, quantifying the relative importance that each factor had in the extinction risk of species has been challenging, mostly due to the spatio‐temporal biases of fossil records, which complicate the calibration of realistic and accurate ecological niche modeling. Here, we overcome this problem by using ecotypes, and not real species, to run our models. We created 40 ecotypes with different temperature requirements (mean temperature from −20 °C to 25 °C and temperature range from 10 °C to 40 °C) and used them to quantify the effect of climate change and human impact. Our results show that cold‐adapted ecotypes would have been highly affected by past temperature changes in Europe, whereas temperate and warm‐adapted ecotypes would have been positively affected by temperature change. Human impact affected all ecotypes negatively, and temperate ecotypes suffered the greatest impacts. Based on these results, the extinction of cold‐adapted species like Mammuthus primigenius may be related to temperature change, while the extinction of temperate species, like Crocuta crocuta , may be related to human impact. Our results suggest that temperature change and human impact affected different ecotypes in distinct ways, and that the interaction of both impacts may have shaped species extinctions in Europe.

Antiulcerogenic activity of Carica papaya seed in rats - Lorraine Aparecida Pinto; Kátia Wolff Cordeiro; Viviane Carrasco; Carlos Alexandre Carollo; Cláudia Andréa Lima Cardoso; Eliana Janet Sanjinez Argadoña; Karine de Cássia Freitas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Variation in Guiana dolphin (Sotalia guianensis) whistles: using a broadband recording system to analyze acoustic parameters in three areas of southeastern Brazil - Luciana Guimarães de Andrade; Isabela Maria Seabra Lima; Halerson da Silva Macedo; Rafael Ramos de Carvalho; José Lailson-Brito; Leonardo Flach; Alexandre de Freitas Azevedo (acta ethologica, 2015)

Trends and correlations in annual extreme precipitation indices for mainland Portugal, 1941–2007 - M. Isabel P. de Lima; Fátima Espírito Santo; Alexandre M. Ramos; Ricardo M. Trigo (Theoretical and Applied Climatology, 2015)

Seasonal changes in daily precipitation extremes in mainland Portugal from 1941 to 2007 - Fátima Espírito Santo; Alexandre M. Ramos; M. Isabel P. de Lima; Ricardo M. Trigo (Regional Environmental Change, 2014)

Two Hundred Years of Local Avian Extinctions in Eastern Amazonia - NÁRGILA G. MOURA; ALEXANDER C. LEES; ALEXANDRE ALEIXO; JOS BARLOW; SIDNEI M. DANTAS; JOICE FERREIRA; MARIA DE FÁTIMA C. LIMA; TOBY A. GARDNER (Conservation Biology, 2014)
Local, regional, and global extinctions caused by habitat loss, degradation, and fragmentation have been widely reported for the tropics. The patterns and drivers of this loss of species are now increasingly well known in Amazonia, but there remains a significant gap in understanding of long‐term trends in species persistence and extinction in anthropogenic landscapes. Such a historical perspective is critical for understanding the status and trends of extant biodiversity as well as for identifying priorities to halt further losses. Using extensive historical data sets of specimen records and results of contemporary surveys, we searched for evidence of local extinctions of a terra firma rainforest avifauna over 200 years in a 2500 km 2 eastern Amazonian region around the Brazilian city of Belém. This region has the longest history of ornithological fieldwork in the entire Amazon basin and lies in the highly threatened Belém Centre of Endemism. We also compared our historically inferred extinction events with extensive data on species occurrences in a sample of catchments in a nearby municipality (Paragominas) that encompass a gradient of past forest loss. We found evidence for the possible extinction of 47 species (14% of the regional species pool) that were unreported from 1980 to 2013 (80% last recorded between 1900 and 1980). Seventeen species appear on the International Union for Conservation of Nature Red List, and many of these are large‐bodied. The species lost from the region immediately around Belém are similar to those which are currently restricted to well‐forested catchments in Paragominas. Although we anticipate the future rediscovery or recolonization of some species inferred to be extinct by our calculations, we also expect that there are likely to be additional local extinctions, not reported here, given the ongoing loss and degradation of remaining areas of native vegetation across eastern Amazonia. Doscientos Años de Extinciones Locales de Aves en la Amazonia Oriental

Physiological and production response of dairy goats bred in a tropical climate - Priscila Teixeira de Souza; Maria Gorete Flores Salles; Antônio Nélson Lima da Costa; Hilton Alexandre Vidal Carneiro; Leonardo Peres de Souza; Davide Rondina; Airton Alencar de Araújo (International Journal of Biometeorology, 2014)

Phytoplankton spatial distribution on the Continental Shelf off Rio de Janeiro, from Paraíba do Sul River to Cabo Frio - Gleyci A. O. Moser; Robson Alves Takanohashi; Mariana de Chagas Braz; Domênica Teixeira de Lima; Fabiana Vasconcelos Kirsten; Josefa Varela Guerra; Alexandre M. Fernandes; Ricardo César Gonçalves Pollery (Hydrobiologia, 2014)

HBV infection in HIV-infected subjects in the state of Piauí, Northeast Brazil - Evaldo H. Oliveira; Roseane M. C. Lima Verde; Luiz Marcelo L. Pinheiro; Marcos G. Benchimol; Ana Luisa E. D. Aragão; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho; Antonio C. R. Vallinoto (Archives of Virology, 2014)

Trends in seasonal surface air temperature in mainland Portugal, since 1941 - Fátima Espírito Santo; M. Isabel P. de Lima; Alexandre M. Ramos; Ricardo M. Trigo (International Journal of Climatology, 2014)
This study provides a thorough assessment of recent changes in near‐surface air temperature in mainland Portugal at both the local and regional level, focusing on extreme events (maximum and minimum) at a seasonal scale. It examines trends in selected specific indices that are calculated from daily air temperature data from 23 measuring stations scattered across the territory, recorded between 1941 and 2006. The results show overall warming trends over mainland Portugal that are consistent with the dominant global warming and reflect an increase in both maximum and minimum air temperature. When we split the study period into two sub‐periods, 1945–1975 and 1976–2006, the partial trend analysis reveals that the first sub‐period is mostly characterized by cooling followed by an even stronger tendency towards warmer benchmarks in all the indices evaluated, in particular for the warm‐related temperature extremes in spring and summer. The changes observed in seasonal patterns confirm the well‐known asymmetries in the climate in mainland Portugal and suggest that they are likely to be aggravated. There are changes associated with extreme temperatures, in particular, the significant increase in the frequency and duration of heat waves, and the increase in the frequency of hot days and tropical nights, especially in spring and summer; moreover there is a significant decrease in the frequency of cold waves and frost days. Teleconnections associated with changing patterns of temperature are also investigated. The results show that, over mainland Portugal, cold‐related air temperature extremes have been associated with the East Atlantic mode in autumn, whereas warm‐related extremes have been associated with the Scandinavia teleconnection pattern in spring, summer and autumn. However, the most prominent Northern Hemisphere pattern, the North Atlantic Oscillation, exerts limited influence, which is felt mostly in winter and spring.

Antinociceptive and anti-inflammatory effects of flavonoids PMT1 and PMT2 isolated from Piper montealegreanum Yuncker (Piperaceae) in mice - Aline Cavalcanti de Queiroz; Harley da Silva Alves; Luiz Henrique Agra Cavalcante-Silva; Thays de Lima Matos Freire Dias; Mariana da Silva Santos; Gabriela Muniz de Albuquerque Melo; Eliane Aparecida Campesatto; Maria Célia de Oliveira Chaves; Magna Suzana Alexandre-Moreira (Natural Product Research, 2014)

Phenotyping soybean plants transformed with rd29A:AtDREB1A for drought tolerance in the greenhouse and field - Amanda Alves de Paiva Rolla; Josirley de Fátima Corrêa Carvalho; Renata Fuganti-Pagliarini; Cibelle Engels; Alexandre do Rio; Silvana Regina Rockenbach Marin; Maria Cristina Neves de Oliveira; Magda A. Beneventi; Francismar Corrêa Marcelino-Guimarães; José Renato Bouças Farias; Norman Neumaier; Kazuo Nakashima; et al. (Transgenic Research, 2014)

Functional properties of a manganese-activated exo-polygalacturonase produced by a thermotolerant fungus Aspergillus niveus - Alexandre Maller; Tony Marcio da Silva; André Ricardo de Lima Damásio; Izaura Yoshico Hirata; João Atílio Jorge; Hector Francisco Terenzi; Maria de Lourdes Teixeira de Moraes Polizeli (Folia Microbiologica, 2013)

Purification, partial characterization, and covalent immobilization–stabilization of an extracellular α-amylase from Aspergillus niveus - Tony Marcio Silva; André Ricardo de Lima Damásio; Alexandre Maller; Michele Michelin; Fabio M. Squina; João Atílio Jorge; Maria de Lourdes Teixeira de Moraes Polizeli (Folia Microbiologica, 2013)

Effect of Stearic Acid on Enalapril Stability and Dissolution from Multiparticulate Solid Dosage Forms - Talita A. Cunha; Raphael C. Serpa; Ana Paula M. de Oliveira; Letícia N. Nasser; Luis Alexandre P. de Freitas; Stephania F. Taveira; Danielle G. A. Diniz; Eliana M. Lima; Ricardo N. Marreto (AAPS PharmSciTech, 2013)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Overexpression of the ABA-Dependent AREB1 Transcription Factor from Arabidopsis thaliana Improves Soybean Tolerance to Water Deficit - Elton Gargioni Grisoste Barbosa; Juliana Paula Leite; Silvana Regina Rockenbach Marin; Juliane Prela Marinho; Josirley de Fátima Corrêa Carvalho; Renata Fuganti-Pagliarini; José Renato Bouças Farias; Norman Neumaier; Francismar Corrêa Marcelino-Guimarães; Maria Cristina Neves de Oliveira; Kazuko Yamaguchi-Shinozaki; Kazuo Nakashima; et al. (Plant Molecular Biology Reporter, 2013)

Assessment of groundwater quality in a region of endemic fluorosis in the northeast of Brazil - Consuelo Fernanda Macedo de Souza; José Ferreira Lima; Maria Soraya Pereira Franco Adriano; Fabíola Galbiatti de Carvalho; Franklin Delano Soares Forte; Rosimere de Farias Oliveira; Alexandre Pessoa Silva; Fábio Correia Sampaio (Environmental Monitoring and Assessment, 2013)

Anxiogenic-like profile of Wistar adult rats based on the pilocarpine model: an animal model for trait anxiety? - Filipe S. Duarte; Marcelo Duzzioni; Alexandre A. Hoeller; Nayana M. Silva; Andy L. Ern; Tetsade C. Piermartiri; Carla I. Tasca; Elaine C. Gavioli; Tadeu Lemos; Antonio P. Carobrez; Thereza C. M. De Lima (Psychopharmacology, 2013)

CYP2C9 and VKORC1 polymorphisms influence warfarin dose variability in patients on long-term anticoagulation - Paulo Caleb Junior Lima Santos; Carla Luana Dinardo; Isolmar Tadeu Schettert; Renata Alonso Gadi Soares; Liz Kawabata-Yoshihara; Isabela Martins Bensenor; José Eduardo Krieger; Paulo Andrade Lotufo; Alexandre Costa Pereira (European Journal of Clinical Pharmacology, 2013)

Drawbacks to palaeodistribution modelling: the case of South American seasonally dry forests - Rosane G. Collevatti; Levi Carina Terribile; Guilherme de Oliveira; Matheus S. Lima‐Ribeiro; João C. Nabout; Thiago F. Rangel; Jose Alexandre F. Diniz‐Filho (Journal of Biogeography, 2013)
Aim Species distribution modelling ( SDM ) has increasingly been used to predict palaeodistributions at regional and global scales in order to understand the response of vegetation to climate change and to estimate palaeodistributions for the testing of biogeographical hypotheses. However, there are many sources of uncertainty in SDM that may restrict the ability of models to hindcast palaeo‐distributions and provide a basis for hypothesis testing in molecular phylogenetics and phylogeographical studies. Location Seasonally dry forests (SDFs) in South America. Methods We addressed the problem of using palaeodistribution modelling for SDF s based on the projection of their current distribution into past environments (21 ka) using 11 methods for SDM s and five coupled atmosphere–ocean global circulation models ( AOGCM s) for 16 species. Results We observed considerable uncertainty in the hindcasts, with the most important effects for AOGCM (median 12.2%), species (median 15.6%) and their interaction (median 13.6%). The effects of AOGCM s were stronger in the Amazon region, whereas the species effect occurred primarily in the dry areas of central Brazil. The log‐linear model detected significant effects of the three sources of variation and their interaction on the classification of each map in supporting alternative hypotheses. An expansion scenario combining the Pleistocene arc and Amazonian expansion, and Pennington's Amazonian expansion alone, were the most frequently supported palaeodistribution scenarios. Main conclusions As a basis for evaluating a given hypothesis, hindcast distributions must be used in direct association with other evidence, such as molecular variation and the fossil record. We propose an alternative framework concerning hypothesis testing that couples SDM and phylogeographical work, in which palaeoclimatic distributions and other sources of information, such as the pollen fossil record and coalescence modelling, must be weighted equally.

Anti-inflammatory and anti-arthritic activities of 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione (β-lapachone) - Marília Maria Sitônio; Carlson H. R. de Carvalho Júnior; Ingrid de A. Campos; José Bruno Nunes Ferreira Silva; Maria do Carmo Alves de Lima; Alexandre J. S. Góes; Maria Bernadete Sousa Maia; Pedro J. Rolim Neto; Teresinha G. Silva (Inflammation Research, 2013)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

Evaluating the possible anticoagulant and antioxidant effects of sulfated polysaccharides from the tropical green alga Caulerpa cupressoides var. flabellata - Mariana Santana Santos Pereira Costa; Leandro Silva Costa; Sara Lima Cordeiro; Jailma Almeida-Lima; Nednaldo Dantas-Santos; Kaline Dantas Magalhães; Diego Araujo Sabry; Ivan Rui Lopes Albuquerque; Marcia Rodrigues Pereira; Edda Lisboa Leite; Hugo Alexandre Oliveira Rocha (Journal of Applied Phycology, 2012)

Planning for optimal conservation of geographical genetic variability within species - José Alexandre Felizola Diniz-Filho; Dayane Borges Melo; Guilherme de Oliveira; Rosane Garcia Collevatti; Thannya Nascimento Soares; João Carlos Nabout; Jacqueline de Souza Lima; Ricardo Dobrovolski; Lázaro José Chaves; Ronaldo Veloso Naves; Rafael Dias Loyola; Mariana Pires de Campos Telles (Conservation Genetics, 2012)

Kinetic analysis of constructed systems for the recovery of contaminated areas by acid mine drainage - Erlon Mendes; Erilson Barros; Jairo José Zocche; Nadja Zim Alexandre; Sérgio Luciano Galatto; Marcos Back; Jader Lima Pereira; Jonathan Frassetto; Elidio Angioletto (Environmental Science and Pollution Research, 2012)

SLCO1B1 haplotypes are not associated with atorvastatin-induced myalgia in Brazilian patients with familial hypercholesterolemia - Paulo Caleb Junior Lima Santos; Ana Carolina Moron Gagliardi; Márcio Hiroshi Miname; Ana Paula Chacra; Raul Dias Santos; Jose Eduardo Krieger; Alexandre Costa Pereira (European Journal of Clinical Pharmacology, 2012)

Chronic methylphenidate administration alters antioxidant defenses and butyrylcholinesterase activity in blood of juvenile rats - Felipe Schmitz; Emilene Barros da Silva Scherer; Maira Jaqueline da Cunha; Aline Andrea da Cunha; Daniela Delwing Lima; Débora Delwing; Carlos Alexandre Netto; Angela Terezinha de Souza Wyse (Molecular and Cellular Biochemistry, 2012)

Identification of lineage III of G12 rotavirus strains in diarrheic children in the Northern Region of Brazil between 2008 and 2010 - Luana da Silva Soares; Patrícia dos Santos Lobo; Joana D’Arc Pereira Mascarenhas; Darivaldo Luz Neri; Sylvia de Fátima dos Santos Guerra; Alessilva do Socorro Lima de Oliveira; Régis Piloni Maestri; Darleise de Souza Oliveira; Euzeni Maria de Fátima Costa de Menezes; Alexandre da Costa Linhares (Archives of Virology, 2012)

High-fat diet based on dried bovine brain: an effective animal model of dyslipidemia and insulin resistance - Tiago Gomes Araújo; Ana Catarina Rezende Leite; Caíque Silveira Martins da Fonseca; Bruno Melo Carvalho; Alexandre Ricardo Pereira Schuler; Vera Lúcia de Menezes Lima (Journal of Physiology and Biochemistry, 2011)

Long-Term Runoff Modeling Using Rainfall Forecasts with Application to the Iguaçu River Basin - Alexandre Gonçalves Evsukoff; Beatriz S. L. P. de Lima; Nelson F. F. Ebecken (Water Resources Management, 2011)

Short- and long-term anxiogenic effects induced by a single injection of subconvulsant doses of pilocarpine in rats: investigation of the putative role of hippocampal pathways - Filipe Silveira Duarte; Elaine Cristina Gavioli; Marcelo Duzzioni; Alexandre Ademar Hoeller; Newton Sabino Canteras; Thereza Christina Monteiro De Lima (Psychopharmacology, 2010)

Tunicamycin inhibition of N-glycosylation of α-glucosidase from Aspergillus niveus: partial influence on biochemical properties - Tony Márcio Silva; Fausto Bruno Dos Reis Almeida; André Ricardo de Lima Damásio; Alexandre Maller; Michele Michelin; João Atílio Jorge; Ebert Seixas Hanna; Maria Cristina Roque-Barreira; Héctor F. Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Biotechnology Letters, 2010)

Chemical variations and significance of phosphates from the Fregeneda-Almendra pegmatite field, Central Iberian Zone (Spain and Portugal) - Encarnación Roda-Robles; Romeu Vieira; Alfonso Pesquera; Alexandre Lima (Mineralogy and Petrology, 2010)

Erratum to: Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Reproductive ecology of Brazilian freshwater fishes - Alexandre Lima Godinho; Ivana Reis Lamas; Hugo Pereira Godinho (Environmental Biology of Fishes, 2010)

Purification and biochemical characterization of a novel α-glucosidase from Aspergillus niveus - Tony Marcio da Silva; Michele Michelin; Andre Ricardo de Lima Damásio; Alexandre Maller; Fausto Bruno Dos Reis Almeida; Roberto Ruller; Richard John Ward; José Cesar Rosa; João Atilio Jorge; Héctor Francisco Terenzi; Maria de Lourdes Teixeira de Moraes Poliz (Antonie van Leeuwenhoek, 2009)

Nitrogen-fixing bacteria communities occurring in soils under different uses in the Western Amazon Region as indicated by nodulation of siratro (Macroptilium atropurpureum) - Adriana Silva Lima; Rafaela Simão Abrahão Nóbrega; Alexandre Barberi; Krisle da Silva; Daniel Furtado Ferreira; Fátima Maria de Souza Moreira (Plant and Soil, 2009)

Salivary cortisol in top-level professional soccer players - Alexandre Moreira; Franco Arsati; Ynara Bosco de Oliveira Lima Arsati; Danilo Augusto da Silva; Vera Cavalcanti de Araújo (European Journal of Applied Physiology, 2009)

Influence of recovery manipulation after hyperlactemia induction on the lactate minimum intensity - Luiz Fernando Paulino Ribeiro; Cássio Gustavo Santana Gonçalves; Daniele Preto Kater; Manoel Carlos Spiguel Lima; Claudio Alexandre Gobatto (European Journal of Applied Physiology, 2009)

Anticonvulsant and anxiolytic-like effects of compounds isolated from Polygala sabulosa (Polygalaceae) in rodents: in vitro and in vivo interactions with benzodiazepine binding sites - Filipe Silveira Duarte; Mariel Marder; Alexandre Ademar Hoeller; Marcelo Duzzioni; Beatriz Garcia Mendes; Moacir Geraldo Pizzolatti; Thereza Christina Monteiro De Lima (Psychopharmacology, 2008)

Respiratory stimulus in Rhizobium sp. by legume lectins - Cosme R. Martínez; Alessandro V.P. Albertini; Márcia V.B. Figueiredo; Valdinete L. Silva; Alexandre H. Sampaio; Benildo S. Cavada; José L. Lima-Filho (World Journal of Microbiology and Biotechnology, 2004)

Induction and inhibition of human lymphocyte transformation by the lectin from the red marine alga Amansia multifida - Hermenio C. Lima; Francisco H. F. Costa; Alexandre H. Sampaio; Samya A. Neves; Norma M. B. Benevides; Darlio I. A. Teixeira; David J. Rogers; Ana Lúcia P. Freitas (Journal of Applied Phycology, 1998)